Electron pump-shuttle cathode enables coupled directed-electron flows for resource-oriented treatment of radioactive wastewater - Xijun Fu; Shuai Gao; Haodong Ji; Yanbiao Liu; Sujie Yang; Binsheng He; Ping Cao; Qingyan Zhang; Le Li; Yifeng Hu; Qingyi Zeng (Water Research, 2026)

Magnet-absorbed detrital magnetite from the western Qaidam Basin: Implications to Mars sample return missions - Qi-Tao Hu; Wen-Ping Liu; Qi-Zhi Yao; Shao-Bing Zhang; Wan-Cai Li; Sheng-Quan Fu; Yi-Liang Li; Gen-Tao Zhou (Icarus, 2026)

Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

A novel control strategy: Suppressing histone acetyltransferase ClHAC703 with curcumin to prevent germination of the invasive weed Cenchrus longispinus - Xiao-Min Han; Jia-Ying Wang; Yan-Ping Fu; Bin Guo; Wei He; Ya-Hui Wei (Plant Science, 2026)

The Holocene transgression in the Bohai Sea: insights from multi-proxy sedimentary records - Lichao Tang; Ya Ping Wang; Yuanfu Yue; Wei Feng; Fu Wang; Cong-Qiang Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Assessing present-day tectonic stability, sea-level change, and tsunami hazards from a coastal multi-hazard GNSS station in the southern South China Sea - Qiang Qiu; Linlin Li; Mai Ye; Hongqiang Yang; Xingyu Song; Jian Ping Yin; Tingting Zheng; Jinghe Cao; Peitao Wang; Zhanying Chen; Zhiwen Zhang; Kuilin Xiao; et al. (Engineering Geology, 2026)

In situ construction of a Cu/Cu2O/CuO@hydrogel heterojunction catalyst: Efficient removal of cationic organic dyes irrespective of light availability - Ziyi Wang; Hao Fu; Shi Chen; Yuchao Wang; Zhi Hu; Hongmei Cao; Xiangrong Wang; Ping Zong (Colloids and Surfaces C: Environmental Aspects, 2026)

Erratum to ‘Insights into the crucial role of clay minerals in the transport of gold nanoparticles through porous media’ [Applied Clay Science 290 (2026) 108250] - Wenqi Luo; Xin Nie; Zonghua Qin; Wenbin Yu; Yuhong Fu; Ping Zeng; Qi Sun; Meizhi Yang; Liang Chen; Quan Wan (Applied Clay Science, 2026)

Object preference versus novelty preference: The importance of object selection and recommendations for the Novel Object Recognition test in mice - Yuan Yuan; Jing Li; Xiaoying Gu; Shuangshuang Ye; Yuanze Li; Zhuangfei Chen; Ping Ren; Yu Fu (Applied Animal Behaviour Science, 2026)

AIE-active photoresponsive Ir(III) complex as an oxidase mimic for ratiometric ascorbic acid detection - Qianghui Zheng; Ping Huang; Ying Peng; Mei-Jin Li; Fengfu Fu (Analytica Chimica Acta, 2026)

Tuning the signal-to-noise ratio: An electrokinetic strategy for high-fidelity SERS biosensing of microRNA-21 - Kangzhe Cao; Fan Zhang; Jiakun Zhang; Jinjin Fu; Ping Lu; Jun-Tao Cao; Huiqiao Liu (Analytica Chimica Acta, 2026)

Decadal gelatinization and phenological advancement of small jellyfish in Laizhou Bay, Bohai Sea - Ping Fu; Shan Sun; Huichao Jiang; Jianlong He; Ling Cheng; Bo Su; Hongyan Xing; Yuanqing Ma; Lijuan Liu; Yuting Zhao; Juan Zhang; Xiaowen Zhang (Marine Pollution Bulletin, 2026)

Natural-convection-dominated heat transfer from a partially-embedded high-temperature subsea pipeline: Coupled thermo-hydro-soil analysis and scaling law - Jun Cheng; Fu-Ping Gao; Jia-Hao Yu; Xu-Hui Zhang (Ocean Engineering, 2026)

Analytical modeling for uplift resistance of subsea pipelines in loose sand: Local flow-around failure mechanism and smooth-pipe validation - Xiao-Mi Li; Yu-Min Shi; Ning Wang; Xiao-Bing Lu; Fu-Ping Gao (Ocean Engineering, 2026)

Multistage metamorphism recorded by garnet amphibolites from the Xiarihamu area, NW China: Implications for Early Paleozoic tectonic evolution of the East Kunlun Orogenic Belt - Huan Tang; An-Ping Chen; Haibo Zou; Ming-Jie Zhang; Juan Zhang; Hong-Fu Zhang (Lithos, 2026)

Enhanced solar-driven interfacial vapor generation of lignite-based aerogel via water and thermal dual management - Mei Xiong; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Zhao Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2026)

Direct chiral-selective detection of (3S,3′S)-astaxanthin using hydrogel-based SERS chips - Liru Liu; Ping Cheng; Yingxiao Xiao; Sijin Chen; Yiping Zhang; Weizhu Chen; Fengfu Fu; Zhenyu Lin; Yongqiang Dong (Food Chemistry, 2026)

A non-complex-algorithmic and manually calculable fragment-resolved isotope framework ratios for geographic authentication of refined sugar - ShuoCong Li; ZhenPeng Zhen; XiaoFeng Xie; RongWei Fu; DeJin Kong; Zhu Lin; ZhaoHua Ping; GuiHua Wang; YuFeng Gao (Food Chemistry, 2026)

Role of pectin degree of esterification in the structural assembly and oxidative stability of WPI–citrus Pectin–EGCG conjugates stabilized emulsion - Guang-Lin Luo; Ping-Ping Wang; Chun Chen; Xiong Fu (Food Hydrocolloids, 2026)

A coupled model for simultaneous consolidation and decontamination in heavy metal-laden sediments dewatered by PHDs-VP - Jinxin Sun; Ping Wang; Chuanxun Li; Lijun Han; Saiou Fu; Jing Nie; Jiangshan Li (Computers and Geotechnics, 2026)

Two-dimensional metal-organic frameworks: Structural design, electron/ion transport, and energy-storage applications - Yiming Wu; Ruiying Fu; Zhishu Zheng; Xutian Yang; Hang Zhan; Hua Wu; Kuaibing Wang; Ping Yang (Chemical Engineering Journal, 2026)

Inside-out conversion of open pores into closed nanopores enables high-plateau hard carbon anodes for sodium-ion batteries - Zhuo Xiong; Rui Li; Ping Liu; Shuang Lin; Chaoshu Zhao; Wenyuan Fu; Jiale Shen; Lili Xiao; Xuedan Chen; Jianping Long; Xianguang Zeng; Anjun Hu; et al. (Chemical Engineering Journal, 2026)

Network toxicology and multi-omics reveal the mechanism of testicular toxicity induced by chronic AFB1 exposure in male quails - Zhenlei Ping; Yu Wang; Linlin Fu; Xiaoying Cui; Songtao Zheng; Xiaowen Jiang; Wenhui Yu (Journal of Hazardous Materials, 2026)

Enhanced power factor n-type carbon nanotube thermoelectric films enabled by liquid-crystal ordering for self-powered encrypted signal sensing - Qing-Yi Ma; Wen-Qian Leng; Zi-Yan Li; Fei-Peng Du; Ping Fu; Chak-Yin Tang; Chi-Pong Tsui; Wing-Cheung Law; Yun-Fei Zhang (Chemical Engineering Journal, 2026)

From bacterial template to green catalyst: Bio-fabrication of nanostructured nickel hydroxycarbonate for oxygen evolution via microbial mineralization - Feng Duan; Qichang Li; Li Xu; Haifang Wu; Ercai Pan; Wei Ding; Junhui Guo; Hang Ping; Liuyi Zhao; Hao Xie; Zhengyi Fu; Zhaoyong Zou (Chemical Engineering Journal, 2026)

Insights into the crucial role of clay minerals in the transport of gold nanoparticles through porous media - Wenqi Luo; Xin Nie; Zonghua Qin; Wenbin Yu; Yuhong Fu; Ping Zeng; Qi Sun; Meizhi Yang; Liang Chen; Quan Wan (Applied Clay Science, 2026)

Correction: Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

New linear bromopyrrole-imidazolidine alkaloids from the Formosan sponge Agelas nakamurai - You-Cheng Lin; Atallah F. Ahmed; Chung-Wei Fu; Shu-Fen Chiou; Hui-Chun Wang; Ping-Jyun Sung; Jyh-Horng Sheu (Natural Product Research, 2026)

Hydraulic connectivity of water-rich strata and directional drilling grouting for deep tunnel - Songtao Li; Yujie Wang; Ping Fu; Zhongsheng Tan; Qiang Lu; Xiaolong Pei (Journal of Mountain Science, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Self-crosslinking emulsion gels stabilized by thiolated pectin for high-efficiency curcumin encapsulation: A crosslinker-free strategy - Lv Ya-Nan; Wang Ping-Ping; Fu Xiong; Chen Chun (Food Chemistry, 2026)

Engineering Brønsted acidity of the H–ZSM–5 framework for efficient oxidative carbonylation of methane to acetic acid - Yujing Fu; Qing-Wen Song; Ping Liu (Chemical Engineering Journal, 2026)

An improved method for Gill’s hematoxylin and eosin staining based on the optimal acetic acid ratio - Zhijie Ma; Caixia Sheng; Danju Wu; Huimin An; Wen Tang; Ping Zhao; Guoxiang Fu (Histochemistry and Cell Biology, 2026)

Advances in carrier-free nanodrug delivery systems - Jin-Ye Liu; Yan-Yan Zheng; Shu-Yu Wang; Yan-Ping Bi; Ming-Shuang Sun; Ji-Fu Hao; Yu-Jing He (Drug Delivery and Translational Research, 2026)

Form-associated quality variation and exploratory transcriptome-metabolome characteristics in selected Gastrodia elata tuber samples - Rui Yang; Fu-Lai Luo; Ping Wen (Plant Biotechnology Reports, 2026)

Synthesis and biological evaluation of Phorbazole D analogues identify IO-5a as a promoter of hUC-MSC chondrogenic differentiation - Ai-zhu Wang; Xiao-mei Liu; Li-ming Zhang; Lu-lu Fu; Ping Li; Jie-ping Zhang; Hua Han (Molecular Diversity, 2026)

Novel sesquiterpenoids from Colletotrichum camelliae LP76, a predominant endophytic fungus from Camellia taliensis - Xiaoman Fu; Yuancao Shu; Zhiyu Zhang; Weihua Wang; Sida Xie; Xiaoqin Yang; Yingjun Zhang; Ping Zhao; Guolei Zhu (Natural Product Research, 2026)

Novel eudesmanolides from the flowers of Pentanema britannicum (L.) D.Gut.Larr with antidepressant activities - Yu-Qing Xie; Xin-Yue Zhang; Jun-Hui Zhang; Ping He; Sheng-He Yang; Yan Fu; Zhi-Yu Ni; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Integrated metabolomic and transcriptomic analyses reveal that pectin metabolism mediates texture divergence in grape berries - Zhi-Meng Gan; Xiao-Yan Ai; Yong Liu; Wei Zhu; Yang Zhang; Hui-Liang Wang; Fu-Rong Wang; Xiao-Dong Hou; Hua-Ping He; Lin-Zhong Gong (Postharvest Biology and Technology, 2026)

Enhanced mechanical, thermal, and rheological properties of nanocellulose-reinforced multifunctional sanxan gum hydrogels - Yue Wang; Baoping Wang; Ping Cheng; Xue Zhang; Jun Han; Fang Tian; Lina Fu; Zhiping Fan (Food and Bioproducts Processing, 2026)

Direct visual evidence of S-scheme charge transfer: CeO2 quantum dots anchored on CdS nanosheets for synergistically enhanced photocatalysis - Yaodi Fu; Ke Wen; Shimei Liu; Ping Li; Banpeng Cao; Lihong Cheng; Jingjing Liu; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Lingfang Qiu; Shuwang Duo (Environmental Research, 2026)

Effects of dietary Portulaca oleracea L. aqueous extract on growth performance, intestinal health and intestinal microflora of common carp (Cyprinus carpio) - Jing-Tong Huang; Cong-Fu Liu; Yu-Shi Cai; Li-Fang Li; Hai-Tao Zhao; Yan-Ping Yang; Rui-Fang Wang (Animal Feed Science and Technology, 2026)

Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

Study on the Dynamic Splitting Mechanical Behavior and Crack Evolution Characteristics of Potassium Salts Under High Strain Rates - Lisha Ma; Liyun Yang; Huanzhen Xie; Haoran Zhang; Wenfei Fu; Yongsheng Jia; Liang Ma; Ping Wu (Rock Mechanics and Rock Engineering, 2026)

Salt cavern identification method based on spectrum decomposition of matching pursuit algorithm - Ping Ren; Ya-ping Huang; Dong-lin Zhou; Si-han Luo; Jian-fu Wang; Jia-hao Yan; Shao-hua Liu; Zhi-feng Shi (Applied Geophysics, 2026)

Longitudinal multi-omics unveils rice-fish co-culture promotes common carp health and growth via microbiome remodeling - Chang Fang; Shi-jun Chen; Ke-ni Chen; Nian-nian Zhang; Bing Fu; Shu-ping Zhang; Si-yuan Xiong; Jia-en Zhang; Hui-rong Yang (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Generalized interpolation phase field material point method for mixed-mode rock fracture - Xiao-Ping Zhou; Chi Lv; Liang-Fu Xie (International Journal of Rock Mechanics and Mining Sciences, 2026)

Mg–K isotopic compositions deciphering mantle heterogeneity beneath southeast Tibet - Qiong Chen; Hao Cheng; Guo-Chun Zhao; Mei-Fu Zhou; Ping-Ping Liu; Wen-Jun Li; Min Sun (Geochimica et Cosmochimica Acta, 2026)

Cryoprotective effect of natural deep eutectic solvent combined with sous-vide cooking treatment on the pre-maturation and freeze-thaw cycle of Penaeus vannamei - Jing-jing Fu; Jie Deng; Bo-yang Tan; Yi-shu Ni; Xiu-ping Dong; Si-min Zhang; Yue-wen Chen (Food Chemistry, 2026)

Mutual activation of g-C3N4 and persulfate synchronizes rapid visible-light-triggered fabrication of multifunctional hydrogels - Mingming Deng; Dagang Zhou; Lin Luo; Boyi Fu; Ping Li; Qi Liu; Chi Huang (Chemical Engineering Journal, 2026)

Quantifying scale effects in pile scour depth prediction for field applications via interpretable machine learning - Yang-Xin Zhou; Qing-Kai Song; Wen-Gang Qi; Li-Jing Yang; Xiao-Bing Lu; Fu-Ping Gao (Coastal Engineering, 2026)

Fungi involved in lignin degradation and humic substances formation during composting of Chinese medicinal herbal residues - Qiannuo Zeng; Minxin Rao; Jiayi Fu; Daiying Zhang; Ping Yan; Quan Xia; Chunyi Wang; Ying Zhang (Bioresource Technology Reports, 2026)

Research Progress of Micro-mixing Technologies in Microfluidic Chips and Their Applications in Heavy Metal Detection in Seawater: A Review - Yuxuan Geng; Yanyong Liu; Longjiang Song; Junfei Wu; Ping Fu; Wenjie Zhao; Luning Jia; Yalin Yuan; Xueyong Liu (Thalassas: An International Journal of Marine Sciences, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Microscopic Hydraulic–Mechanical Coupling Fracturing Behavior and Failure Mechanisms of Reservoir Rocks - Zhi Zhao; Zhi-Hong Li; Yun-Gang Duan; Liang-Fu Xie; Zheng Li; Guo-Feng Yu; Xiao-Ping Zhou (Rock Mechanics and Rock Engineering, 2026)

Analysis of the morphological structure and metabolic characteristics of Moniezia in sheep - Qian Mu; Wan-Ling Yao; Bao-Shan Wang; Wen-Zhu Chai; Fu-Hua Liu; Zhen Huang; Yong-Cheng Meng; Jing Pan; Xi-Ping Fan; Wan-Hong He; Wang-Dong Zhang (Veterinary Parasitology, 2026)

Interpretable prediction of undrained shear strength in deep-sea soft clays using SHAP and symbolic regression - Gai-Yun Huang; Fu-Ping Gao; Yu-Min Shi; Jian-Tao Liu (Ocean Engineering, 2026)

Digital disaster prevention for ocean engineering: Current progress and future directions - Zhen-Zhong Hu; Yilin Li; Fu-Ping Gao; Jian-Min Zhang (Ocean Engineering, 2026)

Assessment of commercial NF membranes for selective separation of Mg2+/Li+ in simulated brines - Tian-tian Xue; Jian-wei Jia; Fan-xin Kong; Li-ping Yue; Guang-dong Sun; Jin-fu Chen (Journal of Water Process Engineering, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Synergistic inhibition of advanced glycation end products and enhancement of flavor by the combination of oligomeric proanthocyanidins and glycated yeast proteins - Jing-jing Fu; Bo-wen Ru; Qi-cheng Zhang; Yu-jun Wu; Hai-yang Feng; Lian-ping Zheng; Yue-wen Chen (Food Research International, 2026)

High-throughput sequencing and metabolomics reveal changes in microorganisms, volatile metabolites, and free fatty acids in preceding and after the 4th round stacked fermentation of sauce-flavored Baijiu - Shaoji Zhang; Yao Lin; Tianxiang Wu; Dandan Yuan; Shoufa Jiang; Ping Fu (Food Chemistry, 2026)

Lactiplantibacillus plantarum ZJ316 synergizes with tryptophan diet to modulate gut microbiota and metabolite profiles in mice - Qingqing Zhou; Yingying Zhou; Lu Li; Kening Fu; Shibo Liu; Ping Li; Qing Gu (Food Bioscience, 2026)

Zircon evidence for exogenous water delivery to the lunar interior - Yong Wang; Xiao-Ping Xia; Jian Xu; Yong-Sheng Liu; Christopher J. Spencer; Trevor Ireland; Ze-Xian Cui; Xiao-Jia Zeng; Jan C.M. De Hoog; Aaron J. Cavosie; Bin Fu; Qing Yang; et al. (Earth and Planetary Science Letters, 2026)

SF-based electro-responsive conductive composite NGCs promote peripheral nerve regeneration by inhibiting ferroptosis in Schwann cells - Guanjie Han; Tengfei Fu; Xingdong Xiang; Ping Wei; Lei Huang; Ning Wang; Mengxuan Bian; Shunyi Lu; Dihan Su; Jiayi Wang; Libo Jiang; Jian Zhang (Chemical Engineering Journal, 2026)

Holocene glaciers and climates inferred from quantitative reconstruction for the Rongbuk and Khumbu glaciers on the southern and northern slopes of the Mount Qomolangma - Ping Yu; Jiule Li; Xiangke Xu; Ping Fu; Hongjie Zhang; Yaqing Sun; Baiqing Xu (Journal of Geographical Sciences, 2026)

New sesquiterpenoids from the flowers of Pentanema britannicum with cytotoxicity activities - Jun-Hui Zhang; Ping He; Sheng-He Yang; Jia-Li Lang; Yan Fu; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

Application of Magnetic-Seismic Geophysical Prospecting Technology in Identifying the Carboniferous Volcanic Rocks in the Chepaizi, West Margin of Junggar Basin - Guo-hua Jiao; Wei-ping Zhang; Jin-ke Zhou; Fu-gang Sun; Hai-tao Yang; Man Li; Zhu-qiang Li (Applied Geophysics, 2026)

Eocene topography differentiation between the western and eastern North China Craton: Insights from multi-method chronometry in the northern Taihangshan Mountains - Li-Xia Feng; Ping-Ping Li; Zeng-Zhen Wang; Rong Ren; Lin Wu; Bo Zheng; Bo Liu; Jian-Qing Ji; Bao-Fu Han (Tectonophysics, 2026)

Transforming soil health with biochar-driven slow-release fertilizers: Emphasis on biochar dual-function for acidification and alkalinization reclamation - Tawasul Ali; Pingyu Qiu; Ping Liu; Nisar Muhammad; Guangquan Chen; Tengfei Fu; Changsheng Peng (Journal of Environmental Chemical Engineering, 2026)

Impacts of rainfall runoff on algal community in a humid region reservoir riverine zone - Cunli Li; Miao Yang; Aiju You; Guangwei Zhu; Ping Zhang; Qiaoxi Zheng; Mengyuan Zhu; Linxing Tu; Hongqing Zhang; Lei Fu; Bin Wang; Jinwen Hu; et al. (Journal of Environmental Chemical Engineering, 2026)

Ceramic membrane contactors for removing ammonia from wastewater: 2D model establishment and module scaling-up - Shiji Sun; Kexin Zhang; Dawei Gong; Kaiyun Fu; Xianfu Chen; Minghui Qiu; Ping Luo (Journal of Environmental Chemical Engineering, 2026)

Harnessing Machine learning to quantify ecosystem services in coastal Wetlands: A case study of the Bohai economic Rim - Ting Lu; Ya Ping Wang; Jiyuan Jin; Shibing Zhu; Jianhua Gao; Hu Ding; Qinglong Wu; Fu Wang; Chao Gao (Ecosystem Services, 2026)

An ultra-tough and impact-resistant elastomer forged by a spider silk-inspired strategy of molecular rivets and sacrificial bonds - Po Hu; Yangyu Shen; Weiming Hu; Xintong Xiao; Ping Zhang; Junwei Wang; Jiajun Fu (Chemical Engineering Journal, 2026)

Topographic primacy in rock glacier distribution revealed by GAMs and their water storage: Insights from a new polygonised inventory of the southeastern Tibetan Plateau - Ping Fu; Shuyang Xu; Tian Jia; Yang Zhan; Qian Zhang; Yingkui Li (CATENA, 2026)

Engineering stress tolerance in Saccharomyces cerevisiae by overexpressing PIR3 and SPI1 for efficient ethanol production from high-concentration sugarcane molasses - Wei-Yang Wang; Bei Liao; Ping Zheng; Ming-Yue Huang; Yu-Tuo Wei; Fu-Xing Niu (Bioresource Technology, 2026)

‘1347B’ module confers durable stripe rust resistance in wheat - Hongkui Fu; Delin Li; Huaizhi Zhang; Yongxing Chen; Ping Lu; Miaomiao Li; Gaojie Wang; Keyu Zhu; Lei Dong; Jian Yang; Chunhuan Chen; Bin Bai; et al. (Theoretical and Applied Genetics, 2026)

Unraveling iron and zinc efficiency in pepper: integration of root architecture, uptake kinetics, and transcriptional regulation - Cheng-Xiang Zhou; Wei Zhang; Bao-Gang Yu; Hao-Feng Yang; Yuan Wang; Kai Sun; Fu-Lin Zhao; Huai-Yu Yang; Prakash Lakshmanan; Xin-Ping Chen; Chun-Qin Zou (Plant and Soil, 2026)

Rapid selection of early-maturing and low-ear position maize hybrids suitable for China using genomic prediction - Ping Luo; Wenzhe Li; Lin Zhang; Jie Yang; Houwen Wang; Fei Wang; Ruisi Yang; Xinlong Xu; Ke Yang; Hongjun Yong; Mingshun Li; Jianfeng Weng; et al. (Plant Molecular Biology, 2026)

Genome-wide identification and functional characterization of the CaD27 gene family in pepper under cold stress - Jian Li; Jie Li; Hongbo Fu; Yanzhuang Wang; Juan Li; Minkun Pei; Jihua Yu; Ping Yang (Plant Molecular Biology, 2026)

Immobilization and magnetic removal of lead in contaminated soils using a waste-derived magnetic molecular sieve - Chang Lei; Xiu-Ru Xie; Lai-Shou Long; Rui Li; Zhi-Ping Fu; Zhi-Yue Zhao (Journal of Soils and Sediments, 2026)

ACT001 alleviates sepsis-induced acute lung injury by downregulating PANoptosis via the JAK2/STAT3 pathway - Nana Zhang; Hewei Zhang; Jialu Ping; Na Shen; Tao Fang; Qiang Fu (Inflammation Research, 2026)

COF-Zincon dual signal amplification: A sensitive real-time electrochemical sensor for Zn2+ detection towards anxiety disorder diagnosis - Honglong Zou; Yonggui Song; Jiaqi Shao; Bin Lai; Qinghui Fu; Zhifu Ai; Yali Liu; Yuhui Ping; Dan Su; Youhui Zhang; Huihui Liang (Analytica Chimica Acta, 2026)

Metabolic Engineering of Selenocysteine Biosynthesis and Insertion Pathway in Lactococcus Lactis - Jing-Jing Peng; Yao Qin; Shi-Yang Yue; Ping Shi; Ling-Yu Wang; Chen-Xing Liu; Yu-Hui Fang; Xiao-Dong Pei; Fu-Tian Yu; Xin-Bi Huang; Xiao-Ling Liu; Cheng-Hua Wang (Biological Trace Element Research, 2026)

Research on spontaneous combustion thermal generation and transfer effects of coal–based activated carbon and its precursors - Hui-Fei Lyu; Fu-Xing Shen; Yue Li; Cai-Ping Wang; Jun Deng; Wei-Feng Wang (Process Safety and Environmental Protection, 2026)

Proanthocyanidins in food and health: structure–activity relationships, application challenges, and emerging strategies - Ziyu Li; Wenjun Wang; Ping Cheng; Qirong Dong; Haiqi Chen; Kai Fu; Chao Fu; Yunfeng Pu; Donghong Liu (Food Chemistry, 2026)

Key structural characteristics enhancing digestion resistance in rice starch-sugarcane polyphenols complexes - Zhang Tong; Li Jia-Jiong; Fu Xiong; Wang Ping-Ping; Chen Hai-Ming; Chen Chun (Food Chemistry, 2026)

Dipole-engineered pyridinium iodide passivation for efficient Sn-Pb and all-perovskite tandem solar cells - Ciyu Ge; Chenwei Ni; Qi Xu; Bokai Hao; Wei Ai; Chengjie Deng; Peiyan Zhang; Xinzhi Zu; Hongyan Lu; Zeyu Zhang; Weijun Ke; Haisheng Song; et al. (Chemical Engineering Journal, 2026)

Solar-driven one-pot synthesis of freezing-tolerant and self-healing nanocellulose eutectogels for sustainable flexible electronics - Chaoqiang Fu; Sanwei Hao; Jun Yang; Jifei Zhang; Jialong Wen; Wenfeng Ren; Bing Wang; Ling-Ping Xiao; Changyou Shao; Runcang Sun (Chemical Engineering Journal, 2026)

Stepwise biofabrication of CuMnS from electroplating wastewater: bimetal-sulfur synergy for enhanced peroxymonosulfate activation - Xian-Zhong Fu; Yong-Qiang Ma; Xiao-Jing Zhao; Wen-Hui Xu; Chen-Xuan Li; Chun-Yan Guo; Xue-Yuan Wang; Fei-Yang Wang; You-De Zhang; Kang-Ping Cui (Bioresource Technology, 2026)

Spring frost frequency increased in North America but decreased in Eurasia from 1948 to 2016 - Wei Guo; Chuhan Lu; Ping Xia; Lijiang Fu; Govindjee Govindjee; Hao Tang; Jian Chen; Li Song; Jinglu Tan; Zhenyu Xu; Ya Guo (Theoretical and Applied Climatology, 2026)

Nitrogen-fixing bacteria and arbuscular mycorrhizal fungi alleviated nitrogen limitation in halophytes and reduced soil salinity in salt-aggregating and salt-secreting plants - Zehao Zhang; Tian Li; Rui Hu; Zhanyong Fu; Yao Zhang; Jinzhao Ma; Ping Wang; Jingkuan Sun (Plant and Soil, 2026)

On-exosome-membrane DNA polymerization-powered magneto-electrochemical aptasensing for osteosarcoma - Guang-Xian Zhong; Huang-Feng Lin; Fei-Huan Fu; Jing-Wei Zhou; Chong-Yu Chen; Chao-Yang Wu; Jian-Ping Lin; Xiong-Wei Xu; Jian-Hua Lin; Jin-Yuan Chen (Analytica Chimica Acta, 2026)

Effects of mulch drip irrigation on the coupled heat-Fe drive in root zone soils and analysis of soil Cr(Ⅵ) remediation mechanism - Mingxuan Liu; Qiang Fu; Tianxiao Li; Renjie Hou; Xiangyu Wang; Ping Xue; Xuechen Yang; Mo Li; Dong Liu; Fanying Kong (Soil and Tillage Research, 2026)

Immune modulation of Spodoptera litura larvae parasitized by Meteorus pulchricornis and role of the host β-1, 3-glucan-binding protein in parasitism success - Yan Song; Zhi-Xiang Liu; Feng-ming Gu; Ping Li; Wei-Hong Zhou; Jun Wang; Fu-An Wu; Sheng Sheng (Pesticide Biochemistry and Physiology, 2026)

Anthropogenic disturbances drive stepwise geomorphic changes of shoal-channel systems in a tide-dominated estuary - Ping Zhang; Linxi Fu; Xiangyuan Li; Jianliang Lin; Huayang Cai; Zhijun Dai; Qingshu Yang (Marine Geology, 2026)

Resource utilization of multi-source coal-based humic acid residues: Enhancing the remediation potential of cadmium pollution in water-soil-plant systems - Xiaofang Qin; Shuyue Wang; Huaqiang Zhang; Zhanyong Fu; Jingkuan Sun; Jinzhao Ma; Fei Wang; Zhanbin Huang; Zhaohua Lu; Ping Wang; Yaxuan Zhang (Journal of Water Process Engineering, 2026)

MsTIFY10a gene from alfalfa negatively regulates drought and salt tolerance in transgenic tobacco - Qi Chen; Yan Zhang; Ying Tian; Jing Xu; Qing-Wen Fu; Zhen-Yi Li; Feng-Ling Shi; Cui-Ping Gao; Zhi-Qiang Zhang (Journal of Plant Physiology, 2026)

Synergistic enhancement of bisphenol A photodegradation by BiOCl via nitrite-induced charge separation and reactive oxygen species generation: A dual role for nitrite in pollutant degradation and transformation - Zengkai Fu; Zili Lin; Junle Jian; Siling Zhang; Fengyuan Zhang; Yanfang Wang; Yunshuang He; Linsheng Liu; Yishun Wang; Hongda Zhan; Zheng Hu; Ping Chen; et al. (Journal of Environmental Chemical Engineering, 2026)

Polyetheramine-derived hydrophobic di-cationic ionic liquids for moisture tolerant and selective SF₆ recovery - Yi Pan; Fengyu Fu; Yu Dou; Bin He; Zhiyan Ma; Panpan Mi; Ping He; Wei Kou; Changli Li; Lixin Xia (Journal of Environmental Chemical Engineering, 2026)

Structure-optimized hollow carbon spheres from lignite for advanced lithium–sulfur batteries - Yao Huang; Long-Jun Zhang; Wei Wang; Zhan-Ku Li; Xu Liu; Hong-Lei Yan; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; et al. (Fuel, 2026)

Identification, antioxidant and acetylcholinesterase inhibitory activities of soluble and insoluble-bioactive components from Cinnamomum camphora seed kernel residue - Pinpin Zhang; Junmin Long; Zheling Zeng; Xianghui Yan; Yujing Yang; Rongping Fu; Yuling Lin; Deming Gong; Cheng Zeng; Ping Yu (Food Research International, 2026)

Self-assembly of bayberry-like porous BiVO4 nanospheres for self-powered marine underwater optical communication - Ping Wang; Shuai Ren; Kun Fu; Yizhou Lv; Yayue Wang; Ping Rong; Weipeng Chen; Jianhua Zhang; Xifei Li; Qi Yu (Chemical Engineering Journal, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Tracing fertilizer transformation and leaching in karst soils via soil column experiments and nitrogen isotopes - Ping Zhang; Yi-Meng Ren; Xiao-Dan Wang; Fu-Jun Yue (CATENA, 2026)

Wheat-associated Antagonistic Bacteria Exerts Biocontrol Activity Against Fungal Growth and Deoxynivalenol Production in Fusarium Graminearum - Ziting Ding; Wenjing Fu; Ping Zhou; Tao Gao; Zhitian Zheng (Current Microbiology, 2026)

Isolation and characterization of a novel reassortant H3N8 avian influenza virus from chickens in Eastern China - Ping Wang; Jiamin Fu; Han Wu; Linwei Zhu; Taoming Tang; Zhigang Wu; Linfang Cheng; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Virus Genes, 2026)

An electrocatalytic dual molecularly imprinted polymer-based biosensor enables femtomolar detection of CD44 without antibodies - Ping Xia; Cheng Chen; Ruifang Bai; Weige Dong; Yuchun Fu; Chungu Zhang; Lianhai Shan; Shun Feng (Analytica Chimica Acta, 2026)

Caffeoylquinic acid derivatives (CQAs) from Daphne gemmata and their antimicrobial activities - Lin Li; Fu-Qiang Song; Ping-Jing Yu; Li-Ping Tang; Xian Li (Natural Product Research, 2026)

Multi-stage Rotation-Stirring and Diameter-Expanding Integrated Strengthened Anchoring Technology for Large-Diameter Cable Bolts and Its Applications - Housheng Jia; Shuohui Song; Guanghui Zhi; Shaowei Liu; Mengxiong Fu; Shaolin Yin; Jinhui Guo; Ping Zhan (Rock Mechanics and Rock Engineering, 2026)

Polyprenylated xanthones with potential anti-inflammatory and anti-HIV effects from the stems and leaves of Cratoxylum cochinchinense (Lour.) Blume - Yong Zhang; You-Di Rao; Jing-Su Yu; Jia-Yi Hu; Wen-Hui Hu; Shu-Ri Li; Hui Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Enhancing oil-water separation via droplet coalescence regulated by particle self-rotation in swirling fields - Wei Zhao; Ao-song Wei; Shu Zhu; Tong Zhang; Peng-bo Fu; Jian-ping Li; Xue-jing Yang; Hua-lin Wang (Water Research, 2026)

Spatiotemporal changes in dissolved organic matter chemodiversity and its interaction with microbial composition in heavy-metal polluted river - Chun Liu; Rujie Li; Yuheng Zhang; Lijie Zhang; Zhaoling Liu; Ping Li; Guanghui Fan; Yingjie Zhu; Yue Zuo; Xule Liu; Zhiyong Fu; Xiufeng Zhang (Water Research, 2026)

Rational design of Whey protein–polysaccharide delivery systems: Synergistic mechanisms and advanced applications - Guang-Lin Luo; Ping-Ping Wang; Chun Chen; Xiong Fu (Trends in Food Science & Technology, 2026)

Interspecific interactions increase soil aggregate stability through altered root traits in long-term legume/maize intercropping - Xiao-Yang Duan; Surigaoge Surigaoge; Yu-He Du; Dai-Han Fu; Hao Yang; Xin Yang; Huai-Yin Ma; Hu Zhou; Peter Christie; Dario Fornara; Wei-Ping Zhang; Long Li (Soil and Tillage Research, 2026)

Efficient charge carrier separation over [Mo7O24]6- polyanions-intercalated porous graphitic carbon nitride for remarkably enhanced photocatalytic performance - Jiajia Liu; Yaodi Fu; Shimei Liu; Ping Li; Banpeng Cao; Lihong Cheng; Jingjing Liu; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Lingfang Qiu; Shuwang Duo (Process Safety and Environmental Protection, 2026)

An interpretable machine learning model for predicting p-y curves of monopiles in clay - Biao Li; Wen-Gang Qi; Yi-Fa Wang; Fu-Ping Gao; Lu Jing; Shun-Yi Wang; Ben He (Ocean Engineering, 2026)

Effects of biochar on farmland soil aggregate stability and phosphorus desorption - Ping Xue; Tianxiao Li; Qiang Fu; Renjie Hou; Mo Li; Song Cui; Zhaoqiang Zhou; Qinglin Li; Fanying Kong (Journal of Environmental Management, 2026)

Nickel isotopic evidence for potential deep magmatic sulfide ore bodies in orogenic settings - Peng-Yi Li; Shui-Jiong Wang; Fu-Ping Pei; Guan-Wen Yu; Bing-Qian Ding; Zi-Cheng Guan; Kai Song; Wen-Liang Xu (Geochimica et Cosmochimica Acta, 2026)

Evolution of rheological properties and prediction of mastic viscoelastic behavior of warm mix asphalt - Meiyan Huang; Jianguo Wei; Ping Li; Yuming Zhou; Yiliang Li; Qilin Fu (Fuel, 2026)

Sugarcane extract enhances stress resilience and longevity in Caenorhabditis elegans: NMR structural elucidation and transcriptomic mechanisms - Dong Yu-Hao; Chen Chun; Wang Ping-Ping; Wang Chun; Fu Xiong (Food Research International, 2026)

Self-assembled nanoparticles from sugarcane polyphenol compounds for enhanced antioxidant activity and in vivo absorption - Zhang Tong; Fang Jia-Qin; Fu Xiong; Wang Ping-Ping; Wang Chun; Fu Yu-Xuan; Chen Chun (Food Research International, 2026)

Application of nano-selenium and glutathione with pyrimethanil enhance cucumber resistance to Botrytis cinerea by boosting root secretion and recruiting beneficial microorganisms - Yujiao Jia; Lu Kang; Ping Wang; Tong Wu; Xiaorui Fu; Xiaoying Wan; Tingjie Huang; Xiangzhong Wei; Xi Wang; Yaling Bi; Canping Pan (Chemical Engineering Journal, 2026)

Physics-based unified formulation for predicting clear-water equilibrium scour depth and scour threshold velocity around piles - Wen-Gang Qi; Biao Li; Shun-Yi Wang; Yong Wan; Pei-Qing Zhao; Fu-Ping Gao (Coastal Engineering, 2026)

HSPA8 lactylation attenuates neuronal pyroptosis via E3 ligase-mediated NLRP3 degradation after ischemic stroke - Jing Fu; Liang Yu; Nengwei Yu; Ping Ni; Chaohui He; Qiao Chen; Suping Li; Fei Xu (Apoptosis, 2026)

Susceptibility of five thrips pests to spinetoram and the frequency of G275E target-site mutation in a major vegetable production region of China - Hong-Ping Tian; Hong-Xia Tian; Jin-Cui Chen; Fu-Jun Li; Jing-Jing Kang; Hui-Juan Li; Jin-Peng Gao; Guo-Cai Lu; Ya-Jun Gong; Shu-Jun Wei (Crop Protection, 2025)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Groundwater depletion in China’s Granary: The unintended consequences of cropping pattern shifts - Yiqun Shang; Jinwei Dong; Ping Fu; Nanshan You; Xi Zhang; Yuanyuan Di; Yan Zhou; Xi Chen; Zhichao Li; Xinqi Zheng (Journal of Hydrology, 2025)

Ni/Al-based additives for deep desulfurization of high-sulfur coal: Cooperative desulfurization and sulfur migration behavior - Zheng-Zhi Zhang; Zhan-Ku Li; Jing-Tao Yao; Mu-Xin Liu; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Cai Wang; Zhi-Ping Lei; Shi-Biao Ren; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

Presence of a queen (Apis mellifera) reduces the sensitivity of worker bees to environmental risks - De Fang Niu; Qiu Lan Zheng; Bin Yuan; Xiao Ling Su; Cui Ping Zhang; Yuan Yuan Lu; Ping Liu; Fu Liang Hu; Huo Qing Zheng (Journal of Asia-Pacific Entomology, 2025)

Corrigendum to “Synthesis of an autochthonous microbial community by analyzing the core microorganisms responsible for the critical flavor of bran vinegar” [Food Res. Int. 175 (2024) 113742] - Li Li; Na Li; Junjie Fu; Jun Liu; Xue Ping Wen; Hong Cao; Hongwei Xu; Ying Zhang; Rong Cao (Food Research International, 2025)

Ambient-dried polymer aerogel engineered via interparticle “stringing” towards ultrahigh robustness, flame retardancy and harsh-environment durability - Ting-Ting Li; Ting Wang; Chengxu Xu; Xue Gou; Xi-Ping Huang; Si-Yao Zhong; Zhi-Cheng Fu; Jinni Deng; Wenli An; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Tailoring anchoring functionalities of self-assembled materials for efficient wide-bandgap perovskite solar cells - Zhong-En Shi; Yu-Fan Fu; Bo-Shun Peng; Ting-Chun Hung; Deebakkrishnan Ganesan; Rajendiran Balasaravanan; Shao-Huan Hong; Cheng-Liang Liu; Chun-Jen Su; Ming-Chou Chen; Chih-Ping Chen (Chemical Engineering Journal, 2025)

Polydopamine-Ag engineered BaTiO₃ core-double-shells nanohybrids in PDMS composites for synergistically enhanced triboelectric output and antibiosis in self-sustaining wearables - Haiyan Fu; Lei Liu; Wei Liu; Zuchang Long; Ping Huang; Kai Fu; Hui Ou; Linmin Hu; Minhao Liao; Jianliang Gong (Chemical Engineering Journal, 2025)

Morphology-controlled synthesis of WO3 nanosheet arrays/nanonet via in-situ solvothermal reactions for morphology-dependent N2H4/NO2 sensing performance at near room temperature - Yanan Fu; Ping Wang; Dan Zhao; Xiaojing Bai; Lijie Zhao; Lili Sui; Bing Zhao; Yan Jiang; Haixia Yu (Chemical Engineering Journal, 2025)

Enhanced piezoelectric demulsification for high-efficiency separation of water-in-oil (W/O) emulsions based on biomimetic PVDF/liquid metal nanofiber membranes - Wen-Qiang Qiu; Jia-Qi Luo; Qing-Ke Luo; Yan-Ping Zhao; Zhi-Yu Xue; Jing-Song Tang; Hai-Feng Lu; Yi Zhang; Da-Wei Fu (Chemical Engineering Journal, 2025)

Skeletal and sedimentary structures in yardang caverns in the Mars analog, Qaidam Basin: origin and implication - Qi-Tao Hu; Wen-Ping Liu; Yu-Lu Xue; Qi-Zhi Yao; Sheng-Quan Fu; Yi-Liang Li; Gen-Tao Zhou (CATENA, 2025)

Correction: Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells - Ping Lin; Jiejun Fu; Binjiahui Zhao; Feng Lin; Haifeng Zou; Leiyu Liu; Cheng Zhu; Hongmei Wang; Xiaoguang Yu (Molecular Biology Reports, 2025)

Araloside A Induces Raf/MEK/ERK-Dependent Autophagy to Mitigate Alzheimer’s and Parkinson’s Pathology in Cellular and C. elegans Models - Xue Chen; Xing-Yue Zhou; Cai Lan; Hai-Jun Fu; Zhi-Chao Li; Meng-Yi Chen; Yong-Ping Wen; Lu Yu; Da-Lian Qin; An-Guo Wu; Jian-Ming Wu; Xiao-Gang Zhou (Molecular Neurobiology, 2025)

Licochalcone A inhibits glioma migration, invasion, and growth by triggering mitochondrial dysfunction and ROS-mediated oxidative damage - Chao Yu; Deyan Yang; Nannan Li; Xiaotong Feng; Qile Song; Fusen Zhang; Yuyang Fu; Ping Li (Molecular and Cellular Biochemistry, 2025)

Amino acid substitutions associated with adaptation of novel H10N3 and H10N5 avian influenza viruses to mice - Ping Wang; Jiamin Fu; Han Wu; Linwei Zhu; Linfang Cheng; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Archives of Virology, 2025)

Efficient socket-based data transmission method and implementation in deep learning - Xin-Jian Wei; Shu-Ping Li; Wu-Yang Yang; Xiang-Yang Zhang; Hai-Shan Li; Xin Xu; Nan Wang; Zhanbao Fu (Applied Geophysics, 2025)

Identification and characterization of the first G8P[1] sheep rotavirus strain in China: Genetic similarity to human rotavirus and zoonotic potential - DengShuai Zhao; Ping Li; Junyan Fu; YuanHang Zhang; MiaoMiao Zhang; TianYu Wang; DiXi Yu; Han Gao; LiMei Qin; MengMeng Zhao; Feng Wen; ShengFeng Chen; et al. (Veterinary Microbiology, 2025)

Effect of apparent pore-fluid compressibility and degree of saturation with atmospheric pressure on wave-induced transient pore pressure response - Wen-Gang Qi; Pei-Qing Zhao; Li-Jing Yang; Mo-Zhen Zhou; Fu-Ping Gao; Dong-Sheng Jeng (Ocean Engineering, 2025)

Spring-neap variations in tidal duration asymmetry in the Pearl River Estuary: Dominant tidal combinations and long-term evolution - Jianliang Lin; Shuai Hu; Ping Zhang; Linxi Fu; Xianzhao He; Huayang Cai; Lixia Niu; Xiaohe Zhang; Qingshu Yang (Journal of Hydrology, 2025)

Acidity-Tuned ZSM-5@Silicalite-1 Core–Shell Catalysts for Upgrading Lignite Pyrolysis Volatiles to Light Aromatics - Fu Wei; Jing-Pei Cao; Jing-Ping Zhao; Xiao-Yan Zhao (Fuel, 2025)

Corrigendum to “NIR- and pH-responsive injectable nanocomposite alginate-graft-dopamine hydrogel for melanoma suppression and wound repair” [Carbohydrate Polymers 314(2023)120899] - Ping Li; Yang Li; Rongzhan Fu; Zhiguang Duan; Chenhui Zhu; Daidi Fan (Carbohydrate Polymers, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

The role of TLR4/NF-kB signaling axis in pneumonia: from molecular mechanisms to regulation by phytochemicals - Jun Yin; Jianxiang Huang; Ping Zhou; Linwei Li; Qin Zheng; Hong Fu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Defining a Triassic carbonatite-related Mo-(REE) metallogenic belt along the southern margin of the North China Craton - Sheng-Ren Chang; Xin-Fu Zhao; Jian-Hui Su; Shao-Rui Zhao; Li-Ping Zeng; Carl Spandler (Mineralium Deposita, 2025)

Hanging drop culture reprograms mesenchymal stem cell transcriptome to enhance cell delivery efficiency via attenuated pulmonary entrapment - Hsiang-Tzu Lee; Sheng-Yung Fu; Wei-Han Weng; Wei-Chen Chao; Yu-Pao Hsu; Nan-Ping Yang; Yu-Hsu Chen; Shau-Kwaun Chen; Chien-Wen Chang (Drug Delivery and Translational Research, 2025)
The three-dimensional (3D) culture system has emerged as an indispensable platform for modulating stem cell function in biomedicine, drug screening, and cell therapy. Despite a few studies confirming the functionality of 3D culture, the molecular factors underlying this process remain obscure. Here, we have utilized a hanging drop method to generate 3D spheroid-derived mesenchymal stem cells (3D MSCs) and compared them to conventionally 2D-cultured MSCs. The results showed that 3D MSCs exhibited distinct phenotypic features than 2D-cultured MSCs and expressed different transcriptional responses, as found from RNA-Seq analysis. Gene ontology (GO) annotations and KEGG pathway mapping pinpointed that the 3D MSCs responded more actively to incoming signals as they upregulated receptors and cytokine production while downregulating proteolysis-, cytoskeletal-, extracellular matrix-, and adhesion-related genes. Functionally, these MSCs also displayed enhanced chemotaxis and improved pulmonary transgression post-intravenous injection. This study provides mechanistic insights on addressing a significant limitation of MSC therapy: pulmonary entrapment after systemic delivery. Moreover, upregulated pluripotency-associated genes, such as Oct4, Sox2, and Nanog, suggest that the 3D MSCs possessed enhanced stemness and regenerative capacity. The results indicate that 3D spheroid culture reshapes MSC transcriptomic and functional profiles and emerges as a promising strategy for improving their therapeutic potential in regenerative medicine. Graphical abstract

Crushing characteristics and energy dissipation modeling of Single-Particle-Size carbonaceous mudstone as roadbed fill - Yan Wang; Hong-yuan Fu; Jian-Ping Song; Ling Zeng; Tao Li; Jian-Ping Xiong; Hong-Ri Zhang; Wen-Guang Wang; You-Jun Li; Jing-Cheng Chen (Bulletin of Engineering Geology and the Environment, 2025)

Durability and damage mechanisms of electrolytic manganese residue-based grouting materials for seepage prevention in solid waste landfills under simulated service environments - Conggan Xu; Ping Wang; Yifu Xu; Lijun Han; Saiou Fu; Yao Qu; Yongyong Chen; Weiyu Liu; Yaoyi Wang; Zhen Qi; Jing Nie; Xuewen Lei; et al. (Journal of Environmental Management, 2025)

Tailoring molecular structure of coal tar for monolithic phenolic aerogels to reduce enthalpy for solar desalination - Yu Han; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; Lun-Jing Yan (Journal of Environmental Chemical Engineering, 2025)

Experimental study on the mechanism of CO2/external fluid interaction in shale pore structure - Jianguang Wei; Qiuyu Lu; Ao Zhang; Zhejun Pan; Guo Li; Chao Tang; Ping Fu; Haoran Cheng; Ying Yang (Fuel, 2025)

Comprehensive insights into the mechanisms influencing flavor alteration in mutton soup induced by thermal and cold sterilization: Integration of flavoromics and lipidomics - Chunyuan Ping; Xiaoping Li; Tianyang Wang; Bowen Zan; Xingyou Chen; Fu Wang; Jicai Bi; Xiang Li (Food Chemistry, 2025)

Synergistic neurotoxicity of polystyrene nanoparticles and MEHP in zebrafish (Danio rerio) - Yiyun Liu; Qi-Ping Tang; Si-Jia Zuo; Yuan Ding; Feng-Yi Guo; Bao-Fu Zhang; Qin-Hong Zhou; Dongmei Xie; De-Sheng Pei (Environmental Pollution, 2025)

Construction of Mn-UiO-66 with enhanced charge transfer for periodate-driven degradation of sulfaisoxazole: Degradation mechanisms and pathways - Junle Jian; Jin Wu; Linsheng Liu; Fengyuan Zhang; Yanfang Wang; Yunshuang He; Siling Zhang; Zhenjun Xiao; Zengkai Fu; Ping Chen; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2025)

The role of evaporites in Kiruna-type iron oxide-apatite deposits in the Northern Norrbotten region, Sweden: Evidence from in situ halogen analyses of scapolite - Li-Ping Zeng; Carl Spandler; Ying-Ying Liu; Johannes Hammerli; Wang Liao; Hao Hu; Sanna Olsson; De-Xian Zhang; Tao He; Jian-Wei Li; Xin-Fu Zhao (Chemical Geology, 2025)

Recycling of continental crust into the deep mantle in orogens: Constraints from zircon U-Pb-Hf-O and whole-rock Mg-Fe isotopes of Baihua complex, North Qinling Orogen - Gang Yang; Juan Zhang; Hong-Fu Zhang; An-Ping Chen; A-Bing Lin (Chemical Geology, 2025)

What Controls the Distribution of Ore Veins in Quartz Vein-Type Tungsten Deposits: Constrains from Fan-Shaped Mineralization in SE China - Gui-Cong Fang; Deng-Hong Wang; Fu-Qiang Yang; Zhan-Xu Ni; Chang-Shuai Huang; Ping Wang; Meng Feng; Zuo-Hai Feng (Journal of Earth Science, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Physiological and molecular responses to different sizes of polystyrene micro/nanoplastics in the model unicellular eukaryote Paramecium tetraurelia - Ping Ni; Congjun Li; Yu Fu; Naomi A. Stover; Lifang Li (Journal of Hazardous Materials, 2025)

Comparative analysis of microplastic and microbial communities in varied aquatic environments: Disparities in occurrence, interconnections, and ecological implications - Lingfang Fu; Yongxin Guo; Jialiang Tang; Mengdi Yang; Lu Huang; Jieer Xiao; Zhongya Fan; Zhongyang Wang; Jiangyu Zhi; Zhiwei Huang; Huaiyang Fang; Ping Li (Journal of Hazardous Materials, 2025)

The advantages in crop yields and carbon footprints of maize-soybean relay strip intercropping - Zhidan Fu; Ping Chen; Ping Lin; Yiling Li; Kai Luo; Chao Gao; Tian Pu; Yuze Li; Yushan Wu; Xiaochun Wang; Taiwen Yong; Wenyu Yang (Journal of Environmental Management, 2025)

Storage evolution in non-volatile and volatile lipid oxidation products of salted large yellow croaker based on targeted lipidomics and GC–MS analysis - Min Zhang; Jing-jing Fu; Jun-long Mao; Xiu-ping Dong; Yue-wen Chen (Food Chemistry, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Genomic selection for hard-to-measure traits in aquaculture: Challenges in balancing genetic gain and diversity - Ziyi Kang; Jie Kong; Qi Li; Juan Sui; Ping Dai; Kun Luo; Xianhong Meng; Baolong Chen; Jiawang Cao; Jian Tan; Qiang Fu; Zhaoxin Wang; et al. (Aquaculture, 2025)

A new benzoquinone and a new dihydroflavone from Fissistigma polyanthum and their bioactivity - Jian-Fen Xiao; Ming-Rui Yang; Pin-Xiang Fu; Rui Yang; Hong-Ping He; Hua-Yi Jiang (Phytochemistry Letters, 2025)

BarleyOmics: A comprehensive multi-omics database of barley - Junheng Zhao; Shanggeng Xie; Chenyang Zhang; Zengjie Hu; Xiangqian Lu; Nannan Zheng; Yujie Fu; Jie Yao; Ping Zhou; Danyin Huang; Zhizhong Zhang; Mengdi Li; et al. (Molecular Plant, 2025)

Temperature-dependent convection induced incremental extraction of anthocyanins from Melastoma dodecandrum Lour. Based on recyclable natural deep eutectic system - Hao Huang; Ping Ying; Ye Wang; Qinghong Wu; Lei Wang; Xizhe Fu (Food Chemistry, 2025)

High-efficient and reversible capture of protein by oxidized and carboxymethylated starch nanocrystals: Understanding interaction mechanism and regulating complexation - Wen-Xuan Hu; Jia-Yang Fu; Liang-Sen Liao; Ping Wang; Kexin Wang; Chang-Sen Jin; Xiuzhu Yu; Shuang-kui Du (Food Chemistry, 2025)

Initiatorless solar-photopolymerized heterostructured hydrogel with high performance, environmental adaptability, and recyclability - Chenghao Wang; Ping Li; Mingming Deng; Lin Luo; Boyi Fu; Qi Liu; Chi Huang (Chemical Engineering Journal, 2025)

Electroacupuncture regulates the P2X7R-NLRP3 inflammatory cascade to relieve decreased sensation on ocular surface of type 2 diabetic rats with dry eye - Mi-Mi Wan; Zhang-Yitian Fu; Tuo Jin; Zhuo-Yuan Wang; Xin-Yi Sun; Wei-Ping Gao (Purinergic Signalling, 2025)

Long-term settlement of deepsea pipelines on a soft clayey seabed: Poro-elasto-viscoplastic modeling - Jun Cheng; Jian Li; Fu-Ping Gao; Zhen-Yu Yin (Ocean Engineering, 2025)

Mechanism study of the effects of astragaloside IV and quercetin on idiopathic pulmonary fibrosis - Ye Luo; Chang-jun Xu; Xing-hui Ai; Yu-ping Li; Xing Zhu; Chang-fu Yang (Journal of Natural Medicines, 2025)

Anthropogenic nitrogen inputs favour increased nitrogen and organic carbon levels in Qinghai–Tibetan Plateau lakes: Evidence from sedimentary records - Ping Zhang; Xiangzhong Li; Fu-Jun Yue; Yuyan Zhang; Yuan Wang; Deyan Wu; Dongkun Liu; Fang Li; Xin Wang; Xuefang Ji (Water Research, 2025)

Discovery of structurally intriguing diterpenoids as anti-neuroinflammatory agents from mangrove plant Excoecaria agallocha L. via inhibiting macrophage polarization and inflammasome - Jun-Yi Li; Ming-Bin Chen; Ting-Ting Fu; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Jing Zhou; Yong Rao; Zhong-Ping Jiang; Ling Huang (Phytochemistry, 2025)

Human presence in the southeastern Tibetan Plateau after the Last Glacial Maximum - Jia-Jing Wang; Pei-Yang Tan; Yue Feng; Zhe-Xuan Zheng; Yu-Jie Guo; Jia-Ning He; You-Ping Wang; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Composite geopolymer based on copper tailings: Mechanical properties, strength models and microstructure - Wei Wang; Pengfei Wei; Ping Jiang; Na Li; Fuyong Chu; Jiajia Fu; Xudong Wang (Journal of Environmental Chemical Engineering, 2025)

BECCS carbon-negative technologies based on biomass thermochemical conversion: A review of critical pathways and research advances - Fu Wei; Shuxun Sang; Shiqi Liu; Jing-Ping Zhao; Xiao-Yan Zhao; Jing-Pei Cao (Fuel, 2025)

Lightweight deep learning model for embedded systems efficiently predicts oil and protein content in rapeseed - Mengshuai Guo; Huifang Ma; Xin Lv; Dan Wang; Li Fu; Ping He; Desheng Mei; Hong Chen; Fang Wei (Food Chemistry, 2025)

Macrogenomic and physicochemical analyses reveal microbial community and functional differences among traditional, commercial, and fortified Xiaoqu - Shaoji Zhang; Yao Lin; Tianxiang Wu; Dandan Yuan; Shoufa Jiang; Ping Fu; Wenqiang Nie (Food Bioscience, 2025)

Optimizing agricultural management practices to promote ratoon rice yield during ratoon crop: A comprehensive global meta-analysis - Shi-Wen Deng; Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Ping-Lei Gao; Mutaz Mohammed Abdallah; Muhammad Shoaib Rana; Fu-Qiang Yu; Qi-Gen Dai; Rui-Long Wang (Field Crops Research, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

The effect and mechanisms of nano cerium dioxide (Nano-CeO2) on cardiovascular development in zebrafish (Danio rerio) - Yiyun Liu; Yan-Ling Liao; Jin-Xia Wang; Bao-Fu Zhang; Qi-Ping Tang; Yuan Ding; Si-Jia Zuo; Qin-Hong Zhou; De-Sheng Pei (Environmental Pollution, 2025)

Polysaccharide network protection strategy enhances photodynamic stability: Unlocking new applications of edible pigments in fruit preservation - Bingzhi Li; Yiqi Wang; Linpin Luo; Liang Zhang; Yiya Ping; Bangfeng Fu; Wetao Zhang; Lei Liu; Jianlong Wang (Chemical Engineering Journal, 2025)

Bytes drive green: decoding the global digital economy’s environmental impact - Gen-Fu Feng; Ping-Chuan Jiang; Zhu-jia Yin; Chun-Ping Chang (Stochastic Environmental Research and Risk Assessment, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

The responses of stress tolerance, physiological performance and energy metabolism to acclimation temperature between tropical and temperate fish species - Yong-Fei Zhang; Ping Xiang; Shi-Jian Fu (Frontiers in Marine Science, 2025)
The responses of stress tolerance and other critical physiological functions of fish species to temperature fluctuations, and the potential relationships with their thermal history and natural habitat conditions, are vital for future population dynamic and distribution. In the present study, the thermal and hypoxia tolerance capacities, oxygen uptake capacity, swimming capacity and energy metabolism traits of two tropical and two temperate fish species acclimated at three temperatures were measured. Two tropical species exhibited much poorer cold tolerance than temperate species as expected. However, irrespective of thermal history, the two species preferred small and stagnant waterbody habitats exhibited greater heat tolerance capacity, lower swimming capacity, higher oxygen supply capacity. hence, higher hypoxia tolerance than the two species preferred to open waterbody. As anticipated, thermal tolerance capacity changed in parallel with acclimation temperature. However, hypoxia tolerance appeared to be the least sensitive to the acclimation temperature, suggesting it is the vital and conservative physiological function for aquatic breathe animals. One of the underlying mechanisms is the parallel increase in oxygen supply capacity with the increased energy and oxygen demanding by higher acclimation temperatures. All variables involved swimming capacity and metabolic parameters were more sensitive in the two tropical species, whereas one eury-thermal species was the least sensitive to temperature change. Moreover, the present study also suggests that in some species, maximum metabolic rate elicited by locomotion and digestion might exhibit different temperature sensitivity ranges, possibly as a result of long-term evolution in response to either habitat environment or life history traits. Nevertheless, the present study suggests that the difference in stress tolerance and other physiological functions, and their sensitivity to temperature, are shaped by both thermal history and habitat conditions. It provides important information for field conservation and the fisheries industry.

Multi-method data-driven prediction for maximum scour depth of pile foundations in clay - Qing-Kai Song; Wen-Gang Qi; Ning Wang; Fu-Ping Gao (Ocean Engineering, 2025)

Mechanochemical treatment boosted microwave-assisted sulfonation of softwood lignin for the fabrication of dye dispersant - Xu Fu; Ling-Ping Xiao; Bo-Wen Meng; Wen-Jie Li; Run-Cang Sun (Chemical Engineering Journal, 2025)

A critical life cycle assessment of present and potential rare earth circularity routes from permanent magnets - Qian-Qian Wang; Lu Wang; Shen Zhao; Fu-Ping Li; Wei-Qiang Chen; Peng Wang (Resources, Conservation and Recycling, 2025)

Carbon dots bridging interface engineering of PVDF-HFP/ZnO nanoarrays cross-linked porous membranes for wastewater purification - Ping Huang; Mingda Wang; Shunjian Xu; Lei Liu; Haiyan Fu; Wei Zhong; Jirui Fan; Wenxiang Xue; Zonghu Xiao; Jianhua Huang (Journal of Environmental Chemical Engineering, 2025)

Ultrasound-enhanced piezoelectric activation of Fe (Ⅵ) by ZnSnO3: A novel and efficient strategy for degrading sulfonamides antibiotics in unbuffered solutions - Linsheng Liu; Siling Zhang; Junle Jian; Ping Chen; Yishun Wang; Hongda Zhan; Zengkai Fu; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2025)

Experimental investigation of scour effects on regular and breaking wave loads on a monopile - Biao Li; Wen-Gang Qi; Fu-Ping Gao; Ben He; Li-Jing Yang (Coastal Engineering, 2025)

Chemical constituents of Xylanche himalaica and their chemotaxonomic significance - Wei Nie; Li-Ping Feng; Jin-Fu Wan; Xiao-Hui Li; Ying-Jie Zhang; De-Huan Fu; Qian Li (Biochemical Systematics and Ecology, 2025)

Intravenous immunoglobulin ameliorates doxorubicin-induced intestinal mucositis by inhibiting the Syk/PI3K/Akt axis and ferroptosis - Xiaochen Yan; Peng Jiang; Changqing Li; Fengjuan Liu; Ping Fu; Dengqun Liu; Xi Du; Li Ma; Tong Wang; Xin Yuan; Shengliang Ye; Zongkui Wang (Apoptosis, 2025)

Dietary supplementation of Litsea cubeba oil promotes growth and intestinal immunity in GIFT tilapia - Fu-Yan Chen; Ying Bai; Gan Yang; Han-Jing Yan; Liu-Yang Li; Zhi-Mou Liu; Ju-Ping Wen; Zhen-Bin Wang; Jun-Hong Xia; Meng-Ling He (Aquaculture, 2025)

Physical modeling of VIV hysteresis of an elastically mounted circular cylinder: Mass-damping Effect - Jun Liu; Fu-Ping Gao; Xiao-Ming Liu; Wen-Gang Qi (Ocean Engineering, 2025)

Exploring the physical disruptions of anammox granular sludge under propylene glycol stress: Implications for nitrogen removal and long-term stability - Hui-Min Fu; Xiao-Wen Jiang; Cai-Ping Sun; Shi-Jun Li; Xun Weng; Meng-Wen Peng; Peng Yan; Xiao-Wei Xu; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2025)

Interactions between riverine sediment organic matter molecular structure and microbial community as regulated by heavy metals - Ping Li; Chun Liu; Lijie Zhang; Zhaoling Liu; Zhiyong Fu; Guanghui Fan; Yingjie Zhu; Yue Zuo; Liqiong Li; Lisha Zhang (Journal of Hazardous Materials, 2025)

Engineering electron delocalization of ultrathin covalent organic framework nanosheets to elevate photocatalytic hydrogen evolution in seawater - Qihong Yue; Zhihao Zhang; Xiaoling Liu; Chenjie Zhu; Ying Wen; Ping Fu; Qizhi Hu; Xinhao Qu; Yu Zhou; Jun Wang (Chemical Engineering Journal, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Effects of plant invasion and land use change on soil labile organic carbon in southern China’s coastal wetlands - Lihua Wang; Wenjing Liu; Xueya Zhou; Shenglei Fu; Ping Yang; Chuan Tong; Hong Yang; Dongyao Sun; Linhai Zhang; Wanyi Zhu; Kam W. Tang (Soil Ecology Letters, 2025)

Simulation study of the production efficiency of family-type agricultural management entities under regulation measures on farmland: Three-stage super-SBM model considering greenhouse gas emissions - Shuqi Dong; Renjie Hou; Tianxiao Li; Qiang Fu; Ping Xue; Yu Gao; Zhaoqiang Zhou; Qinglin Li (Agricultural Systems, 2025)

Assessment of heavy metal ecological risk in typical seagrass beds of the China Yellow Sea - Sai Wang; Jing Wen; Tuan-Qi Guo; Hong-Jin Zhang; Yong-Duo Song; Guo-Ping Fu; Tuan-Tuan Wang (Aquatic Ecology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The bioactive constituents from the fruits of Elaeagnus angustifolia L. - Yang Fu; Jingya Ruan; Ping Zhang; Wei Zhang; Dingshan Yang; Yaqi Zhang; Zhunan Dang; Yi Zhang; Tao Wang (Phytochemistry, 2025)

Dynamic transformation and leaching processes of nitrogen in a karst agricultural soil under simulated rainfall conditions - Ping Zhang; Fu-Jun Yue; Xiao-Dan Wang; Sai-Nan Chen (Journal of Contaminant Hydrology, 2025)

Relationship between pyrolytic sulfur migration behavior and structural composition of high-sulfur fat coal - Zhan-Ku Li; Zheng-Zhi Zhang; Kai Zhang; Hong-Lei Yan; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Shi-Gang Kang; Heng-Fu Shui (Fuel, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Myriscagayanone C, a new compound from the fruit of myristica cagayanensis, inhibits fMLP-induced respiratory bursts by specifically preventing Akt translocation in human neutrophils - Hsiang-Ruei Liao; Chen-Lung Chen; Yu-Yao Kao; Fu-Chao Liu; Ching-Ping Tseng; Jih-Jung Chen (Chemico-Biological Interactions, 2025)

Response of soil phosphorus components to black carbon in seasonally frozen areas: Insight into ecoenzymatic stoichiometry - Ping Xue; Heng Li; Qiang Fu; Tianxiao Li; Renjie Hou; Mo Li; Song Cui; Zhaoqiang Zhou; Qinglin Li (Applied Soil Ecology, 2025)

Associations between dietary carotenoid and biological age acceleration: insights from NHANES 2009–2018 - Xinyun Chen; Chunying He; Wenhui Yu; Liang Ma; Shenju Gou; Ping Fu (Biogerontology, 2025)

The evolution and morphodynamic characteristics of shoals and troughs in Lingdingyang Bay of the Pearl River Estuary - Linxi Fu; Yuhang Zhong; Ping Zhang; Lixia Niu; Xiaohe Zhang; Jianliang Lin; Huayang Cai; Qingshu Yang (Frontiers in Marine Science, 2025)
Shoals and troughs are the fundamental geomorphological units of estuarine systems. However, their definition and morphodynamic characteristics, influenced by the complex dynamic environment, remain a critical challenge. This work introduces a depth–area spatial function as a quantitative criterion for the definition of shoals and troughs, while simultaneously elucidating their geodynamic implications. The Lingdingyang Bay (LDB) of the Pearl River Estuary serves as a case study. From 1901 to 2018, the LDB consisted of the West Shoal, Middle Shoal, and East Shoal and the West Trough and East Trough. The threshold depth of the LDB shifted from −5.75 m in 1901 to −4.75 m between 1964 and 2018. The depth–area distribution curve of the LDB exhibits two dominant peak depths (approximately 0 m and −2 m) within the shoal stable state, which categorizes shallow areas into high, medium and low tidal flats. The shoal–trough area ratio in the LDB, relative to the threshold depths, increased from 1901 to 1998, followed by a decline between 2008 and 2018, and culminated in a restoration to the level seen in 1901 (65% shoals and 35% troughs). Regional variations in dominant forces influencing shoal formation and evolution were observed by the vertical classification of the shoal state. The West Shoal is river dominated, the East Shoal is tide dominated, and the Middle Shoal reflects an interaction between riverine inflows and tides. Stabilized curves observed between 2008 and 2018 indicate that this estuary is progressively achieving new equilibrium states. The depth–area spatial function is useful for identifying shoals and troughs within various estuaries, which also provides a geomorphological framework for understanding the estuarine evolution and sediment dynamics.

The deformation characteristics of modified lightweight expanded polystyrene soils under cyclical loading - Ping Jiang; Yuming Fu; Wei Wang; Xuhui Zhou; Na Li; Huaqiang Tao (Soil Dynamics and Earthquake Engineering, 2025)

Enhancing the affinity of Pb(II) to the metastable ferrihydrite with the presence of gallic acid and anoxia condition - Hao Luo; Yingjing Tian; Fenglian Fu; Liying Bin; Weirui Chen; Ping Li; Bing Tang (Journal of Environmental Management, 2025)

Enhanced chloramphenicol biodegradation and sustainable electricity generation via co-cultured electroactive biofilms modified with in-situ self-assembled gold nanoparticles and reduced graphene oxide - Xiao-Yu Yong; Yong-Qi Jiang; Chao Wang; Jian-Mi Wang; Huan Fu; Yu-Xuan Ji; Xin-Qi Huang; Jun Zhou; Ping Wei (Journal of Environmental Management, 2025)

Unpacking greenwashing: The impact of environmental attitude, proactive strategies, and network embeddedness on corporate environmental performance - Fu Huang; Jiawei Wu; Zhanglan Wu; Weiqiong Fu; Ping Guo; Zhe Zhang; Farina Khan (Journal of Environmental Management, 2025)

Comprehensive physicochemical indicators analysis and quality evaluation model construction for the post-harvest ripening rapeseeds - Qiuhui Xu; Jie Wang; Dan Wang; Xin Lv; Li Fu; Ping He; Desheng Mei; Hong Chen; Fang Wei (Food Chemistry, 2025)

Multifunctional role of surfactant in fabricating polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Aiwen Zhang; Liheng Dai; Siyu Zhou; Wenming Fu; Mengyang Hu; Ping Xu; Pengfei Zhang; Zhan Li; Zhaohuan Mai; Hideto Matsuyama (Desalination, 2025)

Strategic PNDI(2OD)2T doping for all-perovskite tandem solar cells with enhanced efficiency and durability - Ziang Xie; Shiping Zhang; Sen Chen; Yili Pei; Li Li; Jinguang Yang; Guodong Fu; Ping Wu (Chemical Engineering Journal, 2025)

Abundant surface adsorbed oxygen species originated from defect/vacancy sites during preferential CO oxidation - Yang Liu; Kunming Hou; Zhihua Guo; Yan Guo; Yue Jiang; Xinya Wu; Zewei Fu; Heng Zhang; Ping Li; Shanghong Zeng (Chemical Engineering Journal, 2025)

Enhanced prediction of copper-polymetallic deposits in the Kalatag mining district using integrated SVM and GIS technology - Wei Xi; YuanYe Ping; JinTao Tao; XiaoYan Ye; MingRui Fu; YaWen Zhang; MiaoMiao Xie (Earth Science Informatics, 2025)

Combined effect of polystyrene nanoparticles and chlorpyrifos to Daphnia magna - Yu-Hang Zhang; Rong-Yao Gao; Few Zhu; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2024)

Technical and environmental assessment of sludge-derived slag generated from high temperature slagging co-gasification process as a sustainable construction material - Ya Zhao; Wei Ping Chan; Vernette Chin; Yinn Zhao Boon; Xiaoxu Fu; Yan Gu; James Oh; Grzegorz Lisak (Waste Management, 2024)

Mechanisms of phosphorus activation in charosphere and non-charosphere: The priming effect of biochar - Ping Xue; Renjie Hou; Qiang Fu; Tianxiao Li; Mo Li; Song Cui; Qinglin Li (Soil and Tillage Research, 2024)

Hydrogeochemical differences drive distinct microbial community assembly and arsenic biotransformation in unconfined and confined groundwater of the geothermal system - Ling-Zhi Zhang; Shi-ping Xing; Fu-Yi Huang; Wei Xiu; Jonathan R. Lloyd; Christopher Rensing; Yi Zhao; Huaming Guo (Science of The Total Environment, 2024)

Recent development on drought propagation: A comprehensive review - Zhaoqiang Zhou; Ping Wang; Linqi Li; Qiang Fu; Yibo Ding; Peng Chen; Ping Xue; Tian Wang; Haiyun Shi (Journal of Hydrology, 2024)

Critical role of soil-applied molybdenum dioxide composite biochar material in enhancing Cr(VI) remediation process: The driver of Fe(III)/Fe(II) redox cycle - Mingxuan Liu; Heng Li; Qiang Fu; Tianxiao Li; Renjie Hou; Ping Xue; Xuechen Yang; Mo Li; Dong Liu (Journal of Environmental Management, 2024)

Advances in structure-hypoglycemic activity relationship and mechanisms of berry polysaccharides - Su Jiang-Peng; Fang Jia-Qin; Liu Chuang; Liu Shou-Ping; Chen Chun; Tan Chin-Ping; Wang Ping-Ping; Peng Yun-Ping; Fu Xiong (Food Bioscience, 2024)

Biochar addition mitigates asymmetric competition of water and increases yield advantages of maize–alfalfa strip intercropping systems in a semiarid region on the Loess Plateau - Shuai hou; Xingrong Sun; Guohao Chen; Kadambot H.M. Siddique; Zelin Chen; Fu Liu; Shiyu Ping; Hongtao Lai; Hongheng Guo; Yajing An; Zhiling Lin; Zhixin Zhang; et al. (Field Crops Research, 2024)

Effects of biochar and compost on the abundant and rare microbial communities assembly and multifunctionality in pesticide-contaminated soil under freeze‒thaw cycles - Guoxin Shi; Heng Li; Qiang Fu; Tianxiao Li; Renjie Hou; Qingshan Chen; Ping Xue (Environmental Pollution, 2024)

A viscoelastic wave propagation approach for dynamic backcalculation of layer properties of asphalt pavements under an impact load - Guozhi Fu; Dandan Cao; Ghim Ping Ong; Jiaqing Wang; Dong Sha (Computers and Geotechnics, 2024)

Biomimetic Stylophora pistillata-like NiMoO4/NiFeS crystalline–amorphous phase boundary activated lattice oxygen mechanism for efficient electrochemical water oxidation - Weikai Fan; Chaofan Liu; Jiang Wu; Hao Zhou; Tao Jia; Yang Ling; Ping He; Qunzhi Zhu; Zaiguo Fu; Mingze Ou; Jia lin; Zhongwei Chen (Chemical Engineering Journal, 2024)

Effects of biochar on the transformation and utilization of nitrogen fertilizer in the black soil region of Northeast China - Guoxin Shi; Renjie Hou; Tianxiao Li; Qiang Fu; Qingshan Chen; Ping Xue; Xuechen Yang (Science of The Total Environment, 2024)

Evolution and legacy of East Asian aurochs - Jiawen Hou; Xiwen Guan; Xiaoting Xia; Yang Lyu; Xin Liu; Yuri Mazei; Ping Xie; Fengqin Chang; Xiaonan Zhang; Jialei Chen; Xinyi Li; Fengwei Zhang; et al. (Science Bulletin, 2024)

S-scheme 2D/2D B-doped N-deficient g-C3N4/ZnIn2S4 heterojunction for efficient H2 production intergrated with tertracycline degradation under visible-light illumination - Jiajia Liu; Yaodi Fu; Guoliang Chu; Ke Wen; Lingfang Qiu; Ping Li; Lihong Cheng; Banpeng Cao; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Shuwang Duo (Process Safety and Environmental Protection, 2024)

Comparative transcriptome analysis of Cyperus esculentus and C. rotundus with contrasting oil contents in tubers defines genes and regulatory networks involved in oil accumulation - Xue Bai; Mingyong Tang; Xiaodi Hu; Ping Huang; Yuan Wu; Tao Chen; Huiying He; Zeng-Fu Xu (Plant Science, 2024)

Detrital muscovite 40Ar/39Ar geochronology and provenance of Cenozoic deposits in the Qaidam basin, northern Tibetan Plateau and comparison with detrital zircon and apatite records - Shuhuai Ye; Xing Jian; Ling Fu; Wei Zhang; Xiaotian Shen; Ping Guan (Marine and Petroleum Geology, 2024)

Efficient degradation of ciprofloxacin by innovative VUV/BN system: Kinetics, mechanism and toxicity assessment - Hongda Zhan; Zili Lin; Lingrong Chen; Zhenjun Xiao; Dezhu Liu; Yishun Wang; Zhihong Chen; Zhenchao Li; Zengkai Fu; Linsheng Liu; Zihong Xu; Shuyue Chen; et al. (Journal of Water Process Engineering, 2024)

Comprehensive evaluation of phosphate deficiency tolerance in common vetch germplasms and the adaption mechanism to phosphate deficiency - Wenhui Yan; Ping Lu; Yuyan Liu; Zigang Hou; Liran Fu; Jia Shi; Guo Zhenfei; Haifeng Zhu (Journal of Plant Physiology, 2024)

Deformation prediction model of large-span prestressed structure for health monitoring based on robust Gaussian process regression - Wenwei Fu; Yi Chen; Yaozhi Luo; Hua-Ping Wan; Zhi Ma; Yanbin Shen (Engineering Structures, 2024)

N-doped carbon dots/SnS2 heterostructures for ultra-fast and sub-ppb-level detection of NO2 in multiple environments - Ping Guo; Xinxin He; Xuyang An; Xingyu Zhang; Shuai Liang; Jia Zhang; Yongqing Fu (Chemical Engineering Journal, 2024)

Highly effective fluorescence detection of UO22+ ions by an anionic Na/Eu heterometallic metal–organic framework with Lewis basic chelating sites - Feng Guo; Xue-Ling Han; Duo-Fu Li; Chun-Yang Li; Dong-Ping Li; Zhi-Kang Yao; Li-Ping Wang; Yong-Xiu Li (Chemical Engineering Journal, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Genesis of high-Al chromitites from Xiaosuihe peridotite (Central Jilin Province, NE China): Implication for initial subduction of the Paleo-Asian ocean - Bing-Qian Ding; Fu-Ping Pei; Jing-Yang Wei; Jin-Rui Zhang; Zi-Cheng Guan; Kai Song; Tian-Jiao Sang; Peng-Yi Li (Lithos, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

Scour-induced unloading effects on lateral response of large–diameter monopiles in dense sand - Li Biao; Qi Wen-Gang; Wang Yifa; Gao Fu-Ping; Wang Shun-Yi (Computers and Geotechnics, 2024)

Complex variable solution on over-/under-break shallow tunnelling in gravitational geomaterial with reasonable far-field displacement - Luo-bin Lin; Fu-quan Chen; Jin-ping Zhuang (Computers and Geotechnics, 2024)

Multifunctional and immunoregulatory microenvironment-responsive hydrogel for whole course management of infected diabetic wounds - Zhenyu Luo; Xiaoxue Fu; Hua Jiang; Weikun Meng; Shue Jin; Yongrui Cai; Ze Du; Ping Song; Anjing Chen; Li Li; Peifang Li; Jiali Chen; et al. (Chemical Engineering Journal, 2024)

Characteristics and assembly mechanisms of bacterial and fungal communities in soils from Chinese forests across different climatic zones - Ming Sheng; Wei Hu; Cong-Qiang Liu; Mutong Niu; Rui Jin; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (CATENA, 2024)

Identification of transcription factor BnHDG4-A08 as a novel candidate associated with the accumulation of oleic, linoleic, linolenic, and erucic acid in Brassica napus - Ying Fu; Min Yao; Ping Qiu; Maolin Song; Xiyuan Ni; Erli Niu; Jianghua Shi; Tanliu Wang; Yaofeng Zhang; Huasheng Yu; Lunwen Qian (Theoretical and Applied Genetics, 2024)

The Role of Nicotine Metabolic Rate on Nicotine Dependence and Rewarding: Nicotine Metabolism in Chinese Male Smokers and Male Mice - Mingda Liu; Hongjuan Wang; Yaning Fu; Xiangyu Li; Ping Wu; Guanglin Liu; Ruiyan Wang; Yuan Zhang; Huan Chen; Hongwei Hou; Qingyuan Hu (Molecular Neurobiology, 2024)

Paleozoic orogenic gold mineralization from metamorphism of volcanic sequences in the North Qinling terrane (central China): Insights from the Yindongpo gold deposit in the Tongbai area - Ming-Chun Chai; Jian-Wei Li; Ya-Fei Wu; Xiao-Ping Xia; Huai-Yu He; Wei Fu (Mineralium Deposita, 2024)

Applewood Biochar at Different Smoldering Conditions Passivates Pyrite by Promoting the Formation of Jarosite - Hecheng Fu; Jiale Fan; Jie Li; Jianhong Huang; Senlin Tian; Ping Ning (Bulletin of Environmental Contamination and Toxicology, 2024)

Allergenicity, assembly and applications of ovalbumin in egg white: a review - Bin Ma; Xing Fu; Ping Zhu; Zhaoxin Lu; Jiafeng Niu; Fengxia Lu (Critical Reviews in Food Science and Nutrition, 2024)

Real-time PCR method based on single-copy nuclear DNA sequences for the quantitative detection of pork adulteration in processed beef products - Lijuan Chang; Ping Huang; Jikai Liu; Chengping Fu; Wenjuan Liu; Yongfeng Gao; Yuanhong Li; Yongling Liu; Ailin Long (Food Control, 2024)

Corrigendum to “2′-O-galloylhyperin attenuates LPS-induced acute lung injury via upregulation antioxidation and inhibition of inflammatory responses in vivo” [Chem. Biol. Interact. 304 (1 May 2019) 20–27] - Sun-Dong Zhang; Peng Wang; Jing Zhang; Wei Wang; Li-Ping Yao; Cheng-Bo Gu; Thomas Efferth; Yu-Jie Fu (Chemico-Biological Interactions, 2024)

Discovery and Exploration of Lipid-Modifying Drug Targets for ALS by Mendelian Randomization - Zheng Jiang; Xiao-Jing Gu; Wei-Ming Su; Qing-Qing Duan; Kang-Fu Yin; Yan-Lin Ren; Yi Wang; Bei Cao; Yong-Ping Chen (Molecular Neurobiology, 2024)

Distribution and influencing factors of microeukaryote in different water layers of the southwestern Indian Ocean Ridge - Zhong Li; Chao Yuan; Ping Sun; Mingzhu Fu; Xuelei Zhang; Zongling Wang; Qinzeng Xu (Journal of Oceanology and Limnology, 2024)

Advanced strategies for conversing and fixing sulfur during waste resins oxidation through Ca/Zn oxides enhanced Na2CO3-K2CO3 system - Xin Liu; Yong-De Yan; Yun Xue; Yang-Hai Zheng; Jing-Ping Wang; Qing-Guo Zhang; Yue-Lin Wang; Fu-Qiu Ma (Process Safety and Environmental Protection, 2024)

Garciyunnanones A–R: Caged polycyclic polyprenylated acylphloroglucinols decorated with a lavandulyl substituent from Garcinia yunnanensis - Miaomiao Nan; Yueyou Yang; Ping Ying; Qiang Zheng; Youjun Wu; Tianjie Cao; Ting Li; Weiming Huang; Chuanlu Fu; Lingyi Kong; Wenjun Xu (Phytochemistry, 2024)

Extrapolating time development curves of clear-water scour around piles: From empirical fitting to physics-based approach - Shun-Yi Wang; Wen-Gang Qi; Biao Li; Zhan Wang; Fu-Ping Gao (Ocean Engineering, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

Evolution of morphology, structure, and performance of the COF membranes with monomer concentrations: Enabling effective desalination and kinetics analysis - Li-ping Yue; Fan-xin Kong; Yi Wang; Guang-dong Sun; Ai-guo Zhou; Jin-fu Chen (Desalination, 2024)

Detection of allophane by the Zhurong rover indicates water-limited alteration at Utopia Planitia, Mars - Enming Ju; Changqing Liu; Jian Chen; Xiaojia Zeng; Yanqing Xin; Ping Liu; Xiaohui Fu; Zongcheng Ling (Earth and Planetary Science Letters, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Investigation of space group effects of High-Voltage spinel LiNi0.5Mn1.5O4: Unveiling the influences of fluorinate benzimidazole salt additive - Chusnul Khotimah; Rio Akbar Yuwono; Fu-Ming Wang; Chun-Chen Yang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Arif Cahyo Imawan; Ching-Kai Chang; Ping-Hsuan Hsu; Pin-Cheng Huang; Guan-Yi Liu; Yi-De Tsai; et al. (Chemical Engineering Journal, 2024)

Tidal currents-induced scour development around pile foundations: Effects of flow velocity hydrograph - Shun-Yi Wang; Wen-Gang Qi; Biao Li; Chen Wang; Fu-Ping Gao (Coastal Engineering, 2024)

Relay intercropping boosts soybean recovery growth and delays nodule senescence to achieve yield advantages - Ping Chen; Benchuan Zheng; Huan Yang; Qing Du; Zhidan Fu; Kai Luo; Yilin Li; Ping Lin; Xihong Peng; Tian Pu; Yushan Wu; Xiaochun Wang; et al. (Agriculture, Ecosystems & Environment, 2024)

Beauveria bassiana (Ascomycota: Hypocreales) spores carried by Scleroderma guani (Hymenoptera: Bethylidae): a novel strategy for improving the control efficiency of Semanotus bifasciatus (Coleoptera: Cerambycidae) in the field - Jian-Yong Zeng; Jia-Wei Bai; Hua-Ling Wang; Xiao-Yu Su; Xue-Fei Wang; Ning-Ning Fu; Hui-Ping Li (BioControl, 2024)

IGFBP2 induces podocyte apoptosis promoted by mitochondrial damage via integrin α5/FAK in diabetic kidney disease - Xiaochen Wang; Yifan Zhang; Kun Chi; Yuwei Ji; Keying Zhang; Ping Li; Zhangning Fu; Xu Wang; Shaoyuan Cui; Wanjun Shen; Guangyan Cai; Xiangmei Chen; et al. (Apoptosis, 2024)

Role of ginsenoside Rb1 in attenuating depression-like symptoms through astrocytic and microglial complement C3 pathway - Cheng-Fu Li; Qiu-Ping Zhang; Jie Cheng; Guang-Hui Xu; Ji-Xiao Zhu; Li-Tao Yi (Metabolic Brain Disease, 2024)

Two new diarylheptanoids from the green walnut husks of Juglans mandshurica Maxim. - Yuan-Yuan Zhou; Ning-Yu Liu; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Qi-Feng Fu; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2024)

Inhibition of flowering by gibberellins in the woody plant Jatropha curcas is restored by overexpression of JcFT - Ping Huang; Jie Yang; Jiapeng Ke; Li Cai; Yingxiong Hu; Jun Ni; Chaoqiong Li; Zeng-Fu Xu; Mingyong Tang (Plant Science, 2024)

Late-fracture calcite veins decode natural gas preservation - Yijun Zheng; Yuhong Liao; Fu Wang; Wubin Yang; Yangrui Guo; Shuang Yan; Ping'an Peng (Marine and Petroleum Geology, 2024)

Eocene rhyolites in the Shanglaxiu-Xialaxiu area of north-eastern Qiangtang Block, Tibet: Partial melting of juvenile crust? - Yi-Wen Wei; Jun Wang; Qiang Wang; Bing-Zhang Wang; Andrew C. Kerr; Wu-Fu Li; Shan-Ping Li; Jin-Heng Liu; Chun-Tao Wang; Zi-Long Wang (Lithos, 2024)

Efficient capture performance and mechanism of thiadiazole-functionalized covalent organic framework for Pb(II) ion - Dawei Xiang; Hao Wang; Shixing Wang; Manying Zhu; Yuefeng Chen; Xiang Liu; Ping Li; Likang Fu (Journal of Water Process Engineering, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Ternary-coordination-regulated polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Siyu Zhou; Qiangqiang Song; Yongxuan Shi; Wenming Fu; Zhan Li; Ping Xu; Mengyang Hu; Zhaohuan Mai; Pengfei Zhang; Hideto Matsuyama (Desalination, 2024)

GHK-Cu/Pionin-loaded in situ electrospun PVB/PVP smart dressing promotes wound healing via anti-oxidant, anti-inflammatory, antimicrobial, and tissue regenerative effects - Yan Wang; Zhichao Zheng; Janak L. Pathak; Haoyu Cheng; Sizhen Huang; Zi Fu; Ping Li; Lihong Wu; Huade Zheng (Chemical Engineering Journal, 2024)

Tough and biodegradable C-lignin cross-linked polyvinyl alcohol supramolecular composite films with closed-looping recyclability - Tao Gui; Ling-Ping Xiao; Shuang-Lin Zou; Yue Zhang; Xu Fu; Chang-Hao Liu; Run-Cang Sun (Chemical Engineering Journal, 2024)

A study on construction of a prognosis model for liver cancer based on analgesic targets and screening therapeutic drugs - Xueyan Jiang; Yaodong Ping; Yuan Chen; Benben Zhu; Rong Fu; Yiwei Hao; Lei Fan (Genes & Genomics, 2024)

Microstrip isoelectric focusing with deep learning for simultaneous screening of diabetes, anemia, and thalassemia - Haodong Fu; Youli Tian; Genhan Zha; Xuan Xiao; Hengying Zhu; Qiang Zhang; Changjie Yu; Wei Sun; Chang Ming Li; Li Wei; Ping Chen; Chengxi Cao (Analytica Chimica Acta, 2024)

Optical properties and molecular compositions of dissolved organic matter in multiple runoff components during rainfalls on the karst hillslope - Yuheng Zhang; Chun Liu; Zhiyong Fu; Hongsong Chen; Chunhuan He; Kelin Wang; Ping Li (Water Research, 2024)

Seasonal characterization of chemical and optical properties of water-soluble organic aerosol in Beijing - Bo You; Zhiqiang Zhang; Aodong Du; Yan Li; Jiaxing Sun; Zhijie Li; Chun Chen; Wei Zhou; Weiqi Xu; Lu Lei; Pingqing Fu; Shengjie Hou; et al. (Science of The Total Environment, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

ZnO enhanced molten Na2CO3-K2CO3 system for simulated waste resins treatment: Efficient conversion and fixation of organic sulfur and iron(III) - Xin Liu; Yong-De Yan; Yun Xue; Yang-Hai Zheng; Yue-Lin Wang; Jing-Ping Wang; Fu-Qiu Ma (Journal of Environmental Chemical Engineering, 2024)

Correlations of dynamic changes in lipid and protein of salted large yellow croaker during storage - Min Zhang; Jing-jing Fu; Jun-long Mao; Xiu-ping Dong; Yue-wen Chen (Food Research International, 2024)

Ferulic acid alleviates avermectin induced renal injury in carp by inhibiting inflammation, oxidative stress and apoptosis - Qiulu Li; Kaixin Ping; Yannan Xiang; Ying Sun; Zunhan Hu; Shujuan Liu; Xinying Guan; Mian Fu (Fish & Shellfish Immunology, 2024)

The influence of the preheated PSf substrate on COF-LZU1 layer formation and the performance for salt and pharmaceutical rejection - Fan-xin Kong; Shi-yuan Zhang; Ding-wen Zhang; Ping Xia; Jin-fu Chen (Desalination, 2024)

Expansion-flow-modulated 3D printing of vertically aligned graphene photofuel cell - Chunjing Zhang; Xiangyu Qiao; Yihan You; Zhao He; Yifan Wang; Ping Li; Yongyi Zhang; Huili Fu; Zhengpeng Yang (Chemical Engineering Journal, 2024)

Time development of clear-water scour around a pile foundation: Phenomenological theory of turbulence-based approach - Shun-Yi Wang; Wen-Gang Qi; Fu-Ping Gao; Biao Li; Ben He (Coastal Engineering, 2024)

Optimal open nucleus breeding system for long-term genetic gain in the Pacific white shrimp using genomic selection - Ziyi Kang; Jie Kong; Juan Sui; Ping Dai; Kun Luo; Xianhong Meng; Junyu Liu; Baolong Chen; Jiawang Cao; Jian Tan; Qiang Fu; Qi Li; et al. (Aquaculture, 2024)

Reproducible responses of geochemical and microbial successional patterns in the subsurface to carbon source amendment - Jonathan P. Michael; Andrew D. Putt; Yunfeng Yang; Benjamin G. Adams; Kathryn R. McBride; Yupeng Fan; Kenneth A. Lowe; Daliang Ning; Sindhu Jagadamma; Ji Won Moon; Dawn M. Klingeman; Ping Zhang; et al. (Water Research, 2024)

Novel method for identifying the heaviest QED atom - Jing-Hang Fu; Sen Jia; Xing-Yu Zhou; Yu-Jie Zhang; Cheng-Ping Shen; Chang-Zheng Yuan (Science Bulletin, 2024)

Green production planning for circular supply chain and resource management: An empirical study for high-tech textile dyeing - Chen-Fu Chien; Ping-Chen Kuo; Pei-Ching Sun; Hsuan-An Kuo (Resources, Conservation and Recycling, 2024)

Late Quaternary glacial history of the Ulugh Muztagh, central Kunlun Mountains - Yong Sun; Chaolu Yi; Ping Fu; Qian Zhang; Xiangke Xu; Jinhua Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Micromechanical analysis of pipeline-soil interaction in unsaturated granular soil undergoing lateral ground movement - Yu Peng; Zhen-Yu Yin; Fu-Ping Gao (Computers and Geotechnics, 2024)

CFD simulation of pumping ventilation with two asymmetrically arranged openings on the rear wall in a three-story isolated building - Huai-Yu Zhong; Jie Sun; Chao Lin; Hideki Kikumoto; Wei Dong; Yang Cai; Fu-Yun Zhao; Song-Heng Wu; Fu-Ping Qian (Building and Environment, 2024)

Cevanine-type alkaloids from the bulbs of Fritillaria unibracteata var. wabuensis and their antifibrotic activities in vitro - Lu Fu; Wenyue Tian; Meng-Yu Bao; Zhiyan Liu; Wen-Jing Ren; Jiazheng Liu; Wei Zhang; Zhifeng Zhang; Jin Gao; Li-Ping Bai; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2024)

Self-floating, monolithic, and aligned phenolic carbon aerogels from coal tar for solar-driven evaporation - Hong-Lei Yan; Jin-Yuan Cheng; Zhan-Ku Li; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Fuel, 2024)

Structural characteristics and antioxidant activity of Chinese giant salamander enzymatic hydrolysate-glucose conjugates induced by ultrasound Maillard reaction - Jing-jing Fu; Fan-yu He; Xing-tong Zhu; Zhen Wang; Yang-na Huang; Jin-xiu Yu; Zhi-ping Wu; Yue-wen Chen (Food Bioscience, 2024)

Exosome-functionalized heterogeneous nanofibrous scaffolds repair bone defects accompanied by muscle injury - Shue Jin; Zeyu Luo; Yongrui Cai; Jing Wen; Pengyu Lu; Xiaoxue Fu; Ping Mou; Anjin Chen; Weikun Meng; Jidong Li; Zongke Zhou; Weinan Zeng (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Iron oxide–apatite deposits form from hydrosaline liquids exsolved from subvolcanic intrusions - Xin-Fu Zhao; Li-Ping Zeng; Wang Liao; Yi-Zhe Fan; Albert H. Hofstra; Poul Emsbo; Hao Hu; Guang Wen; Jian-Wei Li (Mineralium Deposita, 2024)

LiCOI1 mediates the biosynthesis of monoterpenes induced by methyl jasmonate in Lilium ‘Siberia’ - Zhuo Leng; Ying-Ying Li; Yu-Chen Fu; Jing Wu; Ping-Sheng Leng; Zeng-Hui Hu (Horticulture, Environment, and Biotechnology, 2024)

Combined analysis of transcriptomics and metabolomics provide insights into the antibacterial mechanism of bacteriocin XJS01 against multidrug-resistant Staphylococcus aureus - Jian-Ping Ying; Chao-Min Fu; Yan-Chun Wu; Ya-Mei Chen; Xiao-Yu Liu; Qi-Lin Zhang; Hui Liu; Ming-Zhong Liang (Science of The Total Environment, 2024)

Hedscandines A-C, three undescribed indole alkaloids from Hedyotis scandens with their anti-MRSA activity - Yu-Jun Wang; Xue Chen; Yong Yin; Wei Zhou; Pei-Fu Zhou; Ling-Gao Zeng; Chang-Hua Hu; Guo-Ping Yin (Phytochemistry, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

Co-occurrence of organophosphate esters and phosphorus fractions in river sediments: Implications for pollution prediction and environment risk assessment - Lingfang Fu; Yuxin Liu; Shu Lin; Jieer Xiao; Weijie Li; Yang Yu; Hailong Zeng; Ping Li; Huaiyang Fang (Journal of Hazardous Materials, 2024)

Devonian stratiform ironstone deposits in South China formed in a shallow marine environment of a passive continental margin - Mei-Fu Zhou; Yuanjun Jonathan Lyu; Zerui Ray Liu; Ping-Ping Liu; Lei Meng; Wenhong Johnson Qiu; Wen Winston Zhao (Journal of Asian Earth Sciences, 2024)

Combustion and emission characteristics of CNG/gasoline DFSI engine with CNG direct injection - Ping Sun; Huamei Zhu; Song Yang; Wei Dong; Xiumin Yu; Zhihao Fu (Fuel, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Mixing state and influence factors controlling diurnal variation of particulate nitrophenol compounds at a suburban area in northern China - Ziyong Guo; Xiaodong Hu; Wei Sun; Xiaocong Peng; Yuzhen Fu; Kun Liu; Fengxian Liu; He Meng; Yujiao Zhu; Guohua Zhang; Xinfeng Wang; Likun Xue; et al. (Environmental Pollution, 2024)

Silica-modified few-layered MoS2 for SWCNT-based thermoelectric materials - Duo Jiang; Zan Li; Yi Li; Chi Wang; Yannan Wang; Ping Fu; Yunfei Zhang; Feipeng Du (Chemical Engineering Journal, 2024)

Biological upcycling of nickel and sulfate as electrocatalyst from electroplating wastewater - Xian-Zhong Fu; Yu-Ru Yang; Tian Liu; Zhi-Yan Guo; Chen-Xuan Li; Hai-Yang Li; Kang-Ping Cui; Wen-Wei Li (Water Research, 2024)

Metabolic coupling of arsenic, carbon, nitrogen, and sulfur in high arsenic geothermal groundwater: Evidence from molecular mechanisms to community ecology - Ling-Zhi Zhang; Shi-ping Xing; Fu-Yi Huang; Wei Xiu; Christopher Rensing; Yi Zhao; Huaming Guo (Water Research, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

MiRNAs enabled Golden pompano (Trachinotus blochii) in response to different reoxygenation patterns after hypoxic stress - Tian Jiang; Jun Long Sun; Chun Xiu Jin; Yu Zhang; Zai Hui Tong; Yue Gu; Fu Cheng Yao; Li Ping Shi; Fei Biao Song; Jian Luo (Aquaculture, 2024)

Fluctuating redox conditions accelerate the electron storage and transfer in magnetite and production of dark hydroxyl radicals - Dan Li; Jieyi Sun; Yibo Fu; Wentao Hong; Heli Wang; Qian Yang; Junhong Wu; Sen Yang; Jianhui Xu; Yunfei Zhang; Yirong Deng; Yin Zhong; et al. (Water Research, 2024)

Evaluation of energy-environmental-economic benefits of CNG taxi policy using multi-task deep-learning-based microscopic models and big trajectory data - Bi Yu Chen; Qi Liu; Weishu Gong; Jia Tao; Hui-Ping Chen; Fu-Rong Shi (Travel Behaviour and Society, 2024)

Synthesis and application of wetland plant-based functional materials for aqueous antibiotics removal - Tao Fu; Linna Du; Suqing Wu; Min Zhao; Xiangyong Zheng; Zhiquan Wang; Yejian Zhang; Chunzhen Fan; Wen Wang; Fuyuan Ran; Ping Lin; Chunjie Zhong (Science of The Total Environment, 2024)

Detrital zircon geochronology and provenance of Cenozoic deposits in the Qaidam basin, northern Tibetan plateau: An overview with new data, implications and perspectives - Xing Jian; Ping Guan; Ling Fu; Wei Zhang; Xiaotian Shen; Hanjing Fu; Ling Wang (Marine and Petroleum Geology, 2024)

Synthesis of an autochthonous microbial community by analyzing the core microorganisms responsible for the critical flavor of bran vinegar - Li Li; Na Li; Junjie Fu; Jun Liu; Xue Ping Wen; Hong Cao; Hongwei Xu; Ying Zhang; Rong Cao (Food Research International, 2024)

Accumulation of livestock manure–derived heavy metals in the Hexi Corridor oasis agricultural alkaline soil and bioavailability to Chinese cabbage (Brassica pekinensis L.) after 4-year continuous application - Tian-Xia Guan; Zhao-Ping Lu; Ming Yue; Bao-Guo Li; Ai-Gen Fu; Xu-Dong Zhang; Zhong-Hu Li (Environmental Pollution, 2024)

Comparison studies: The aging character of mask melt blown layers, polypropylene, and polyethylene terephthalate and their adsorption behavior for tetracycline hydrochloride - Ping He; Matin Naghizadeh; Yile Fu; Sheying Dong; Tinglin Huang (Chemical Engineering Journal, 2024)

C vacancy and F decorated g-C3N4 for boosting photocatalytic ozonation of sodium p-perfluorinated nonoxybenzenesulfonate - Weirui Chen; Siyou Fu; Xukai Li; Jing Wang; Xunan Ning; Liying Bin; Ping Li; Bing Tang; Laisheng Li (Chemical Engineering Journal, 2024)

Synthesis of persistent luminescence nanocage as both drug nanocarrier and autofluorescence-free bioimaging agent for the theranostics of bacterial infection - Xuan Fu; Li-Xia Yan; Xu Zhao; Li-Jian Chen; Xiu-Ping Yan (Chemical Engineering Journal, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

Trace element systematics of magnetite from alkaline mafic–ultramafic intrusions of the Permian Emeishan large igneous province, SW China - Zhen-Chao Wang; Xiao-Wen Huang; Ping-Ping Liu; Mei-Fu Zhou (Contributions to Mineralogy and Petrology, 2024)

Lipidomics reveals the relationship between lipid oxidation and flavor formation of basic amnio acids participated Low-Sodium cured large yellow croaker - Min Zhang; Jing-Jing Fu; Jun-Long Mao; Xiu-Ping Dong; Yue-Wen Chen (Food Chemistry, 2023)

Interfacial adsorption of gold nanoparticles on arsenian pyrite: New insights for the transport and deposition of gold nanoparticles - Xin Nie; Quan Wan; Michael F. Hochella; Suxing Luo; Meizhi Yang; Shanshan Li; Yuhong Fu; Ping Zeng; Zonghua Qin; Wenbin Yu (Chemical Geology, 2023)

A Strategy for Reducing Nitrogen Fertilizer Application Based on Application of Biochar: A Case in Northeast China Black Soil Region (Mollisols) - Qinglin Li; Qiang Fu; Tianxiao Li; Renjie Hou; Shuqi Dong; Ping Xue; Xuechen Yang; Yu Gao (Journal of Soil Science and Plant Nutrition, 2023)

Establishment and characterization of a novel hilar cholangiocarcinoma cell line, CBC3T-1 - Mingzhen Bai; Ningzu Jiang; Wenkang Fu; Chongfei Huang; Liang Tian; Ningning Mi; Long Gao; Haidong Ma; Yawen Lu; Jie Cao; Chao Zhang; Ping Yue; et al. (Human Cell, 2023)
Cholangiocarcinoma (CCA) is a group of malignant heterogeneous cancer arising from the biliary tree. The tumor is characterized by insidious onset, high degree of malignancy, poor prognosis, and high recurrence rate. Immortalized cancer cell lines are the best and easiest models for in vitro cancer research. Here, we established a naturally immortalized highly tumorigenic hilar cholangiocarcinoma (hCCA) cell line, CBC3T-1. The CBC3T-1 cell line was cultured for over 60 passages. Thorough analysis showed that CBC3T-1 cells share characteristics similar to original tumor cells from patients with cholangiocarcinoma and display a stable phenotype, including features of epithelial origin, stem cell-like properties, as well as a high invasive and migratory capability and tumorigenicity in mice. Furthermore, this cell line showed the best sensitivity to paclitaxel, followed by gemcitabine. RNA sequencing and whole‑exome sequencing showed that cancer-associated pathways and somatic mutations played a dominant role in the development of CCA. We established and characterized a new hCCA cell line, CBC3T-1, which contributes to a better understanding of bile duct cancer, and can be used to study tumorigenesis and progression and the role of anticancer drugs.

Factors affecting the accumulation of organotins by wild fish: A case study in the Three Gorges Reservoir, China - Jun-min Gao; Jia You; Jing-cheng Wu; Jin-song Guo; Ping-ting Fu; Li-xia Zhang (Environmental Science and Pollution Research, 2023)

Cretaceous Nb-enriched basalts in the western Gan-Hang belt, South China: A response to slab window opening during the Paleo-Pacific ridge subduction - Qiong Chen; Mei-Fu Zhou; Min Sun; Hao Cheng; Ping-Ping Liu (Lithos, 2023)

Iron blocks autophagic flux and induces autophagosomes accumulation in microglia - Deqiang Fu; Xingyue Liang; Yuxuan Jiang; Jieping Liu; Xiaosi Lin; Quan Yang; Xue Chen; Ping Huang; Wei Wang; Wenlin Wu (Food and Chemical Toxicology, 2023)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

Amino acids as in-situ electron donors drive medium chain fatty acids production from sludge acidogenic fermentation liquid by electro-fermentation enhancement - Ping Wu; Peng Ding; Qi-hao Cao; Chao Zhang; Bo Fu; Hong-bo Liu; Chong-jun Chen; He Liu (Chemical Engineering Journal, 2023)

Transcriptome Analysis Revealed the Differential Molecular Response Mechanisms of Roots, Stems, and Leaves in Mung Bean to Cadmium Stress - Ping-min Wu; Yan Leng; Shi-Weng Li; Yu-Lin Wang; Fu-Jun Qiao (Journal of Plant Growth Regulation, 2023)

Livestock wastes from family-operated farms are potential important sources of potentially toxic elements, antibiotics, and estrogens in rural areas in North China - Yang Li; Xinyu Li; Xupu Ma; Tianlei Qiu; Xincheng Fu; Zhihong Ma; Hua Ping; Cheng Li (Environmental Science and Pollution Research, 2023)

A novel “Turn-on” fluorometric assays triggered reaction for β-glucosidase activity based on quercetin derived silicon nanoparticles and its potential use for cell imaging - Yves Iradukunda; Jing-Yan Kang; Xiao-bo Zhao; Stanislas Nsanzamahoro; Xiao-Kang Fu; Jia Liu; Yu-Zhu Ding; Wei Ha; Yan-Ping Shi (Analytica Chimica Acta, 2023)

Invasive Asteraceae plants can enhance community stability by changing pollination network structure, yet cause intense pollen disturbance to native plants in an oceanic island community - Xiang-Ping Wang; Xiao Fu; Miao-Miao Shi; Zhong-Tao Zhao; Shi-Jin Li; Tie-Yao Tu (Biological Invasions, 2023)

QbD-Guided Traditional Chinese Medicine Manufacturing Process: Development and Optimization of Fluid-Bed Granulation and Drying Processes for Xiaochaihu Capsules - Kaixuan Teng; Hao Fu; Gelin Wu; Ping Gong; Yongjian Xie; Peng Zhou; Xingchu Gong; Haibin Qu (AAPS PharmSciTech, 2023)

Spatial and molecular variations in forest topsoil dissolved organic matter as revealed by FT-ICR mass spectrometry - Ming Sheng; Shuang Chen; Cong-Qiang Liu; Qinglong Fu; Donghuan Zhang; Wei Hu; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (Science of The Total Environment, 2023)

Cyclic utilization of waste aluminum polishing solution by an efficient co-extraction system: Influence factors and extraction mechanism - Hui Chen; Shixin Li; Yingna Li; Ziqian Du; Liying Bin; Weidong Li; Fenglian Fu; Ping Li; Bing Tang (Process Safety and Environmental Protection, 2023)

Modeling and optimization of Graphene Oxide (GO) membranes for nanofiltration with artificial neural networks - Haodong Yang; Zhe Chen; Yong Li; Lei Yao; Geming Wang; Quanrong Deng; Ping Fu; Shenggao Wang (Journal of Water Process Engineering, 2023)

The conversion of organic sulfur and strontium into inorganic compounds during the molten salt oxidation of mixed resin - Xin Liu; Yong-De Yan; Yang-Hai Zheng; Wen-Da Xu; Yun Xue; Jing-Ping Wang; Qing-Guo Zhang; Yue-Lin Wang; Fu-Qiu Ma (Journal of Environmental Chemical Engineering, 2023)

Mechanisms of the effects of the biochar application rate and time on farmland water, heat and gas environments during soil thawing in seasonally frozen soil areas: A two-year field trial - Ping Xue; Renjie Hou; Qiang Fu; Tianxiao Li; Mo Li; Dong Liu; Qinglin Li (Journal of Environmental Chemical Engineering, 2023)

The overlooked carbonate radical in micropollutant degradation: An insight into hydration interaction - Ruiyang Xiao; Yunxiang Meng; Yifu Fu; Stanisław Wacławek; Zongsu Wei; Richard Spinney; Dionysios D. Dionysiou; Weizhi Zeng; Wei–Ping Hu (Chemical Engineering Journal, 2023)

Characterization of the fragmented mitochondrial genome of domestic pig louse Haematopinus suis (Insecta: Haematopinidae) from China - Rong Li; Yu Nie; Yi-Tian Fu; Yuan-Ping Deng; Wei Wang; Ping-Ping Ma; Guo-Hua Liu (Systematic Parasitology, 2023)

Potentially migrating and residual components of biochar: Effects on phosphorus adsorption performance and storage capacity of black soil - Ping Xue; Renjie Hou; Qiang Fu; Tianxiao Li; Jinwu Wang; Wenqi Zhou; Weizheng Shen; Zhongbin Su; Yijia Wang (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Engineering thermochemistry to cope with challenges in carbon neutrality - Zhennan Han; Xin Jia; Xingfei Song; Ping An; Liangliang Fu; Junrong Yue; Jian Yu; Xuejing Liu; Zhanguo Zhang; Yong Jin; Mingyuan He; Dingrong Bai; et al. (Journal of Cleaner Production, 2023)

Laboratory synthesis, spectroscopic characteristics, and conversion relationships of five calcium sulfate double salts relevant to Mars - Enming Ju; Erbin Shi; Yanqing Xin; Haijun Cao; Changqing Liu; Ping Liu; Jian Chen; Xiaohui Fu; Zongcheng Ling (Icarus, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

Plant facilitation improves carbon production efficiency while reducing nitrogen input in semiarid agroecosystem - Wei Wang; Meng-Ying Li; Shuang-Guo Zhu; Aziz Khan; Xiu-Ping Tao; Guang-Fu Huang; Hai-Ying Liu; Wei Zhang; Hong-Yan Tao; Dong-Shan Gong; Chao Song; You-Cai Xiong (CATENA, 2023)

Inhibitory Mechanism of EGCG on Advanced Glycation End Products Formation During Low-Temperature Vacuum Heating of Russian Sturgeon - Yue-Wen Chen; Min Zhang; Jing-Jing Fu; Jian-Ling Wei; Wen-Qiang Cai; Xiu-Ping Dong (Journal of Aquatic Food Product Technology, 2023)

Organic carbon preservation in wetlands: Iron oxide protection vs. thermodynamic limitation - Fu-Sheng Sun; Chao Ma; Guang-Hui Yu; Yakov Kuzyakov; Yun-Chao Lang; Ping-Qing Fu; Li-Jun Guo; Hui Henry Teng; Cong-Qiang Liu (Water Research, 2023)

Organic matter enrichment in Asia's palaeolake controlled by the early and middle Eocene global warming and astronomically driven precessional climate - Xiaosong Wei; Yong Deng; Detian Yan; Entao Liu; Ping Jiang; Jiaxiong Zhou; He Huang; Bao Zhang; Haijiao Fu; Yin Gong (Marine and Petroleum Geology, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Urinary Amino-PAHs in relation to diesel engine emissions and urinary mutagenicity - Junfeng (Jim) Zhang; Yuxin Zheng; Roel Vermeulen; Xing (Lucy) Liu; Yufei Dai; Wei Hu; Linchen He; Yan Lin; Dianzhi Ren; Huawei Duan; Yong Niu; Jun Xu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Iron isotope fractionation during fluid metasomatism and ore-forming processes in magmatic-hydrothermal systems - Wang Liao; Xin-Fu Zhao; Li-Ping Zeng; Stefan Weyer; Chao Zhang; Ingo Horn; Francois Holtz (Geochimica et Cosmochimica Acta, 2023)

NIR- and pH-responsive injectable nanocomposite alginate-graft-dopamine hydrogel for melanoma suppression and wound repair - Ping Li; Yang Li; Rongzhan Fu; Zhiguang Duan; Chenhui Zhu; Daidi Fan (Carbohydrate Polymers, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Exploring the migration and transformation behaviors of heavy metals and ammonia nitrogen from electrolytic manganese residue to agricultural soils through column leaching test - Xianwei Zhang; Ping Wang; Jiangshan Li; Yonghong Gao; Shiyu Liu; Saiou Fu; Chikezie Chimere Onyekwena; Xuewen Lei (Environmental Science and Pollution Research, 2023)

Long-term hypoxia and reoxygenation induced oxidative stress lead to immunosuppression and apoptosis in golden pompano (Trachinotus blochii) - Yue Gu; Jun Long Sun; Fu Cheng Yao; Tian Jiang; Chun Xiu Jin; Li Ping Shi; Shu Kui Sun; Fei Biao Song; Jian Luo (Frontiers in Marine Science, 2023)
The fluctuations of dissolved oxygen (DO) often lead to hypoxia in aquaculture, which has a huge adverse impact on fish. This study mainly investigated the effects of long-term hypoxia on oxidative stress, immune response, and cell apoptosis in the liver of golden pompano ( Trachinotus blochii ), which is not tolerant to hypoxia. So we conducted a 14 day low oxygen stress experiment on the golden pompano with a DO of 3.0 ± 0.2 mg/L, then restore the DO to normal levels and continue the 14 day reoxygenation experiment. Results showed that hypoxia and reoxygenation led to significant changes in liver structure. During hypoxia and reoxygenation, the expression of oxidative stress related genes ( SOD1 , SOD2 , GSH-Px , and CAT ) and levels of antioxidant enzymes (CAT and MDA) in the liver were increased. Liver lysozyme activity and the relative expression of the pro-inflammatory factors interleukin ( IL)-1β were significantly increased, but the expression of IL-34 was down-regulated during hypoxia. The expression of IL-12β was significantly increased during reoxygenation. The expression of anti-inflammatory factor IL -11 was decreased duringreoxygenation. The expression of toll like receptors ( TLRs ) -7, -8, and -9 increases after hypoxia and decreases after reoxygenation, indicating that both hypoxia and reoxygenation affect the immune response. In addition, during hypoxia and reoxygenation, TUNEL-positive signals increased, the bcl2/bax ratio decreased, the expression levels of caspases-3 and -8 were significantly up-regulated during hypoxia, and expression levels of caspases-9 was up-regulated during reoxygenation. In summary, hypoxia and reoxygenation can cause oxidative stress, induce inflammatory reactions, inhibit immune processes, activate apoptosis, and lead to liver damage of the golden pompano, which may be irreversible.

Response spectra for transient pore-pressure in a sandy seabed under random waves: Frequency-filtering effect - Jia-Hao Yu; Fu-Ping Gao; Chang-Fei Li (Ocean Engineering, 2023)

Identify nitrogen transport paths and sources contribution in karst valley depression area using isotopic approach - Meng Lu; Fu-Jun Yue; Xiao-Dan Wang; Zi-Han Liu; Zhi-Yu Shi; Ping Zhang (Journal of Environmental Management, 2023)

Recent soybean subsidy policy did not revitalize but stabilize the soybean planting areas in Northeast China - Yuanyuan Di; Nanshan You; Jinwei Dong; Xiaoyong Liao; Kaishan Song; Ping Fu (European Journal of Agronomy, 2023)

A new configuration of Geiger-type cable domes with sliding ridge cables: Computational framework and structural feasibility investigation - Yu Xue; Yaozhi Luo; Yafeng Wang; Xian Xu; Hua-Ping Wan; Yanbin Shen; Wenwei Fu (Engineering Structures, 2023)

Converting sludge to slag through a high temperature slagging co-gasification process: An evaluation based on a demonstration trial and life cycle assessment - Xiaoxu Fu; Wei Ping Chan; Vernette Chin; Yinn Zhao Boon; Wenqian Chen; Ya Zhao; Stephan Heberlein; Yan Gu; James Oh; Grzegorz Lisak (Chemical Engineering Journal, 2023)

Fluorescence Properties and Chemical Composition of Fine Particles in the Background Atmosphere of North China - Ping Li; Siyao Yue; Xiaoyang Yang; Di Liu; Qiang Zhang; Wei Hu; Shengjie Hou; Wanyu Zhao; Hong Ren; Gang Li; Yuanguan Gao; Junjun Deng; et al. (Advances in Atmospheric Sciences, 2023)

Bisabolane-type sesquiterpenoids with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Morinda citrifolia - Ying-Ying Zhao; Yu-Jie Li; Xiao-Mei Yu; Qin-Ting Su; Li-Wen Wang; Yu-Shu Zhu; Yan-Hui Fu; Guang-Ying Chen; Yan-Ping Liu (Natural Product Research, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Efficient removal of refractory dyestuffs from textile wastewater by composite hydrated alumina derived from waste aluminum polishing solution - Shixin Li; Hui Chen; Yingna Li; Ziqian Du; Liying Bin; Weidong Li; Fenglian Fu; Ping Li; Bing Tang (Journal of Environmental Chemical Engineering, 2023)

Li and O isotopes of mantle xenoliths from deep fault-related Cenozoic basalts in eastern China: The role of subducted components in the generation of the heterogeneous lithospheric mantle - Qiong Chen; Mei-Fu Zhou; Xiao-Ping Xia; Ping-Ping Liu (Chemical Geology, 2023)

Rapid granulation of aerobic granular sludge in an integrated moving bed biofilm reactor-membrane bioreactor: Effects and mechanism of Streptomyces cellulosus microspheres - Huanlong Zhang; Yue Xu; Liying Bin; Ping Li; Fenglian Fu; Shaosong Huang; Bing Tang (Bioresource Technology Reports, 2023)

Anthraquinones with potential antiproliferative activities from the fruits of Morinda citrifolia - Zhang-Yang Shen; Ying-Ying Zhao; Ze-Hua Qiao; Zhen Xie; Ruo-Qing Guan; Ze-Yu Liu; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu (Natural Product Research, 2023)

Tree mycorrhizal type controls over soil water-extractable organic matter quantity and biodegradation in a subtropical forest of southern China - Hui-Min Chen; Fu-Xi Shi; Jia-Wen Xu; Xing-Ping Liu; Rong Mao (Forest Ecology and Management, 2023)

Molecular imprinted electrochemical sensor for ovalbumin detection based on boronate affinity and signal amplification approach - Hao Fu; Zhenyu Bai; Ping Li; Xiaoyang Feng; Xueping Hu; Xingliang Song; Lingxin Chen (Food Chemistry, 2023)

Metatranscriptomic insights into the microbial electrosynthesis of acetate by Fe2+/Ni2+ addition - Jie Zhang; He Liu; Yan Zhang; Bo Fu; Chao Zhang; Min-Hua Cui; Ping Wu; Zi-Wei Guan (World Journal of Microbiology and Biotechnology, 2023)

Reliable spectroscopic identification of minerals associated with serpentinization: Relevance to Mars exploration - Wen-Ping Liu; Wei Yin; Bin-Long Ye; Tian-Lei Zhao; Qi-Zhi Yao; Yi-Liang Li; Sheng-Quan Fu; Gen-Tao Zhou (Icarus, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Generating waxy rice starch with target type of amylopectin fine structure and gelatinization temperature by waxy gene editing - Yuhao Fu; Yonghuan Hua; Tingting Luo; Chunyan Liu; Baoli Zhang; Xingyu Zhang; Yiping Liu; Zizhong Zhu; Yang Tao; Zhongyan Zhu; Ping Li; Jun Zhu (Carbohydrate Polymers, 2023)

Depth profiling of arsenian pyrite in Carlin-type ores through wet chemistry - Meizhi Yang; Quan Wan; Xin Nie; Suxing Luo; Yuhong Fu; Ping Zeng; Wenqi Luo (Acta Geochimica, 2023)

Two recyclable and complementary adsorbents of coal-based and bio-based humic acids: High efficient adsorption and immobilization remediation for Pb(II) contaminated water and soil - Peng Zhao; An Wang; Ping Wang; Zhen Huang; Zhanyong Fu; Zhanbin Huang (Chemosphere, 2023)

Comparison of the chronic and multigenerational toxicity of racemic glufosinate and -glufosinate to Caenorhabditis elegans at environmental concentrations - Xu Zhao; Kan Fu; Kai-ping Xiang; Lan-ying Wang; Yun-fei Zhang; Yan-ping Luo (Chemosphere, 2023)

Assessing accuracy of genomic breeding values of selection candidates under biosecurity restrictions by progeny testing in Chinese shrimp Fenneropenaeus chinensis - Mianyu Liu; Ping Dai; Jie Kong; Xianhong Meng; Juan Sui; Kun Luo; Baolong Chen; Qiang Fu; Baoxiang Cao; Jiawang Cao; Sheng Luan (Aquaculture, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Deciphering the role and mechanism of nano zero-valent iron on medium chain fatty acids production from CO2 via chain elongation in microbial electrosynthesis - Ping Wu; Jie Zhang; Jing Li; Yan Zhang; Bo Fu; Ming-Yi Xu; Yi-Feng Zhang; He Liu (Science of The Total Environment, 2023)

Petrogenesis of the Chakabeishan pegmatites, North Qaidam Terrane: Implications for Indosinian lithium mineralization in the northern Tibetan Plateau - Jin-Heng Liu; Qiang Wang; Bing-Zhang Wang; Wu-Fu Li; Chuan-Bing Xu; Shan-Ping Li; Zi-Long Wang; Lu-Lu Hao; Tai-Zhong Song; Chun-Tao Wang; Ying Zheng; Jin-Shou Wang (Lithos, 2023)

Reducing the water residence time is inadequate to limit the algal proliferation in eutrophic lakes - Yingying Huang; Min Fu; Guiqin Chen; Jieyun Zhang; Ping Xu; Liping Pan; Xiaohan Zhang; Xuechu Chen (Journal of Environmental Management, 2023)

Molecular encapsulation of cinnamaldehyde in V-type starch: The role of solvent and temperature - Qing Gao; Yanan Sun; Ruolan He; Jiabao Zheng; Bin Zhang; Chin Ping Tan; Xiong Fu; Qiang Huang (Food Hydrocolloids, 2023)

Accelerated sulfate radical generation from peroxymonosulfate by ZIF-67-derived Co3O4 encapsulated in g-C3N4: A gift from in situ growth - Jinping Liang; Ling Fu; Kai Gao; Ping Zhang; Xiaoguang Duan; Xiaobo Gong; Li Cai (Chemical Engineering Journal, 2023)

24-Epibrassinolide Enhances Resistance Against Colletotrichum fructicola by Promoting Lignin Biosynthesis in Camellia sinensis L. - Lan Zhang; Zheng Zhang; Golam Jalal Ahammed; Xiaorong Wang; Huihan Fang; Peng Yan; Li-Ping Zhang; Shibei Ge; Jianyu Fu; Wen-Yan Han; Xin Li (Journal of Plant Growth Regulation, 2023)

Nightside 135.6 nm emission enhancements of mid/low latitudes during geomagnetic storms as observed by the ionosphere PhotoMeter (IPM) on the Chinese meteorological satellite FY-3D - Fang Jiang; Tian Mao; XiaoXin Zhang; Li-Ping Fu (Advances in Space Research, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Strouhal number for boundary shear flow past a circular cylinder in the subcritical flow regime - Yan Liu; Jun Liu; Fu-Ping Gao (Ocean Engineering, 2023)

Spectral change of dissolved organic matter after extracted by solid-phase extraction and its feasibility in predicting the acute toxicity of polar organic pollutants in textile wastewater - Lingfang Fu; Liying Bin; Zhaobo Luo; Zehong Huang; Ping Li; Shaosong Huang; Dieudonne Nyobe; Fenglian Fu; Bing Tang (Journal of Hazardous Materials, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

Remediation of lindane contaminated soil by fluidization-like dielectric barrier discharge - Shuo Zhang; Zhen Liu; Shuran Li; Shihao Zhang; Hui Fu; Xuan Tu; Wenyi Xu; Xing Shen; Keping Yan; Ping Gan; Xiujuan Feng (Journal of Hazardous Materials, 2023)

Effect of etching and reduction time on the structure, performance, and stability of GO-based membrane for water purification - Fan-xin Kong; Lian You; Jia-mei Cao; Qian Liu; Ping Xia; Jin-fu Chen (Journal of Environmental Chemical Engineering, 2023)

Phospholipase A2 induces acute kidney injury by complement mediated mitochondrial apoptosis via TNF-α/NF-κB signaling pathway - Xin Tang; Tiantian Wei; Mingjing Guan; Peiyun Li; Yajun Pu; Lixin Cheng; Zhifeng Zhou; Ping Fu; Ling Zhang (Food and Chemical Toxicology, 2023)

Cobalt single atom anchored on N-doped carbon nanoboxes as typical single-atom catalysts (SACs) for boosting the overall water splitting - Tong Li; Siyuan Ren; Cheng Zhang; Lingxia Qiao; Jiang Wu; Ping He; Jia Lin; Yongsheng Liu; Zaiguo Fu; Qunzhi Zhu; Weiguo Pan; Baofeng Wang; et al. (Chemical Engineering Journal, 2023)

Molecular characteristics and compositions affecting light absorption features of cloud water revealed by Fourier transform ion cyclotron resonance mass spectrometry - Ziyong Guo; Wei Sun; Xiaodong Hu; Juying Lin; Yuzhen Fu; Xiaocong Peng; Bin Jiang; Yuhong Liao; Guohua Zhang; Xinming Wang; Ping'an Peng; Xinhui Bi (Atmospheric Environment, 2023)

Effects of temperature on the pharmacokinetics, optimal dosage, tissue residue, and withdrawal time of florfenicol in asian seabass ( lates calcarifer ) - Tirawat Rairat; Ming-Kun Hsieh; Wan-Cih Ho; Yi-Ping Lu; Zhu-Ying Fu; Niti Chuchird; Chi-Chung Chou (Food Additives & Contaminants: Part A, 2023)

Biofertilizer made from a mixed microbial community can enhance the suppression of fusarium wilt of banana when combined with acid soil ameliorant - Jianfeng Huang; Yuwan Pang; Gen Cheng; Tengfei Wu; Qiaoyi Huang; Xu Huang; Qiong Yi; Mu Zhang; Shuanhu Tang; Hongting Fu; Ping Li (European Journal of Plant Pathology, 2023)

Cognitive changes are associated with increased blood-brain barrier leakage in non-brain metastases lung cancer patients - Da-Fu Zhang; Zhen-Hui Li; Zhi-Ping Zhang; Yin-Fu He; Bin-Li Shang; Xiu-Feng Xu; Ying-Ying Ding; Yu-Qi Cheng (Brain Imaging and Behavior, 2023)
To explore the relationship between cognitive function and blood–brain barrier leakage in non-brain metastasis lung cancer and healthy controls. 75 lung cancers without brain metastasis and 29 healthy controls matched with age, sex, and education were evaluated by cognitive assessment, and the Patlak pharmacokinetic model was used to calculate the average leakage in each brain region according to the automated anatomical labeling atlas. After that, the relationships between cognitive and blood–brain barrier leakage were evaluated. Compared with healthy controls, the leakage of bilateral temporal gyrus and whole brain gyrus were higher in patients with lung cancers ( P < 0.05), mainly in patients with advanced lung cancer ( P < 0.05), but not in patients with early lung cancer ( P > 0.05). The cognitive impairment of advanced lung cancers was mainly reflected in the damage of visuospatial/executive, and delayed recall. The left temporal gyrus with increased blood–brain barrier leakage showed negative correlations with delayed recall (r = -0.201, P = 0.042). An increase in blood–brain barrier leakage was found in non-brain metastases advanced lung cancers that corresponded to decreased delayed recall. With progression in lung cancer staging, blood–brain barrier shows higher leakage and may lead to brain metastases and lower cognitive development.

An Evaluation of the Coupling Coordination of Technological Innovation System in China’s Marine Biopharmaceutical Industry - Xiumei Fu; Yangming Zheng; Chunyu Lin; Ping Wang; Changyun Wang (Journal of Ocean University of China, 2023)

Effects of micro‐nano bubble aerated irrigation and levels of nitrogen fertilizer on nitrogen accumulation and metabolism in super rice - Wei‐hua Xiao; Qiong Liao; Jian‐jun Fu; Yan‐ni Liu; Cui‐ping Zhang; Wen‐ping Zhang (Irrigation and Drainage, 2023)
Micro‐nano bubble aerated irrigation (MNBI) is an innovative technology that generates nano‐diameter bubbles in irrigation water via a micro‐nano bubble device. In this study, pot experiments with three different nitrogen level treatments under conventional irrigation and MNBI were conducted to investigate the effects of MNBI and nitrogen application levels on rice yield, nitrogen accumulation and utilization. The results showed that MNBI promoted rice yields by increasing the seed setting rate compared to conventional irrigation, and nitrogen accumulation was positively correlated with nitrogen application but significantly increased by MNBI due to the increased root growth and activity. Furthermore, the activity of key enzymes involved in nitrogen metabolism, nitrate reductase and glutamine synthetase, significantly increased under MNBI at a nitrogen level of 225 kg ha −1 . In conclusion, with the elevation of nitrogen application, MNBI improved rice yields and nitrogen accumulation and utilization, indicating that nitrogen and MNBI synergistically enhanced rice yields. Thus, the results provide the basis for efficient and high‐yielding super rice cultivation.

Assessment of contaminants associated with gold-standard ancient DNA protocols - Bo Miao; Yalin Liu; Ruowei Yang; Xiaotian Feng; Feng Liu; Peng Cao; Qingyan Dai; Wanjing Ping; Yichen Liu; Qiaomei Fu (Science Bulletin, 2023)

Stochastic analysis on the lateral buckling of a HPHT pipeline considering the spatial variability of seabed - Yu-Min Shi; Ning Wang; Fu-Ping Gao (Ocean Engineering, 2023)

Petrogenesis of Early Mesozoic volcanic rocks in southeastern NE China: Geochemical and Sr–Nd–Pb–O isotopic evidences - Jing-Yang Wei; Fu-Ping Pei; Wen-Liang Xu; Jing-Gui Sun; Hao Zhou; Tian-Jiao Sang (Lithos, 2023)

Impacts of climate change on future hurricane induced rainfall and flooding in a coastal watershed: A case study on Hurricane Harvey - Xudong Li; Dan Fu; John Nielsen-Gammon; Sudershan Gangrade; Shih-Chieh Kao; Ping Chang; Mario Morales Hernández; Nathalie Voisin; Zhe Zhang; Huilin Gao (Journal of Hydrology, 2023)

Influence and economic analysis of heat storage in the non-heating season on the heat extraction capacity of mid-deep borehole heat exchangers - Haiyu Fu; Liang Fang; Mingzhi Yu; Ping Cui; Wenke Zhang; Yudong Mao; Zhaoyi Zhuang; Zhaohong Fang (Energy and Buildings, 2023)

Combined nonlinear wave and current induced instantaneously-liquefied soil depth in a non-cohesive seabed - Li-Jing Yang; Fu-Ping Gao; Chang-fei Li (Coastal Engineering, 2023)

The involvement of AtMKK1 and AtMKK3 in plant-deleterious microbial volatile compounds-induced defense responses - Ching-Han Chang; Wu-Guei Wang; Pei-Yu Su; Yu-Shuo Chen; Tri-Phuong Nguyen; Jian Xu; Masaru Ohme-Takagi; Tetsuro Mimura; Ping-Fu Hou; Hao-Jen Huang (Plant Molecular Biology, 2023)

Gut microbiota involved in spermatogenic function of Sancai Lianmei granules in obese mice - Yuguo Xia; Ying Tian; Dongqi Zhou; Lei Zhang; Yichen Cai; Shunlian Fu; Xiaoran Zhang; Yang Gao; Qiu Chen; Ping Gao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

The self-powered electrochemical biosensing platform with multi-amplification strategy for ultrasensitive detection of microRNA-155 - Yong-ping Gao; Ke-jing Huang; Fu-ting Wang; Yang-yang Hou; Lu-di Zhao; Bo-ya Wang; Jing Xu; Honglei Shuai; Guoqiang Li (Analytica Chimica Acta, 2023)

Quantitative lateral flow immunoassay for rapid detection of procollagen type I N-terminal propeptide in the monitoring of osteoporosis treatment - Chung-An Chen; Ping-Yeh Chiu; Tse-Hao Huang; Natalie Yi-Ju Ho; Fu-Cheng Kao; Tsung-Ting Tsai (Analytica Chimica Acta, 2023)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Inhibition of Microglial NLRP3 with MCC950 Attenuates Microglial Morphology and NLRP3/Caspase-1/IL-1β Signaling In Stress-induced Mice - Qing Liu; Man-Man Zhang; Min-Xia Guo; Qiu-Ping Zhang; Na-Zhi Li; Jie Cheng; Shi-Le Wang; Guang-Hui Xu; Cheng-Fu Li; Ji-Xiao Zhu; Li-Tao Yi (Journal of Neuroimmune Pharmacology, 2022)

Ecosystem Mercury Recovery and Health Benefit Under the Minamata Convention in a Changing Climate - Qingru Wu; Yanxu Zhang; Ping Li; Xuewu Fu; Qianggong Zhang; Xun Wang; Long Chen; Shuxiao Wang; Feiyue Wang; Xinbin Feng (Reviews of Environmental Contamination and Toxicology, 2022)

Derivation of new resistance principle on flow-induced morphological response of flexible vegetation - Feng-Cong Jia; Wei-Jie Wang; Ling-Hua Liu; Jin-Jin Li; Ai-Ping Huang; Jing Zhang; Yi-Cheng Fu; Yang Yu (Environmental Science and Pollution Research, 2022)

The effect of reservoir expansion from underground karst cave to surface reservoir on water quality in southwestern China - Meng Lu; Xiao-Dan Wang; Fu-Jun Yue; Zi-Han Liu; Zhi-Yu Shi; Ping Zhang (Environmental Science and Pollution Research, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

Increased expression of Myosin X contributes to the metastasis in patients with laryngeal squamous cell carcinoma - Gang Deng; Tie-Jun Fu; Cui-Ping Liu (Molecular Genetics and Genomics, 2022)
Laryngeal Squamous Cell Carcinoma (LSCC) is one of the most common malignancy in Head and neck cancer for which the mechanism underlying its metastasis is poorly understood. Myosin X, a molecular motor in cells has been demonstrated to play an important role in cell migration. However, whether Myosin X is involved in the metastasis of LSCC remains unclear. To investigate the expression of Myosin X and its implication in the metastasis of LSCC, we recruited 30 patients with LSCC and 6 patients with vocal cord polyp range from October 2016 to October 2018. Tissue samples were obtained during surgery and the expression of Myosin X, Cortactin, MMP2, MMP9, E-cadherin, and β-catenin in tissue samples were evaluated by RT-PCR, Western blot, immunohistochemistry or ELISA. Patients with LSCC were further followed-up 2 year after surgery for metastasis analysis. We found that the level of Myosin X, Cortactin, MMP2, and MMP9 was much higher in poorly differentiated LSCC compared to that in moderately and highly LSCC, as well as the control tissues. In contrast, the expression of epithelial-mesenchymal transition related marker, E-cadherin, and β-catenin, were much lower in poorly differentiated LSCC tissues compared to that in moderately and highly differentiated LSCC tissues, as well as the control tissues. Moreover, the expression of Myosin X was positively correlated with Cortactin, MMP2, and MMP9 levels. Increased expression of Myosin X in LSCC tissues was related to higher risk of metastasis. In conclusion, our findings showed that. Myosin X augments the expression of Cortactin, MMP2 and MMP9, which could upregulate the cell migration and the matrix degradation, and consequently reduce the expression of E-cadherin and β-catenin, thereby activating epithelial-mesenchymal transformation and promoting the metastasis of LSCC. Targeting Myosin X may have potential therapeutic effect in the metastasis of LSCC.

Application of regional citrate anticoagulation in patients at high risk of bleeding during intermittent hemodialysis: a prospective multicenter randomized controlled trial - Xiaoyan Tang; Dezheng Chen; Ling Zhang; Ping Fu; Yanxia Chen; Zhou Xiao; Xiangcheng Xiao; Weisheng Peng; Li Cheng; Yanmin Zhang; Hongbo Li; Kehui Li; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Caffeine alleviates acute liver injury by inducing the expression of NEDD4L and deceasing GRP78 level via ubiquitination - Xing-Wang Hu; Xiang-Min Li; Ai-Min Wang; Yong-Ming Fu; Fang-Jie Zhang; Feng Zeng; Li-Ping Cao; Hui Long; Ying-Hui Xiong; Ji Xu; Jia Li (Inflammation Research, 2022)

Distribution of ultrafine aerosols and volatile organic compounds from surgical smoke during electrocauterization - Chi-Tsung Chen; Shiang-Fu Huang; Cheng-Jung Li; Jou-Mien Huang; Kai-Ping Chang; Gwo-Hwa Wan (Air Quality, Atmosphere & Health, 2022)

Dissolved oxygen gradient on three dimensionally printed microfluidic platform for studying its effect on fish at three levels: cell, embryo, and larva - Ping Liu; Longwen Fu; Bowei Li; Mingsan Man; Yunxia Ji; Qi Kang; Xiyan Sun; Dazhong Shen; Lingxin Chen (Environmental Science and Pollution Research, 2022)

Monoterpenoid indole alkaloids with potential neuroprotective activities from the stems and leaves of Melodinus cochinchinensis - Yu-Jie Li; Juan Li; Lan Xie; Jun-Yu Zhou; Qiu-Xuan Li; Rui-Yuan Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2022)

Study on the Effectiveness and Mechanism of Mercapto-Modified Attapulgite for Remediation of Cadmium-Contaminated Paddy Soil - Guangxi He; Xiaping Zhu; Yan An; Yuying Chen; Cheng Fu; Ningfei Lei; Ying Zeng; Junya Li; Zepeng Wang; Ping Zhao (Water, Air, & Soil Pollution, 2022)

Improving pre-harvest sprouting resistance in rice by editing OsABA8ox using CRISPR/Cas9 - Kai Fu; Weihan Song; Cheng Chen; Changling Mou; Yunshuai Huang; Fulin Zhang; Qixian Hao; Ping Wang; Tengfei Ma; Yaping Chen; Ziyan Zhu; Min Zhang; et al. (Plant Cell Reports, 2022)

iTRAQ-based proteomics analysis of diethylstilbestrol induced dysfunction of testicular gubernaculum development in mouse - Hongyan Ping; Degang Wang; Maxian Fu; Kaihong Chen; Jiuhong Zhang; Ke Li; Xuewu Jiang; Shouxing Duan; Xuan Zhang (Molecular & Cellular Toxicology, 2022)

Responses of tidal duration asymmetry to morphological changes in Lingding Bay of the Pearl River Estuary - Qingshu Yang; Shuai Hu; Linxi Fu; Ping Zhang; Nanyang Chu; Feng Liu; Huayang Cai (Frontiers in Marine Science, 2022)
Tidal asymmetry is one of the main factors for generating net transport for waterborne materials in tidal estuaries, and thus, this phenomenon has significant influences on controlling morphological development and the ecological environment. Tidal propagation is sensitive to changes in the coastline and geometry of estuarine regions. Moreover, tidal waveforms vary with various factors, such as coastline changes and bathymetry evolution due to local anthropogenic activities. The topography of Lingding Bay (LDB) of the Pearl River Estuary (PRE) has greatly changed since the 1960s because of human interventions, but the response of tidal duration asymmetry (TDA) to morphological changes is still poorly understood. Utilizing the two-dimensional Delft-3D flexible mesh numerical model, the spatial pattern of TDA and its primary contributors in LDB of the PRE were reproduced for 1964, 1989, and 2016, accounting for the changes in both shoreline and bathymetry owing to human interventions. The results reveal that as the tidal wave propagates upstream, the tidal skewness increases from negative values to positive values longitudinally, indicating the transition from a shorter ebb-duration state to a shorter flood-duration state. Additionally, a prominent shift in TDA and its primary contributors takes place approximately in the period of 1989. In 1964-1989, the tidal skewness increased by at least 0.1 throughout the LDB, indicating that the flood duration of the entire bay was shortened significantly. However, in 1989-2016, the tidal skewness decreased by at most 0.15 throughout the LDB, representing a longer flood duration in the entire LDB. The scenario simulations reveal that reclamation-induced shoreline changes control the increase in TDA and its primary contributors by enhancing width convergence of estuary in the period of 1964-1989. Conversely, the increase in water depth plays a vital role in the decrease of TDA in the period of 1989-2016. The results obtained from this study are particularly useful for understanding the controlled factors contributing to net sediment transport and the associated long-term morphological evolution in estuaries heavily impacted by human interventions.

Novel circularRNA circ-0047078 promotes pancreatic ductal adenocarcinoma progression through mircoRNA miR-11181— Chemokine (C-X-C motif) Ligand 12/Melanoma Cell Adhesion Molecule/Regulator of G-protein signaling 16 pathway - Yuzhou Wang; Hangwei Fu; Yan Jiang; Bo Zhou; Ping Chen (Molecular Biology Reports, 2022)

Impacts of Mercury Exposure Levels and Sources on the Demethylation of Methylmercury Through Human Gut Microbiota - Xian-Feng Yang; Shao-Chen Yang; Fu-Li Wen; Lin Feng; Bo Meng; Hai-Yan Hu; Bao-Lin Wang; Jun Li; Alexandre J. Poulain; Ping Li (Bulletin of Environmental Contamination and Toxicology, 2022)

Microfluidic preparation of a novel phoxim nanoemulsion pesticide against Spodoptera litura - Zong-Nan Li; Yu-Xuan Zhang; Zhi-Ang Zhang; Lian-Han Pan; Ping Li; Yan Xu; Sheng Sheng; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Instability and Failure of Subsea Structures - Fu-Ping Gao; Zhen-Yu Yin (Journal of Marine Science and Engineering, 2022)
Subsea engineering structures are an evolutive system with high diversity, e [...]

Cadinane-type sesquiterpenes with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Mappianthus iodoides - Yan-Ping Liu; Xiao-Mei Yu; Ze-Hua Qiao; Bo Jiang; Lan Xie; Hao-Xuan Tang; Xiao Liang; Yan-Hui Fu (Natural Product Research, 2022)

Improved and Flexible HDR Editing by Targeting Introns in iPSCs - Juan Fu; Ya-Wen Fu; Juan-Juan Zhao; Zhi-Xue Yang; Si-Ang Li; Guo-Hua Li; Zi-Jun Quan; Feng Zhang; Jian-Ping Zhang; Xiao-Bing Zhang; Chang-Kai Sun (Stem Cell Reviews and Reports, 2022)
Highly efficient gene knockout (KO) editing of CRISPR–Cas9 has been achieved in iPSCs, whereas homology-directed repair (HDR)-mediated precise gene knock-in (KI) and high-level expression are still bottlenecks for the clinical applications of iPSCs. Here, we developed a novel editing strategy that targets introns. By targeting the intron before the stop codon, this approach tolerates reading frameshift mutations caused by nonhomologous end-joining (NHEJ)-mediated indels, thereby maintaining gene integrity without damaging the non-HDR-edited allele. Furthermore, to increase the flexibility and screen for the best intron-targeting sgRNA, we designed an HDR donor with an artificial intron in place of the endogenous intron. The presence of artificial introns, particularly an intron that carries an enhancer element, significantly increased the reporter expression levels in iPSCs compared to the intron-deleted control. In addition, a combination of the small molecules M3814 and trichostatin A (TSA) significantly improves HDR efficiency by inhibiting NHEJ. These results should find applications in gene therapy and basic research, such as creating reporter cell lines.

Rapid triage for ischemic stroke: a machine learning-driven approach in the context of predictive, preventive and personalised medicine - Yulu Zheng; Zheng Guo; Yanbo Zhang; Jianjing Shang; Leilei Yu; Ping Fu; Yizhi Liu; Xingang Li; Hao Wang; Ling Ren; Wei Zhang; Haifeng Hou; et al. (EPMA Journal, 2022)
Background Recognising the early signs of ischemic stroke (IS) in emergency settings has been challenging. Machine learning (ML), a robust tool for predictive, preventive and personalised medicine (PPPM/3PM), presents a possible solution for this issue and produces accurate predictions for real-time data processing. Methods This investigation evaluated 4999 IS patients among a total of 10,476 adults included in the initial dataset, and 1076 IS subjects among 3935 participants in the external validation dataset. Six ML-based models for the prediction of IS were trained on the initial dataset of 10,476 participants (split participants into a training set [80%] and an internal validation set [20%]). Selected clinical laboratory features routinely assessed at admission were used to inform the models. Model performance was mainly evaluated by the area under the receiver operating characteristic (AUC) curve. Additional techniques—permutation feature importance (PFI), local interpretable model-agnostic explanations (LIME), and SHapley Additive exPlanations (SHAP)—were applied for explaining the black-box ML models. Results Fifteen routine haematological and biochemical features were selected to establish ML-based models for the prediction of IS. The XGBoost-based model achieved the highest predictive performance, reaching AUCs of 0.91 (0.90–0.92) and 0.92 (0.91–0.93) in the internal and external datasets respectively. PFI globally revealed that demographic feature age, routine haematological parameters, haemoglobin and neutrophil count, and biochemical analytes total protein and high-density lipoprotein cholesterol were more influential on the model’s prediction. LIME and SHAP showed similar local feature attribution explanations. Conclusion In the context of PPPM/3PM, we used the selected predictors obtained from the results of common blood tests to develop and validate ML-based models for the diagnosis of IS. The XGBoost-based model offers the most accurate prediction. By incorporating the individualised patient profile, this prediction tool is simple and quick to administer. This is promising to support subjective decision making in resource-limited settings or primary care, thereby shortening the time window for the treatment, and improving outcomes after IS.

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Diel variation in anti-predation behavior of a ground squirrel and relationships between vigilance and escape - Ling-Ying Shuai; Mei-Ting Liu; A.-Ping Zhu; Yuan-Yuan Cao; Fu-Shun Zhang (Behavioral Ecology and Sociobiology, 2022)

Involvement of Opioid Peptides in the Analgesic Effect of Spinal Cord Stimulation in a Rat Model of Neuropathic Pain - Fu-Jun Zhai; Song-Ping Han; Tian-Jia Song; Ran Huo; Xing-Yu Lan; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2022)

Reduction research on performance index system of satellite navigation system spoofing - Yue Wang; Fu-Ping Sun; Jin-Ming Hao; Lun-Dong Zhang; Xian Wang (GPS Solutions, 2022)

Antifungal sesquiterpenes with post-harvest anthracnose control effect on bananas from the fungus Fusarium lateritium - Junjie Zhu; Ping Xiong; Ziyang Li; Jiazhong Li; Longsheng Lin; Xing Fu; Yuxuan Huang; Yahong Xiong; Chunyuan Li (Natural Product Research, 2022)

The association between environmental exposure to perchlorate, nitrate, and thiocyanate and all-cause and cause-specific mortality - Long Wang; Zhi Fu; Beibei Gao; Xuming Mo; Ping Liang; Jinyu Huang (Environmental Science and Pollution Research, 2022)

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

Endosomal sorting complexes required for transport‐0 ( ESCRT ‐0) are essential for fungal development, pathogenicity, autophagy and ER ‐phagy in Magnaporthe oryzae - Li‐Xiao Sun; Hui Qian; Meng‐Yu Liu; Ming‐Hua Wu; Yun‐Yun Wei; Xue‐Ming Zhu; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2022)
Summary Magnaporthe oryzae is an important plant pathogen that causes rice blast. Hse1 and Vps27 are components of ESCRT‐0 involved in the multivesicular body (MVB) sorting pathway and biogenesis. To date, the biological functions of ESCRT‐0 in M. oryzae have not been determined. In this study, we identified and characterized Hse1 and Vps27 in M. oryzae . Disruption of MoHse1 and MoVps27 caused pleiotropic defects in growth, conidiation, sexual development and pathogenicity, thereby resulting in loss of virulence in rice and barley leaves. Disruption of MoHse1 and MoVps27 triggered increased lipidation of MoAtg8 and degradation of GFP‐MoAtg8, indicating that ESCRT‐0 is involved in the regulation of autophagy. ESCRT‐0 was determined to interact with coat protein complex II (COPII), a regulator functioning in homeostasis of the endoplasmic reticulum (ER homeostasis), and disruption of MoHse1 and MoVps27 also blocked activation of the unfolded protein response (UPR) and autophagy of the endoplasmic reticulum (ER‐phagy). Overall, our results indicate that ESCRT‐0 plays critical roles in regulating fungal development, virulence, autophagy and ER‐phagy in M. oryzae .

Enhancing the production of physiologically active vitamin D3 by engineering the hydroxylase CYP105A1 and the electron transport chain - Bing Fu; Qian Ren; Jian Ma; Qingwei Chen; Qili Zhang; Ping Yu (World Journal of Microbiology and Biotechnology, 2022)

A community effort to assess and improve computerized interpretation of 12-lead resting electrocardiogram - Zijian Ding; Guijin Wang; Huazhong Yang; Ping Zhang; Dapeng Fu; Zhen Yang; Xinkang Wang; Xia Wang; Zhourui Xia; Chiming Zhang; Wenjie Cai; Binhang Yuan; et al. (Medical & Biological Engineering & Computing, 2022)
Computerized interpretation of electrocardiogram plays an important role in daily cardiovascular healthcare. However, inaccurate interpretations lead to misdiagnoses and delay proper treatments. In this work, we built a high-quality Chinese 12-lead resting electrocardiogram dataset with 15,357 records, and called for a community effort to improve the performances of CIE through the China ECG AI Contest 2019. This dataset covers most types of ECG interpretations, including the normal type, 8 common abnormal types, and the other type which includes both uncommon abnormal and noise signals. Based on the Contest, we systematically assessed and analyzed a set of top-performing methods, most of which are deep neural networks, with both their commonalities and characteristics. This study establishes the benchmarks for computerized interpretation of 12-lead resting electrocardiogram and provides insights for the development of new methods.

Association between serum folate levels and blood concentrations of cadmium and lead in US adults - Zuxiang Wu; Huan Hu; Chenxi Wang; Ji Wu; Yurong Xiong; Yang Fu; Xiaoshu Cheng; Hai Su; Ping Li (Environmental Science and Pollution Research, 2022)

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

Discriminative optimization algorithm with global–local feature for LIDAR point cloud registration - Jia Wang; Ping Wang; Biao Li; Ruigang Fu; Siyi Zhao; Hong Zhang (International Journal of Remote Sensing, 2021)

Recent advances in tissue stem cells - Xin Fu; Qiang He; Yu Tao; Mengdi Wang; Wei Wang; Yalong Wang; Qing Cissy Yu; Fang Zhang; Xiaoyu Zhang; Ye-Guang Chen; Dong Gao; Ping Hu; et al. (Science China Life Sciences, 2021)

FKgrain: A topography-based software tool for grain segmentation and sizing using factorial kriging - Fu-Chun Wu; Chi-Kuei Wang; Hong Ping Lo (Earth Science Informatics, 2021)

Transcriptome analysis reveals differing response and tolerance mechanism of EPSPS and GAT genes among transgenic soybeans - Bing-Fu Guo; Hui-Long Hong; Li-Ping Sun; Yong Guo; Li-Juan Qiu (Molecular Biology Reports, 2021)

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

Hydrological characteristics and changes in the Nu-Salween River basin revealed with model-based reconstructed data - Fan Yang; Hui Lu; Kun Yang; Guang-wei Huang; Yi-shan Li; Wei Wang; Ping Lu; Fu-qiang Tian; Yu-gang Huang (Journal of Mountain Science, 2021)

Responses of leaf litter decomposability to nitrogen and phosphorus additions are associated with cell wall carbohydrate composition in a subtropical plantation - Xiang-Min Fang; Xiu-Lan Zhang; Ying-Ying Zong; Wen-Qing Li; Jian-Jun Li; Li-Ping Guo; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2021)

HDAC inhibitors improve CRISPR-mediated HDR editing efficiency in iPSCs - Jian-Ping Zhang; Zhi-Xue Yang; Feng Zhang; Ya-Wen Fu; Xin-Yue Dai; Wei Wen; Beldon Zhang; Hannah Choi; Wanqiu Chen; Meredith Brown; David Baylink; Lei Zhang; et al. (Science China Life Sciences, 2021)

Passivation and remediation of Pb and Cr in contaminated soil by sewage sludge biochar tubule - Lin Chen; Qi Ni; Yan Wu; Chuan Fu; Wei Ping; Hongyu Bai; Mengnan Li; Hongcheng Huang; Hanshuang Liu (Environmental Science and Pollution Research, 2021)

Impacts of Canopy and Understory Nitrogen Additions on Stomatal Conductance and Carbon Assimilation of Dominant Tree Species in a Temperate Broadleaved Deciduous Forest - Yanting Hu; Karina V. R. Schäfer; Liwei Zhu; Ping Zhao; Xiuhua Zhao; Guangyan Ni; Yaxing Zhang; Huiying Ye; Wanli Zhao; Weijun Shen; Shenglei Fu (Ecosystems, 2021)

Seasonal variation of flavonoid metabolites in leaves of Liquidambar formosana ‘Nanlinhong’ trees revealed by UPLC-ESI–MS/MS - Jiu-Xin Lai; Fu-Rong Lin; Ping Huang; Wen-Ying Guo; Lie-Bao Han; Yong-Qi Zheng (Brazilian Journal of Botany, 2021)

Protective effect of Bombyx mori gloverin on intestinal epithelial cells exposure to enterotoxigenic E. coli - Qian Lin; Qingqing Fu; Guoqi Su; Daiwen Chen; Bing Yu; Yuheng Luo; Ping Zheng; Xiangbing Mao; Zhiqing Huang; Jie Yu; Junqiu Luo; Hui Yan; et al. (Brazilian Journal of Microbiology, 2021)

Biomechanical Evaluation of a Fin-type Implant Compared to Traditional Buttress Plate for the Stabilization of the Posteromedial Fragment in Tibial Plateau Split Fractures - Jian-Chih Chen; Kang-Ping Lin; Tien-Ching Lee; Yin-Chih Fu; Kun-Jhih Lin (Journal of Medical and Biological Engineering, 2021)

Triterpene saponins from tea seed pomace ( Camellia oleifera Abel) and their cytotoxic activity on MCF-7 cells in vitro - Xin-Fu Zhang; Ying-Ying Han; Tai-Mei Di; Li-Ping Gao; Tao Xia (Natural Product Research, 2021)

A new p -terphenyl derivative from the fruiting bodies of Sarcodon imbricatus (L.) P. Karst - Feng-Ming Zhang; Yue-Hu Wang; Ping Zhao; Fu-Qiang Yu (Natural Product Research, 2021)

The Integration of Carbon Price Between European and Chinese Markets: What are the Implications? - Yunpeng Wang; Qiang Fu; Chun-Ping Chang (International Journal of Environmental Research, 2021)

Microbial characteristics response to the soil quality of newly created farmland on the Loess Plateau - Chen Xu; Yi-ping Chen; Cui-cui Su; Ji-fu Ma; Jun-hua Wu; Kai-bo Wang; Yi Wang; Yao Jiang (Environmental Science and Pollution Research, 2021)

Ecological carrying capacity of alpine grassland in the Qinghai–Tibet Plateau based on the structural dynamics method - Yi-ping Fang; Fu-biao Zhu; Shu-hua Yi; Xiao-ping Qiu; Yong-jiang Ding (Environment, Development and Sustainability, 2021)

The rescue and selection of thermally stable type O vaccine candidate strains of foot-and-mouth disease virus - Ya Gao; Pinghua Li; Xueqing Ma; Xingwen Bai; Pu Sun; Ping Du; Hong Yuan; Yimei Cao; Kun Li; Yuanfang Fu; Jing Zhang; Huifang Bao; et al. (Archives of Virology, 2021)

Metabolic cold adaptation in the Asiatic toad: intraspecific comparison along an altitudinal gradient - Song Tan; Ping Li; Zhongyi Yao; Gaohui Liu; Bisong Yue; Jinzhong Fu; Jingfeng Chen (Journal of Comparative Physiology B, 2021)

Cysteiniphilum marinum sp. nov., isolated from coastal seawater - Hai-Min Luo; Jun-Hui Feng; Liang-Hui Li; Meng-Meng Li; Ru-Qin Liu; Fu Chen; Ying Lin; Wen-Jun Li; Ping-Hua Qu; Min Xiao (Antonie van Leeuwenhoek, 2021)

Neuroprotective carbazole alkaloids from the stems and leaves of Clausena lenis - Gui Yan; Yu-Jie Li; Ying-Ying Zhao; Jia-Ming Guo; Wen-Hao Zhang; Ming-Ming Zhang; Yan-Hui Fu; Yan-Ping Liu (Natural Product Research, 2021)

Emergent chikungunya fever and vertical transmission in Yunnan Province, China, 2019 - XiaoXiong Yin; Ting-Song Hu; HaiLin Zhang; YongHua Liu; ZhiJian Zhou; LeBin Liu; Ping Li; YiYin Wang; ZhaoLan Yang; Jing Yu; SiYu Chen; Fu-Qiang Zhang (Archives of Virology, 2021)

Effects of Spray Parameters on the Effective Spray Width of Single-Rotor Drone in Sugarcane Plant Protection - Ping Zhang; Wei Zhang; Hai-Tian Sun; Feng-Guang He; Hai-Ba Fu; Li-Qiang Qi; Li-Juan Yu; Li-Yu Jin; Bo Zhang; Jian-Sheng Liu (Sugar Tech, 2021)

Human β-Defensin 118 Attenuates Escherichia coli K88–Induced Inflammation and Intestinal Injury in Mice - Qian Lin; Qingqing Fu; Xiang Li; Yuheng Luo; Junqiu Luo; Daiwen Chen; Xiangbing Mao; Bing Yu; Ping Zheng; Zhiqing Huang; Jie Yu; Hui Yan; et al. (Probiotics and Antimicrobial Proteins, 2021)

Transgenic eukaryotic microalgae as green factories: providing new ideas for the production of biologically active substances - Qianwen Shi; Cheng Chen; Wei Zhang; Ping Wu; Meng Sun; Hui Wu; Haizhen Wu; Pengcheng Fu; Jianhua Fan (Journal of Applied Phycology, 2021)

Polymetamorphic events in the Jiao-Liao-Ji Belt, North China Craton：Evidence from integrated zircon, xenotime, and monazite LA–ICP–MS U–Pb dating - Ping-Hua Liu; Fu-Lai Liu; Zhong-Hua Tian; Da Wang; Jia Cai; Wen Zhang (International Geology Review, 2021)

The roles of NLRP3 inflammasome-mediated signaling pathways in hyperuricemic nephropathy - Li Wen; Hongliu Yang; Liang Ma; Ping Fu (Molecular and Cellular Biochemistry, 2021)

Warming Iron-Limited Oceans Enhance Nitrogen Fixation and Drive Biogeographic Specialization of the Globally Important Cyanobacterium Crocosphaera - Nina Yang; Carlin A. Merkel; Yu-An Lin; Naomi M. Levine; Nicholas J. Hawco; Hai-Bo Jiang; Ping-Ping Qu; Michelle A. DeMers; Eric A. Webb; Fei-Xue Fu; David A. Hutchins (Frontiers in Marine Science, 2021)
Primary productivity in the nutrient-poor subtropical ocean gyres depends on new nitrogen inputs from nitrogen fixers that convert inert dinitrogen gas into bioavailable forms. Temperature and iron (Fe) availability constrain marine nitrogen fixation, and both are changing due to anthropogenic ocean warming. We examined the physiological responses of the globally important marine nitrogen fixer, Crocosphaera watsonii across its full thermal range as a function of iron availability. At the lower end of its thermal range, from 22 to 27°C, Crocosphaera growth, nitrogen fixation, and Nitrogen-specific Iron Use Efficiencies (N-IUEs, mol N fixed hour –1 mol Fe –1 ) increased with temperature. At an optimal growth temperature of 27°C, N-IUEs were 66% higher under iron-limited conditions than iron-replete conditions, indicating that low-iron availability increases metabolic efficiency. However, Crocosphaera growth and function decrease from 27 to 32°C, temperatures that are predicted for an increasing fraction of tropical oceans in the future. Altogether, this suggests that Crocosphaera are well adapted to iron-limited, warm waters, within prescribed limits. A model incorporating these results under the IPCC RCP 8.5 warming scenario predicts that Crocosphaera N-IUEs could increase by a net 47% by 2100, particularly in higher-latitude waters. These results contrast with published responses of another dominant nitrogen fixer ( Trichodesmium ), with predicted N-IUEs that increase most in low-latitude, tropical waters. These models project that differing responses of Crocosphaera and Trichodesmium N-IUEs to future warming of iron-limited oceans could enhance their current contributions to global marine nitrogen fixation with rates increasing by ∼91 and ∼22%, respectively, thereby shifting their relative importance to marine new production and also intensifying their regional divergence. Thus, interactive temperature and iron effects may profoundly transform existing paradigms of nitrogen biogeochemistry and primary productivity in open ocean regimes.

The MYB transcription factor Baymax1 plays a critical role in rice male fertility - Xiao-Jiao Xiang; Lian-Ping Sun; Ping Yu; Zheng-Fu Yang; Pei-Pei Zhang; Ying-Xin Zhang; Wei-Xun Wu; Dai-Bo Chen; Xiao-Deng Zhan; Riaz-Muhammad Khan; Adil Abbas; Shi-Hua Cheng; et al. (Theoretical and Applied Genetics, 2021)

Potential N mineralization and availability to maize in black soils in response to soil fertility improvement in Northeast China - HaiMei Fu; YingHua Duan; Ping Zhu; HongJun Gao; MingGang Xu; XiaoMei Yang (Journal of Soils and Sediments, 2021)

Differential response of microbial diversity and abundance to hydrological residual time and age in cascade reservoirs - Yihong Yue; Fushun Wang; Zhiwei Fu; Yi Tang; Jing Ma; Yong Qin; Meng Li; Ming Yang; Xue-Ping Chen (Journal of Soils and Sediments, 2021)

The role of MYB proto-oncogene like 2 in tamoxifen resistance in breast cancer - Xia Li; Xi Zhang; Cong-Cong Wu; Ping-Ping Li; Yi-Mou Fu; Li-Hua Xie; Shuang-Shuang Sun; Ying-Ying Zhou; Bao-Ling Zhu (Journal of Molecular Histology, 2021)

Cosmosporasides F–H, three new sugar alcohol conjugated acyclic sesquiterpenes from a Fusarium oxysporum fungus - Ying Fu; Ping Wu; Jinghua Xue; Mei Zhang; Xiaoyi Wei (Natural Product Research, 2020)

Bisabolane sesquiterpenes from Clausena sanki with their potential anti-inflammatory activities - Shi Hu; Yan-Lei Ma; Jia-Ming Guo; Qing Wen; Gui Yan; Shuo Yang; Yan-Hui Fu; Yan-Ping Liu (Natural Product Research, 2020)

Correction to: Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Chang-Qi Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Effect of Vanadium on Growth, Photosynthesis, Reactive Oxygen Species, Antioxidant Enzymes, and Cell Death of Rice - Muhammad Mohsin Altaf; Xiao-ping Diao; Atique ur Rehman; Muhammad Imtiaz; Awais Shakoor; Muhammad Ahsan Altaf; Haseeb Younis; Pengcheng Fu; Muhammad Usman Ghani (Journal of Soil Science and Plant Nutrition, 2020)

Differences in evaporite geochemistry of the greater Ordos Ordovician salt basin, China: evidence from the M56 submember of the Majiagou Formation - Fu Fan; Fan-Wei Meng; Yong-Sheng Zhang; Mian-Ping Zheng; Kui Su; En-Yuan Xing (Carbonates and Evaporites, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

Nanostructure of DiR-Loaded Solid Lipid Nanoparticles with Potential Bioimaging Functions - Lei Shu; Fangqin Fu; Zhengwei Huang; Ying Huang; Ping Hu; Xin Pan (AAPS PharmSciTech, 2020)

Stability Analysis of Unsaturated Slopes Considering Combined Influences of Strength Non-homogeneity and Non-saturation - Dan-ping Gu; Tong-hua Ling; Fu Huang; Liang Zhang (Geotechnical and Geological Engineering, 2020)

Combined effects of green manure returning and addition of sewage sludge compost on plant growth and microorganism communities in gold tailings - Yan-Jun Ai; Fu-Ping Li; Hai-Hong Gu; Xiao-Jie Chi; Xue-Tao Yuan; Dong-Yun Han (Environmental Science and Pollution Research, 2020)

Effects of different treatments on genes related to polysaccharide content in Dendrobium huoshanense - Jun Dai; Xing-bang Han; Nai-fu Chen; Cun-wu Chen; Nai-dong Chen; Xiang-wen Song; Xue-ping Jiang; Yu-juan Wang (Brazilian Journal of Botany, 2020)

Prenylated isoflavones with potential antiproliferative activities from Mappianthus iodoides - Yan-Ping Liu; Li-Li Sun; Xiang-Lin Zhang; Hai-Yuan Niu; Zheng-Hong Pan; Yan-Hui Fu (Natural Product Research, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Responses of Primary Afferent Fibers to Acupuncture-Like Peripheral Stimulation at Different Frequencies: Characterization by Single-Unit Recording in Rats - Ran Huo; Song-Ping Han; Feng-Yu Liu; Xiao-Jing Shou; Ling-Yu Liu; Tian-Jia Song; Fu-Jun Zhai; Rong Zhang; Guo-Gang Xing; Ji-Sheng Han (Neuroscience Bulletin, 2020)

Distribution patterns and source identification for heavy metals in Mirs Bay of Hong Kong in China - Mei-Lin Wu; Hao Cheng; Hui Zhao; Fu-Lin Sun; Yu-Tu Wang; Jian-Ping Yin; Jiao Fei; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Phytoplankton community, structure and succession delineated by partial least square regression in Daya Bay, South China Sea - Mei-Lin Wu; Yu-Tu Wang; Hao Cheng; Fu-lin Sun; Jiao Fei; Cui-Ci Sun; Jian-Ping Yin; Hui Zhao; You-Shao Wang (Ecotoxicology, 2020)

Serotonin-induced miR-221/222 contribute to the activation of hepatic stellate cells - Yi Xiang; Yu-Shui Ma; Ji-Bin Liu; Zhi-Jun Wu; Xiao-Ping Wang; Li-Ping Liu; Gao-Ren Wang; Da Fu; Wei Shi (Biologia, 2020)

Estimation of PM2.5 Mass Concentration from Visibility - Denghui Ji; Zhaoze Deng; Xiaoyu Sun; Liang Ran; Xiangao Xia; Disong Fu; Zijue Song; Pucai Wang; Yunfei Wu; Ping Tian; Mengyu Huang (Advances in Atmospheric Sciences, 2020)
Aerosols in the atmosphere not only degrade visibility, but are also detrimental to human health and transportation. In order to develop a method to estimate PM 2.5 mass concentration from the widely measured visibility, a field campaign was conducted in Southwest China in January 2019. Visibility, ambient relative humidity (RH), PM 2.5 mass concentrations and scattering coefficients of dry particles were measured. During the campaign, two pollution episodes, i.e., from 4–9 January and from 10–16 January, were encountered. Each of the two episodes could be divided into two periods. High aerosol hygroscopicity was found during the first period, when RH was higher than 80% at most of the time, and sometimes even approached 100%. The second period experienced a relatively dry but more polluted condition and aerosol hygroscopicity was lower than that during the first period. An empirical relationship between PM 2.5 mass concentration and visibility (ambient aerosol extinction) under different RH conditions could thus be established. Based on the empirical relationship, PM 2.5 mass concentration could be well estimated from visibility and RH. This method will be useful for remote sensing of PM 2.5 mass concentration.

Bioactive Eudesmane sesquiterpenes from Artabotrys hongkongensis Hance - Qing Wen; Yan-Ping Liu; Gui Yan; Shuo Yang; Shi Hu; Jing Hua; Wen-Qing Yin; Guang-Ying Chen; Yan-Hui Fu (Natural Product Research, 2020)

Tracking fluid sources for skarn formation using scapolite geochemistry: an example from the Jinshandian iron skarn deposit, Eastern China - Li-Ping Zeng; Xin-Fu Zhao; Johannes Hammerli; Tian-Wei-Teng Fan; Carl Spandler (Mineralium Deposita, 2020)

Automatic Striatal ROI Delineation for Semi-quantitative Analysis of 99mTc-TRODAT-1 Brain SPECT Imaging - Bang-Hung Yang; Kang-Ping Lin; Mei-Fen Chen; Jui-Hung Weng; Pan-Fu Kao; Wen-Chen Lin; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2020)

Experimental and numerical research on migration of LNAPL contaminants in fractured porous media - Yong Huang; Ping Wang; Zhimin Fu; Huan Shen (Hydrogeology Journal, 2020)

Biological Aerosol Particles in Polluted Regions - Wei Hu; Zihan Wang; Shu Huang; Lujie Ren; Siyao Yue; Ping Li; Qiaorong Xie; Wanyu Zhao; Lianfang Wei; Hong Ren; Libin Wu; Junjun Deng; et al. (Current Pollution Reports, 2020)

Synthesis and biological effects of naphthalene-chalcone derivatives - Qing-Hao Jin; Hong-Hai Chen; Wen-Bo Chen; Zhi-Yang Fu; Li-Ping Guan; Hai-Ying Jiang (Medicinal Chemistry Research, 2020)

Influence of Sediment Characteristics on Heavy Metal Fraction Distribution in the Water-Level Fluctuation Zone of the Three Gorges Reservoir Area, China - Chuan Fu; Qiaojuan Lan; Yan Wu; Bin Yan; Wei Ping; Lianqi Huang; Binrong Yang (Water, Air, & Soil Pollution, 2020)

Transcriptome profiling reveals cytokinin promoted callus regeneration in Brassica juncea - Hongchen Lu; Ping Xu; Kaining Hu; Qing Xiao; Jing Wen; Bin Yi; Chaozhi Ma; Jinxing Tu; Tingdong Fu; Jinxiong Shen (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Antiproliferative effect of 2-Hydroxy-6-tridecylbenzoic acid from ginkgo biloba sarcotestas through the aryl hydrocarbon receptor pathway in triple-negative breast cancer cells - Dayu Zhou; Chunying Jiang; Chenghao Fu; Ping Chang; Bin Yang; Jiadi Wu; Xiaohui Zhao; Shiliang Ma (Natural Product Research, 2020)

Prolonged Neo-Tethyan magmatic arc in Myanmar: evidence from geochemistry and Sr–Nd–Hf isotopes of Cretaceous mafic–felsic intrusions in the Banmauk–Kawlin area - Jin-Xiang Li; Wei-Ming Fan; Li-Yun Zhang; Tou-Ping Peng; Ya-Li Sun; Lin Ding; Fu-Long Cai; Kyaing Sein (International Journal of Earth Sciences, 2020)

Isolation, identification and character analysis of Streptococcus dysgalactiae from Megalobrama terminalis - Fei Zhao; Shan He; Ai‐ping Tan; Xue‐zhong Guo; Lan Jiang; Cui Liu‐Fu; Yu‐ting Deng; Rui‐quan Zhang (Journal of Fish Diseases, 2020)
Pure bacterial cultures were isolated from different tissues of moribund Megalobrama terminalis from a high mortality event that occurred at a farm in Foshan, China. Two isolates (F2 and F3) were identified as Streptococcus dysgalactiae subsp. dysgalactiae based on morphological and biochemical detection as well as molecular analysis. In brain heart infusion broth, the best growth conditions of isolate F3 were 35ºC, salinity 5‰ and pH 7. Furthermore, infection with isolate F3 (1.2 × 10 6 CFU/fish) led to the death of M. terminalis and zebrafish ( Danio rerio ). However, isolate F3 had no obvious pathogenicity to tilapia (GIFT, Oreochromis niloticus ). When the water temperature was 29ºC, the corresponding mortality rates for zebrafish infected by isolate F3 were higher than those at 23ºC. Culture for 24 and 72 hr with isolate F3 resulted in the same mortality rates for zebrafish. The antimicrobial susceptibility assay revealed that isolate F3 was susceptible to ampicillin, florfenicol and several other antibiotics but resistant to nalidixic acid, streptomycin, sulfamethoxazole/trimethoprim, neomycin and amikacin. To our knowledge, this is the first report that S. dysgalactiae infected the subtropical freshwater fish M. terminalis , which indicates that this bacterium is a potential threat to subtropical freshwater fish.

EFFECT OF A ROOT‐ZONE INJECTION IRRIGATION METHOD ON WATER PRODUCTIVITY AND APPLE PRODUCTION IN A SEMI‐ARID REGION IN NORTH‐WESTERN CHINA - Yan‐Ping Wang; Lin‐Sen Zhang; Yan Mu; Wei‐Hong Liu; Fu‐Xing Guo; Tian‐Ran Chang (Irrigation and Drainage, 2020)
Within the Chinese Loess Plateau, water resources are scarce and irrigation efficiency is a challenging issue. Traditional surface drip irrigation (SDI) methods have failed to improve irrigation efficiency and reduce surface evaporation in the region. An easy‐to‐install and practicable root‐zone injection irrigation (RII) method, with a low risk of emitter clogging and which uses subsurface infiltration‐promoting apparatuses (SIPA) to deliver water directly to the root zone, was designed and tested in an apple orchard over 3 years in northern Shaanxi, China. In the 0–0.6 m soil layer (where the apple roots are concentrated), the RII method produced consistently higher soil water content than the SDI method over all three growing seasons. The soil water content was consistently higher than 60% of field capacity, thus meeting the water requirements of fruit‐bearing apple trees. In addition, the RII method alleviated soil desiccation, significantly increased apple yields and improved fruit quality compared with the SDI method using the same volume of irrigation water. Both irrigation efficiency and water‐use efficiency were improved with the RII method. These results provide a theoretical basis for the utilization of the RII irrigation method in apple orchards in semi‐arid regions, which may improve water conservation and the sustainability of apple production. © 2019 John Wiley & Sons, Ltd.

Reduction of the Criteria System for Identifying Effective Reservoirs in the Joint Operation of a Flood Control System - Jieyu Li; Ping-an Zhong; Feilin Zhu; Juan Chen; Minzhi Yang; Jisi Fu; Weifeng Liu (Water Resources Management, 2020)

Identification of rs11615992 as a novel regulatory SNP for human P2RX7 by allele-specific expression - Tao Peng; Li Zhong; Jing Gao; Zhu Wan; Wei-Ping Fu; Chang Sun (Molecular Genetics and Genomics, 2020)

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Carbazole alkaloids from Clausena emarginata with their potential antiproliferative activities - Yan-Hui Fu; Yan-Lei Ma; Gui Yan; Qing Wen; Shi Hu; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Ping Liu (Natural Product Research, 2019)

Inositol as a new enhancer for improving lipid production and accumulation in Schizochytrium sp. SR21 - Zhao-Xin Liu; Shuai You; Bin-Ping Tang; Bo Wang; Sheng Sheng; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2019)

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

Evaluation of Coherence Between ECG and PPG Derived Parameters on Heart Rate Variability and Respiration in Healthy Volunteers With/Without Controlled Breathing - Hao-Yu Jan; Mei-Fen Chen; Tieh-Cheng Fu; Wen-Chen Lin; Cheng-Lun Tsai; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2019)

Furanocoumarins with potential antiproliferative activities from Clausena lenis - Yan-Ping Liu; Qing Wen; Shi Hu; Yan-Lei Ma; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Hui Fu; Shen-Xiang Qiu (Natural Product Research, 2019)

Microsatellite records for volume 11, issue 3 - Pengfei Hu; Hao-Xiang Liu; Ying Pan; Yan-Fu Qu; Xueqi Tian; Ke-Xin Wang; Yu-Heng Wei; Xue-Ping Wu; Xiumei Xing; Zhengyi Zhang; Pei Zhao; Yu-Tian Zhao; et al. (Conservation Genetics Resources, 2019)

The effects of simulated deposited nitrogen on nutrient dynamics in decomposing litters across a wide quality spectrum using a 15N tracing technique - Xue-Min Ye; Yang Zhang; Fu-Sheng Chen; G. Geoff Wang; Xiang-Min Fang; Xiao-Fan Lin; Song-Ze Wan; Ping He (Plant and Soil, 2019)

Synthesis and biological evaluation of novel disulfides incorporating 1,3,4-thiadiazole scaffold as promising antitumor agents - Sha Li; Hai-Xin Wang; Hai-Ying Liu; Fen Jing; Xiao-Yun Fu; Cai-Wen Li; Yan-Ping Shi; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

5-Azacytidine and trichostatin A enhance the osteogenic differentiation of bone marrow mesenchymal stem cells isolated from steroid-induced avascular necrosis of the femoral head in rabbit - Peng Zhang; Fulin Tao; Qinghu Li; Shuai Wu; Baisheng Fu; Ping Liu (Journal of Biosciences, 2019)

Recent research progress in geochemical properties and restoration of heavy metals in contaminated soil by phytoremediation - Jiang-tao Fu; Dong-mei Yu; Xi Chen; Ying Su; Cai-hong Li; Yong-ping Wei (Journal of Mountain Science, 2019)

Numerical simulation of ground motion amplification in Modong area, Lushan - Chao Han; Jiashun Yu; Wei-Zu Liu; Jian-Long Yuan; Xiao-Bo Fu; Xiao-Ping Hou (Applied Geophysics, 2019)

Biologically active oligostilbenes from the stems of Vatica mangachapoi and chemotaxonomic significance - Shou-Yuan Wu; Yan-Hui Fu; Qi Zhou; Meng Bai; Guang-Ying Chen; Chang-Ri Han; Xiao-Ping Song (Natural Product Research, 2019)

Extreme stress threatened double rice production in Southern China during 1981–2010 - Sheng-Li Liu; Xing Wang; Shou-Tian Ma; Xin Zhao; Fu Chen; Xiao-Ping Xiao; Rattan Lal; Hai-Lin Zhang (Theoretical and Applied Climatology, 2019)

Spatial variation of the relationship between transport accessibility and the level of economic development in Qinghai-Tibet Plateau, China - Xue-ting Yang; Xiao-ping Qiu; Yi-ping Fang; Yun Xu; Fu-biao Zhu (Journal of Mountain Science, 2019)

F‐box proteins MoFwd1, MoCdc4 and MoFbx15 regulate development and pathogenicity in the rice blast fungus Magnaporthe oryzae - Huan‐Bin Shi; Nan Chen; Xue‐Ming Zhu; Shuang Liang; Lin Li; Jiao‐Yu Wang; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2019)
Summary The Skp1‐Cul1‐F‐box‐protein (SCF) ubiquitin ligases are important parts of the ubiquitin system controlling many cellular biological processes in eukaryotes. However, the roles of SCF ubiquitin ligases remain unclear in phytopathogenic Magnaporthe oryzae . Here, we cloned 24 F‐box proteins and confirmed that 17 proteins could interact with MoSkp1, showing their potential to participate in SCF complexes. To determine their functions, null mutants of 21 F‐box‐containing genes were created. Among them, the F‐box proteins MoFwd1, MoCdc4 and MoFbx15 were found to be required for growth, development and full virulence. Fluorescent‐microscopy observations demonstrated that both MoFbx15 and MoCdc4 were localized to the nucleus, compared with MoFwd1, which was distributed in the cytosol. MoCdc4 and MoFwd1 bound to MoSkp1 via the F‐box domain, the deletion of which abrogated their function. Race tube and qRT‐PCR assays confirmed that MoFwd1 was involved in circadian rhythm by regulating transcription and protein stability of the core circadian clock regulator MoFRQ . Moreover, MoFWD1 also orchestrates conidial germination by influencing conidial amino acids pools and oxidative stress release. Overall, our results indicate that SCF ubiquitin ligases play indispensable roles in development and pathogenicity in M. oryzae .

Suppression of Fusarium wilt of banana by combining acid soil ameliorant with biofertilizer made from Bacillus velezensis H-6 - Jianfeng Huang; Yuwan Pang; Fabao Zhang; Qiaoyi Huang; Mu Zhang; Shuanhu Tang; Hongting Fu; Ping Li (European Journal of Plant Pathology, 2019)

Evaluation of the integrated multi-satellite retrievals for global precipitation measurement over the Tibetan Plateau - Lu Ma; Lin Zhao; Li-ming Tian; Li-ming Yuan; Yao Xiao; Le-le Zhang; De-fu Zou; Yong-ping Qiao (Journal of Mountain Science, 2019)

Water Resources Allocation in Transboundary River Basins Based on a Game Model Considering Inflow Forecasting Errors - Jisi Fu; Ping-an Zhong; Juan Chen; Bin Xu; Feilin Zhu; Yu Zhang (Water Resources Management, 2019)

Identification and Characterization of ATP/ADP Isopentenyltransferases (ATP/ADP PpIPTs) Genes in Peach - Min-ji Li; Qin-ping Wei; Fu-tian Peng; Wen Yu; Jing-jing Luo; Yong-fei Zhao (Journal of Plant Growth Regulation, 2019)

Correction to: Elicitation of Isatis tinctoria L. hairy root cultures by salicylic acid and methyl jasmonate for the enhanced production of pharmacologically active alkaloids and flavonoids - Qing-Yan Gai; Jiao Jiao; Xin Wang; Yu-Ping Zang; Li-Li Niu; Yu-Jie Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Pyrosequencing of nirS gene revealed spatial variation of denitrifying bacterial assemblages in response to wetland desertification at Tibet plateau - Yun-fu Gu; Ting Liu; Yan Bai; Quan-ju Xiang; Xiao-ping Zhang; Qiang Chen (Journal of Mountain Science, 2019)

Structurally diverse diterpenoids from Trigonostemon howii - Yan-Ping Liu; Qing Wen; Shi Hu; Yan-Lei Ma; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Hui Fu (Natural Product Research, 2019)

Elicitation of Isatis tinctoria L. hairy root cultures by salicylic acid and methyl jasmonate for the enhanced production of pharmacologically active alkaloids and flavonoids - Qing-Yan Gai; Jiao Jiao; Xin Wang; Yu-Ping Zang; Li-Li Niu; Yu-Jie Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Skinfold thickness for rivastigmine patch application in Alzheimer’s disease - Ping-Song Chou; Kai-Ming Jhang; Ling-Chun Huang; Wen-Fu Wang; Yuan-Han Yang (Psychopharmacology, 2019)

Coupled evolution of Neoproterozoic arc mafic magmatism and mantle wedge in the western margin of the South China Craton - Jun-Hong Zhao; Mei-Fu Zhou; Yuan-Bao Wu; Jian-Ping Zheng; Wei Wang (Contributions to Mineralogy and Petrology, 2019)

Correction to: Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2019)

Microsatellite records for volume 11, issue 1 - Da-Qing Chen; Zaijie Dong; Min Fang; Jianjun Fu; Xiang-Yang Jia; Bingjie Jiang; Jingmiao Li; Qingqing Li; Suhui Liao; Ping Liu; Yulin Liu; Guocheng Shu; et al. (Conservation Genetics Resources, 2019)

Nonstationary inversion-based directional deconvolution of airgun array signature - Hao Li; Guo-Fa Li; Xiang-Hui Guo; Xi-Ping Sun; Jian-Fu Wang (Applied Geophysics, 2019)

A new morphinandienone alkaloid from the stems of Fissistigma tungfangense - Qi Zhou; Yan-Hui Fu; Yu-Qin Zhang; Shou-Yuan Wu; Xiao-Ping Song; Wei Xu; Guang-Ying Chen (Natural Product Research, 2019)

Programmed cell death induced by cadmium stress and/or boron deprivation in tobacco (Nicotiana tabacum L.) cultivar Bright Yellow 2 cells - Li Ping Jiang; Lin Zi; Xiao Fang Liu; Zi-Xi Liu; Lai Fu Zhong; Xiang Xin Xue (In Vitro Cellular & Developmental Biology - Plant, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Profiling of indole metabolic pathway in thermo-sensitive Bainong male sterile line in wheat (Triticum aestivum L.) - Qing Su; Jing Yang; Qing Yun Fu; Fei Yun Jia; Suo Ping Li; Yong Li; You Yong Li (Physiology and Molecular Biology of Plants, 2019)

Study on synthesis and biological effects of a series of 3,4-dihydroisoquinoline-2(1H)-carboxamide derivatives - Zhi-Yang Fu; Qing-Hao Jin; Ya-Nan Xia; Hai-Ying Jiang; Li-Ping Guan (Medicinal Chemistry Research, 2019)

Biochar can improve the soil quality of new creation farmland on the Loess Plateau - Cui-Cui Su; Ji-Fu Ma; Yi-Ping Chen (Environmental Science and Pollution Research, 2019)

Role of permafrost in resilience of social-ecological system and its spatio-temporal dynamics in the source regions of Yangtze and Yellow Rivers - Yi-ping Fang; Fu-biao Zhu; Shu-hua Yi; Xiao-ping Qiu; Yong-jian Ding (Journal of Mountain Science, 2019)

Cytotoxic indole alkaloids from Nauclea orientalis - Yan-Ping Liu; Peng-Kun Ju; Jin-Tao Long; Liang Lai; Wan-Hui Zhao; Chao Zhang; Zhi-Jie Zhang; Yan-Hui Fu (Natural Product Research, 2018)

Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2018)

Phytoplankton pigment pattern in the subsurface chlorophyll maximum in the South Java coastal upwelling system, Indonesia - Chunlei Gao; Mingzhu Fu; Hongjun Song; Lei Wang; Qinsheng Wei; Ping Sun; Lin Liu; Xuelei Zhang (Acta Oceanologica Sinica, 2018)

A new polyoxygenated abietane diterpenoid from the rattans of Bauhinia championii (Benth.) Benth - Li-Ping Hua; Yu-Qin Zhang; Miao Ye; Wen Xu; Xiao-Ying Wang; Yan-Hui Fu; Wei Xu (Natural Product Research, 2018)

Shifts in the structure and function of the microbial community in response to metal pollution of fresh water sediments in Finland - Xue-Ping Chen; Hao-Yu Chen; Jing Sun; Xu Zhang; Chi-Quan He; Xiao-Yan Liu; Xin Huang; Min Yang; Fu-Shun Wang; Kristiina Väänänen (Journal of Soils and Sediments, 2018)

A new abietane diterpenoid from the roots of Tripterygium regelii - Zhi-Hua Jiang; Yan-Ping Liu; Miao He; Jin-Hua Zhao; Ting-Ting Wang; Xing-Yang Feng; Hao Yue; Ren-Bo An; Yan-Hui Fu (Natural Product Research, 2018)

Gram-negative bacilli-derived peptide antibiotics developed since 2000 - Yun Xue; Mengya Wang; Pengchao Zhao; Chunshan Quan; Xin Li; Lina Wang; Weina Gao; Jinghua Li; Xiangyang Zu; Dongliao Fu; Shuxiao Feng; Ping Li (Biotechnology Letters, 2018)

Bioactive furanocoumarins from the stems and leaves of Clausena hainanensis - Yan-Lei Ma; Chao Zhang; Wan-Hui Zhao; Shi Shi; Dan-Nv He; Pan Zhang; Xiao-Hong Liu; Ting-Ting Han; Yan-Hui Fu; Yan-Ping Liu (Natural Product Research, 2018)

Comparison of gene co-networks reveals the molecular mechanisms of the rice (Oryza sativa L.) response to Rhizoctonia solani AG1 IA infection - Jinfeng Zhang; Wenjuan Zhao; Rong Fu; Chenglin Fu; Lingxia Wang; Huainian Liu; Shuangcheng Li; Qiming Deng; Shiquan Wang; Jun Zhu; Yueyang Liang; Ping Li; et al. (Functional & Integrative Genomics, 2018)

The impacts of environmental governance on political turnover of municipal party secretary in China - Gen-Fu Feng; Minyi Dong; Jun Wen; Chun-Ping Chang (Environmental Science and Pollution Research, 2018)

An inversion of transient electromagnetic data from a conical source - Hai-Yan Yang; Feng-Ping Li; Shen-En Chen; Jian-Hua Yue; Fu-Sheng Guo; Xiao Chen; Hua Zhang (Applied Geophysics, 2018)

Impacts of a Compound Amendment on Cd Immobilization, Enzyme Activities and Crop Uptake in Acidic Cd-Contaminated Paddy Soils - Shiping Shan; Zhaohui Guo; Ping Lei; Wei Cheng; Minxi Wu; Zujiao Fu; Shandong Wu; Dongxia Du; Liyang Wu (Bulletin of Environmental Contamination and Toxicology, 2018)

Lateral instability and tunnel erosion of a submarine pipeline: competition mechanism - Yu-min Shi; Fu-ping Gao (Bulletin of Engineering Geology and the Environment, 2018)

A new polyoxygenated cyclohexene derivative from Artabotrys hainanensis - Jin-Ying Tang; Yan-Ping Liu; Peng-Kun Ju; Xiu-Lan Luo; Zhi-Jie Zhang; Peng Ren; Liang Lai; Guang-Ying Chen; Yan-Hui Fu (Natural Product Research, 2018)

Evaluation of global climate model on performances of precipitation simulation and prediction in the Huaihe River basin - Yenan Wu; Ping-an Zhong; Bin Xu; Feilin Zhu; Jisi Fu (Theoretical and Applied Climatology, 2018)

Origin and tectonic evolution of early Paleozoic arc terranes abutting the northern margin of North China Craton - Hao Zhou; Fu-Ping Pei; Ying Zhang; Zhong-Biao Zhou; Wen-Liang Xu; Zhi-Wei Wang; Hua-Hua Cao; Chuan Yang (International Journal of Earth Sciences, 2018)

Seismic prediction method of multiscale fractured reservoir - Ling-Ling Wang; Jian-Xin Wei; Ping Huang; Bang-Rang Di; Fu-Hong Zhang (Applied Geophysics, 2018)

Prodigiosin stimulates endoplasmic reticulum stress and induces autophagic cell death in glioblastoma cells - Shu-Yu Cheng; Nan-Fu Chen; Hsiao-Mei Kuo; San-Nan Yang; Chun-Sung Sung; Ping-Jyun Sung; Zhi-Hong Wen; Wu-Fu Chen (Apoptosis, 2018)

Eriodictyol protects against Staphylococcus aureus-induced lung cell injury by inhibiting alpha-hemolysin expression - He Xuewen; Ouyang Ping; Yuan Zhongwei; Yin Zhongqiong; Fu Hualin; Lin Juchun; He Changliang; Shu Gang; Yuan Zhixiang; Song Xu; Zou Yuanfeng; Li Lixia; et al. (World Journal of Microbiology and Biotechnology, 2018)

A new dihydrochalcone glycoside from the stems of Homalium stenophyllum - Shou-Yuan Wu; Yan-Hui Fu; Qi Zhou; Meng Bai; Guang-Ying Chen; Chang-Ri Han; Xiao-Ping Song (Natural Product Research, 2018)

Failure mode and dynamic response of a double-sided slope with high water content of soil - Bing Yang; Fu-ping Gao; Dong-sheng Jeng (Journal of Mountain Science, 2018)

VPS9 domain‐containing proteins are essential for autophagy and endocytosis in Pyricularia oryzae - Xue‐Ming Zhu; Shuang Liang; Huan‐Bin Shi; Jian‐Ping Lu; Bo Dong; Qian‐Sheng Liao; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2018)
Summary Pyricularia oryzae is the causal pathogen of rice blast disease. Autophagy has been shown to play important roles in P . oryzae development and plant infection. The P. oryzae endosomal system is highly dynamic and has been shown to be associated with conidiogenesis and pathogenicity as well. To date, the crosstalk between autophagy and endocytosis has not been explored in P. oryzae . Here, we identified three P. oryzae VPS9 domain‐containing proteins, PoVps9, PoMuk1 and PoVrl1. We found that PoVps9 and PoMuk1 are localized to vesicles and are each co‐localized with PoVps21, a recognized marker of early endosomes. Deletion of PoVPS9 resulted in severe defects in endocytosis and autophagosome degradation and impaired the localization of PoVps21 to endosomes. Additionally, deletion of the PoMUK1 gene in the Δ Povps9 mutant background exhibited more severe defects in development, autophagy and endocytosis compared with the Δ Povps9 mutant. Pull‐down assay showed that PoVps9 interacts with PoVps21, PoRab11 and PoRab1, which have been verified to participate in endocytosis. Furthermore, yeast two‐hybrid and co‐immunoprecipitation assays confirmed that PoVps9 directly interacts with the GDP form of PoVps21. Thus, PoVps9 is a key protein involved in autophagy and in endocytosis.

Revealing histological and morphological features of female reproductive system in tree shrew (Tupaia belangeri) - Shan Zhong; Shi-yao Zhang; Hui-jie Xing; Xiao-tan Zhang; Guang Wang; Yong-ping Bao; Jiang-nan Fu; Xuesong Yang (Zoomorphology, 2018)

Effects of altitude on county economic development in China - Fu-biao Zhu; Yi-ping Fang; Xue-ting Yang; Xiao-ping Qiu; Hu Yu (Journal of Mountain Science, 2018)

A new isoflavone from the roots of Ficus auriculata - Cui-Cui Qi; Yan-Hui Fu; Wen-Hao Chen; Guang-Ying Chen; Chun-Yan Dai; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2018)

Gradient effect of road transportation on economic development in different geomorphic regions - Xue-ting Yang; Yi-ping Fang; Xiao-ping Qiu; Fu-biao Zhu (Journal of Mountain Science, 2018)

Correction to: Molecular characterization of a genetically divergent equine pegivirus strain identified in China - Gang Lu; Cheng Fu; Ji Huang; Haibin Xu; Peixin Wu; Xiaokun Ping; Shoujun Li (Archives of Virology, 2018)

Molecular characterization of a genetically divergent equine pegivirus strain identified in China - Gang Lu; Cheng Fu; Ji Huang; Haibin Xu; Peixin Wu; Xiaokun Ping; Shoujun Li (Archives of Virology, 2018)

Effect of Temperature–Water Coupled Actions on Joint Morphology - Jing-shuo Liu; Ping Cao; Jie Liu; Jin-xing Fan; Guo-guo Ning; Fu-liang Li (Geotechnical and Geological Engineering, 2017)

Morphological and molecular divergence of Rhipicephalus turanicus tick from Albania and China - Hong-Yu Li; Shan-Shan Zhao; Sándor Hornok; Róbert Farkas; Li-Ping Guo; Chuang-Fu Chen; Ren-Fu Shao; Ji-Zhou Lv; Yuan-Zhi Wang (Experimental and Applied Acarology, 2017)

A two-step sensitivity analysis for hydrological signatures in Jinhua River Basin, East China - Suli Pan; Guangtao Fu; Yen-Ming Chiang; Qihua Ran; Yue-Ping Xu (Hydrological Sciences Journal, 2017)

A Multiobjective Stochastic Programming Model for Hydropower Hedging Operations under Inexact Information - Bin Xu; Ping-an Zhong; Yenan Wu; Fangming Fu; Yuting Chen; Yunfa Zhao (Water Resources Management, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

Artepillin C, is it a good marker for quality control of Brazilian green propolis? - Cui-ping Zhang; Xiao-ge Shen; Jia-wei Chen; Xia-sen Jiang; Kai Wang; Fu-liang Hu (Natural Product Research, 2017)

Testing of antiviral characteristics of flammutoxin in transgenic tobacco - Li-Ping Wu; Xue-Ling Gao; Yuan-Dan Duan; Ye-Yu Bian; Tao Yang; Ming-Jia Fu (Journal of Plant Diseases and Protection, 2017)

The Study of Graph Measurements for Hub Identification in Multiple Parcellated Brain Networks of Healthy Older Adult - Cong Jin; Yi-Ping Chao; Lan Lin; Zhenrong Fu; Baiwen Zhang; Shuicai Wu (Journal of Medical and Biological Engineering, 2017)

Lysophosphatidic acid enhances human umbilical cord mesenchymal stem cell viability without differentiation via LPA receptor mediating manner - Narengerile Li; Ya-Li Yan; Sachaofu Fu; Rui-Juan Li; Peng-Fei Zhao; Xi-Yuan Xu; Jing-Ping Yang; Alatangaole Damirin (Apoptosis, 2017)

Development of Albumin Coupled, Cholesterol Stabilized, Lipid Nanoemulsion of Methotrexate, and TNF-α Inhibitor for Improved In Vivo Efficacy Against Rheumatoid Arthritis - Xiao-yan Li; Hui Li; Yan Zhang; Shan Gao; Chun-ping Dong; Gui-fu Wu (AAPS PharmSciTech, 2017)

A new indole alkaloid with anti-inflammatory activity from Nauclea officinalis - Qing-Long Liu; A-Hong Chen; Jin-Ying Tang; Yan-Lei Ma; Zhi-Hua Jiang; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu; Wei Xu (Natural Product Research, 2017)

Genome-wide analysis of GDSL-type esterases/lipases in Arabidopsis - Chia-Ping Lai; Li-Min Huang; Long-Fang O. Chen; Ming-Tsair Chan; Jei-Fu Shaw (Plant Molecular Biology, 2017)

An analysis of patents for anesthetic laryngoscopes - Cheng-dong Ji; Xin Pan; Yuan-chang Xiong; Xuan Guo; Shu-wen Qian; Chang Xu; Qiang-qiang Fu; Zhi-ping Yang; Yu Ma; Yue-zhu Wan (Journal of Zhejiang University-SCIENCE B, 2017)

Adhesion of bone marrow mesenchymal stem cells on porous titanium surfaces with strontium-doped hydroxyapatite coating - Dan-Li Fu; Qiao-hong Jiang; Fu-ming He; Bai-ping Fu (Journal of Zhejiang University-SCIENCE B, 2017)

Global changes of 5-hydroxymethylcytosine and 5-methylcytosine from normal to tumor tissues are associated with carcinogenesis and prognosis in colorectal cancer - Yi-ping Tian; Ai-fen Lin; Mei-fu Gan; Hao Wang; Dan Yu; Chong Lai; Dan-dan Zhang; Yi-min Zhu; Mao-de Lai (Journal of Zhejiang University-SCIENCE B, 2017)

Detection of exercise periodic breathing using thermal flowmeter in patients with heart failure - Tieh-Cheng Fu; Wen-Chen Lin; Jong-Shyan Wang; Chao-Hung Wang; Chun-Tien Chang; Cheng-Lun Tsai; Yun-Shien Lee; Kang-Ping Lin (Medical & Biological Engineering & Computing, 2017)

A new norsesquiterpene from the roots of Polyalthia laui - Zhang-Xin Yu; Ming-Ye Zhuo; Xiao-Bao Li; Yan-Hui Fu; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han; Xin-Ming Song; Qi-Jing Fan (Natural Product Research, 2017)

A new monoterpenoid indole alkaloid from Ochrosia elliptica - A-Hong Chen; Qing-Long Liu; Yan-Lei Ma; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu; Wei Xu (Natural Product Research, 2017)

Whole-exome sequencing identified compound heterozygous variants in MMKS in a Chinese pedigree with Bardet-Biedl syndrome - Zhan Qi; Ying Shen; Qian Fu; Wei Li; Wei Yang; Wenshan Xu; Ping Chu; Yaxin Zhang; Hui Wang (Science China Life Sciences, 2017)

A dramatic blood plasticity in hibernating and 14-day hindlimb unloading Daurian ground squirrels (Spermophilus dauricus) - Huan-Xin Hu; Fang-Ying Du; Wei-Wei Fu; Shan-Feng Jiang; Jin Cao; Shen-Hui Xu; Hui-Ping Wang; Hui Chang; Nandu Goswami; Yun-Fang Gao (Journal of Comparative Physiology B, 2017)

Identification of different cytoplasms based on newly developed mitotype-specific markers for marker-assisted selection breeding in Brassica napus L. - Shuangping Heng; Fengyi Chen; Chao Wei; Kaining Hu; Zonghui Yang; Jing Wen; Bin Yi; Chaozhi Ma; Jinxing Tu; Ping Si; Tingdong Fu; Jinxiong Shen (Plant Cell Reports, 2017)

Serum Protein-Based Profiles as Novel Biomarkers for the Diagnosis of Alzheimer’s Disease - Shu Yu; Yue-Ping Liu; Hai-Liang Liu; Jie Li; Yang Xiang; Yu-Hui Liu; Shu-Sheng Jiao; Lu Liu; Yajiang Wang; Weiling Fu (Molecular Neurobiology, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

Platelet receptor Gene (P2Y12, P2Y1) and platelet glycoprotein Gene (GPIIIa) polymorphisms are associated with antiplatelet drug responsiveness and clinical outcomes after acute minor ischemic stroke - Xingyang Yi; Qiang Zhou; Chun Wang; Jing Lin; Ping Liu; Cheng Fu (European Journal of Clinical Pharmacology, 2017)

Cone-shaped source characteristics and inductance effect of transient electromagnetic method - Hai-Yan Yang; Feng-Ping Li; Jian-Hua Yue; Fu-Sheng Guo; Xu-Hua Liu; Hua Zhang (Applied Geophysics, 2017)

Soil application of zinc fertilizer could achieve high yield and high grain zinc concentration in maize - Dun-Yi Liu; Wei Zhang; Peng Yan; Xin-Ping Chen; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2017)

Effects of zinc application rate and zinc distribution relative to root distribution on grain yield and grain Zn concentration in wheat - Dun-Yi Liu; Wei Zhang; Li-Li Pang; Yue-Qiang Zhang; Xiao-Zhong Wang; Yu-Min Liu; Xin-Ping Chen; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2017)

Evolution Mechanism and Rainfall Warning Criteria for Maijianwo Slope in Henan Province, China - Yi-heng Pan; Jian-ping Chen; Li-qing Wu; Wei Wang; Fu-lin Tan (Geotechnical and Geological Engineering, 2017)

Remote sensing Penman–Monteith model to estimate catchment evapotranspiration considering the vegetation diversity - Fawen Li; Runxiang Cao; Yong Zhao; Dongjing Mu; Changfeng Fu; Feng Ping (Theoretical and Applied Climatology, 2017)

Geochemistry of Altungol cap dolostones from the Tarim Basin, NW China - Fan Feng; Ping Guan; Wenhui Liu; Wei Zhang; Peixian Liu; Xing Jian; Ling Fu (Arabian Journal of Geosciences, 2016)

MoRad6‐mediated ubiquitination pathways are essential for development and pathogenicity in Magnaporthe oryzae - Huan‐Bin Shi; Guo‐Qing Chen; Ya‐Ping Chen; Bo Dong; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2016)
Summary The ubiquitin system modulates protein functions through targeting substrates for ubiquitination. Here, E2 conjugating enzyme MoRad6‐related ubiquitination pathways are identified and analyzed in Magnaporthe oryzae , the causal agent of rice blast disease. Disruption of MoRad6 leads to severe defects in growth, sporulation, conidial germination, appressorium formation, and plant infection. To depict the functions of MoRad6, three putative ubiquitin ligases, MoRad18, MoBre1 and MoUbr1, are also characterized. Deletion of MoRad18 causes minor phenotypic changes, while MoBre1 is required for growth, conidiation and pathogenicity in M. oryzae . Defects in ΔMobre1 likely resulted from the reduction in di‐ and tri‐methylation level of Histone 3 lysine 4 (H3K4). Notably, MoUbr1 is crucial for conidial adhesion and germination, possibly by degrading components of cAMP/PKA and mitogen‐activated protein kinase (MAPK) Pmk1 signaling pathways via the N‐end rule pathway. Germination failure of ΔMoubr1 conidia could be rescued by elevation of cAMP level or enhanced Pmk1 phosphorylation resulting from further deletion of MoIra1, the M. oryzae homolog of yeast Ira1/2. These reveal vital effects of cAMP/PKA and MAPK Pmk1 signaling on conidial germination in M. oryzae . Altogether, our results suggest that MoRad6‐mediated ubiquitination pathways are essential for the infection‐related development and pathogenicity of M. oryzae .

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Smoking and Serum Lipid Profiles in Schizophrenia - Hui-Mei An; Yun-Long Tan; Shu-ping Tan; Jing Shi; Zhi-Ren Wang; Fu-De Yang; Xu-Feng Huang; Jair C. Soars; Thomas R. Kosten; Xiang-Yang Zhang (Neuroscience Bulletin, 2016)

Two new triterpenoid glycosides from the stems of Camellia oleifera Abel - Qing-Wei Yan; Hui-Zheng Fu; Yue-Hua Luo; Guo-Ping Zhou; Kai-Hua Wan; Rui-Jian Zhong (Natural Product Research, 2016)

Imperatorin inhibits the expression of alpha-hemolysin in Staphylococcus aureus strain BAA-1717 (USA300) - Ping Ouyang; Junjie Chen; Mao Sun; Zhongqiong Yin; Juchun Lin; Hualin Fu; Gang Shu; Changliang He; Cheng Lv; Xuming Deng; Kaiyu Wang; Yi Geng; et al. (Antonie van Leeuwenhoek, 2016)

Investigation of absorption and scattering characteristics of kiwifruit tissue using a single integrating sphere system - Zhen-huan Fang; Xia-ping Fu; Xue-ming He (Journal of Zhejiang University-SCIENCE B, 2016)

Airborne polybrominated diphenyl ethers (PBDEs), polybrominated dibenzo-p-dioxins/furans (PBDD/Fs), and dechlorane plus (DP) in concentrated vehicle parking areas - Huiru Li; Hehuan Liu; Ligui Mo; Guoying Sheng; Jiamo Fu; Ping’an Peng (Environmental Science and Pollution Research, 2016)

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway - Xiang-Ru Wen; Yan-Yan Fu; Hong-Zhi Liu; Jian Wu; Xiao-Ping Shao; Xun-Bao Zhang; Man Tang; Yue Shi; Kai Ma; Fang Zhang; Yi-Wen Wang; Hui Tang; et al. (Molecular Neurobiology, 2016)

Imbalanced expression of Bcl-xL and Bax in platelets treated with plasma from immune thrombocytopenia - Jianlin Qiao; Yun Liu; Depeng Li; Yulu Wu; Xiaoqian Li; Yao Yao; Mingshan Niu; Chunling Fu; Hongchun Li; Ping Ma; Zhenyu Li; Kailin Xu; et al. (Immunologic Research, 2016)

Epigenetic mechanisms of salt tolerance and heterosis in Upland cotton (Gossypium hirsutum L.) revealed by methylation-sensitive amplified polymorphism analysis - Baohua Wang; Mi Zhang; Rong Fu; Xiaowei Qian; Ping Rong; Yan Zhang; Peng Jiang; Junjuan Wang; Xuke Lu; Delong Wang; Wuwei Ye; Xinyu Zhu (Euphytica, 2016)

Ectomycorrhizae of Tuber huidongense and T. liyuanum with Castanea mollissima and Pinus armandii - Shan-Ping Wan; Fu-Qiang Yu; Li Tang; Ran Wang; Yun Wang; Pei-Gui Liu; Xiang-Hua Wang; Yi Zheng (Mycorrhiza, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Effects of cigarette smoking and alcohol use on neurocognition and BDNF levels in a Chinese population - Xiang Yang Zhang; Yun-Long Tan; Da-Chun Chen; Shu-Ping Tan; Fu-De Yang; Giovana B. Zunta-Soares; Jair C Soares (Psychopharmacology, 2016)

Photodegradation of Mefenamic Acid in Aqueous Media: Kinetics, Toxicity and Photolysis Products - Ping Chen; Feng Liang Wang; Kun Yao; Jing Shuai Ma; Fu Hua Li; Wen Ying Lv; Guo Guang Liu (Bulletin of Environmental Contamination and Toxicology, 2016)

Different Responses of an Invasive Clonal Plant Wedelia trilobata and its Native Congener to Gibberellin: Implications for Biological Invasion - Zhi-Cong Dai; Wei Fu; Shan-Shan Qi; De-Li Zhai; Si-Chong Chen; Ling-Yun Wan; Ping Huang; Dao-Lin Du (Journal of Chemical Ecology, 2016)

Overexpression of a phospholipase Dα gene from Ammopiptanthus nanus enhances salt tolerance of phospholipase Dα1-deficient Arabidopsis mutant - Hao Qiang Yu; Tai Ming Yong; Hong Jie Li; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Planta, 2015)

Isolation and characterization of a crude oil degrading bacteria from formation water: comparative genomic analysis of environmental Ochrobactrum intermedium isolate versus clinical strains - Lu-jun Chai; Xia-wei Jiang; Fan Zhang; Bei-wen Zheng; Fu-chang Shu; Zheng-liang Wang; Qing-feng Cui; Han-ping Dong; Zhong-zhi Zhang; Du-jie Hou; Yue-hui She (Journal of Zhejiang University-SCIENCE B, 2015)

Subcutaneous Injections of the Mannose-Sensitive Hemagglutination Pilus Strain of Pseudomonas aeruginosa Stimulate Host Immunity, Reduce Bladder Cancer Size and Improve Tumor Survival in Mice - Tao Li; Li Yang; Sheng-jun Fu; Er-long Xiao; Xuan Yuan; Jian-zhong Lu; Bao-liang Ma; Ting-kai Shi; Zhi-ping Wang (Cell Biochemistry and Biophysics, 2015)

Direct cloning, expression of a thermostable xylanase gene from the metagenomic DNA of cow dung compost and enzymatic production of xylooligosaccharides from corncob - Ming-zhe Sun; Hong-chen Zheng; Ling-cai Meng; Jun-she Sun; Hui Song; Yun-juan Bao; Hai-sheng Pei; Zheng Yan; Xiu-qing Zhang; Jing-sheng Zhang; Yi-han Liu; Fu-ping Lu (Biotechnology Letters, 2015)

Lipophilic constituents from two processed products and three different parts of Changium smyrnioides Wolff. - Gang-Gang Bai; Fei Yuan; Fu-Qiang Li; Kun-Jun Mao; Ping Zhou; Jian-Wei Chen; Xiang Li (Natural Product Research, 2015)

Screening for simple sequence repeat markers in Puccinia striiformis tritici based on genomic sequence - Gang-ming Zhan; Fu-ping Wang; Huai-yong Luo; Shu-chang Jiang; Wen-ming Zheng; Li-li Huang; Zhen-sheng Kang (Journal of Zhejiang University-SCIENCE B, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

Versicorin, a new lovastatin analogue from the fungus Aspergillus versicolor SC0156 - Ying Fu; Ping Wu; Jinghua Xue; Xiaoyi Wei; Hanxiang Li (Natural Product Research, 2015)

Cloning and functional validation of molybdenum cofactor sulfurase gene from Ammopiptanthus nanus - Hao Qiang Yu; Yuan Yuan Zhang; Tai Ming Yong; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Plant Cell Reports, 2015)

Elevated Serum Homocysteine (Hcy) Levels May Contribute to the Pathogenesis of Cerebral Infarction - Hong-Juan Fu; Li-Bo Zhao; Ju-Jun Xue; Zhi-Xuan Wu; Yue-Ping Huang; Wei Liu; Zhan Gao (Journal of Molecular Neuroscience, 2015)

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

iTRAQ-based quantitative proteomic analysis of longissimus muscle from growing pigs with dietary supplementation of non-starch polysaccharide enzymes - Ji-ze Zhang; Yang Gao; Qing-ping Lu; Ren-na Sa; Hong-fu Zhang (Journal of Zhejiang University-SCIENCE B, 2015)

HSF1 Relieves Amyloid-β-Induced Cardiomyocytes Apoptosis - Beiru Zhang; Ping He; Yonghao Lu; Xiaohui Bian; Xu Yang; Xiaoying Fu; Yan Wu; Detian Li (Cell Biochemistry and Biophysics, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

Hydrogeochemical and isotopic characteristics of groundwater in the salt chemical industrial base of Guyuan City, northwestern China - Ying Li; Fu Sheng Hu; Zhong Qi Xue; Yan Qing Yu; Ping Wu (Arabian Journal of Geosciences, 2015)

Dissipation and Degradation Dynamics of Thifluzamide in Rice Field - Li Na Wei; Ping Wu; Fu Rong Wang; Hong Yang (Water, Air, & Soil Pollution, 2015)

Evaluation of pedotransfer functions for estimating saturated hydraulic conductivity in coastal salt-affected mud farmland - Rong-Jiang Yao; Jing-Song Yang; Dan-Hua Wu; Fu-Rong Li; Peng Gao; Xiang-Ping Wang (Journal of Soils and Sediments, 2015)

Photodegradation of Ibuprofen Under UV–Vis Irradiation: Mechanism and Toxicity of Photolysis Products - Fu Hua Li; Kun Yao; Wen Ying Lv; Guo Guang Liu; Ping Chen; Hao Ping Huang; Ya Pu Kang (Bulletin of Environmental Contamination and Toxicology, 2015)

Optimization of Astragalus membranaceus hairy roots induction and culture conditions for augmentation production of astragalosides - Jiao Jiao; Qing-Yan Gai; Yu-Jie Fu; Wei Ma; Li-Ping Yao; Chen Feng; Xin-Xin Xia (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Matching methods of classic hail echo cores of weather radar - Xue-tao Yu; Xiao-ping Rui; Shuang-xi Fu; Wei Liu (Natural Hazards, 2015)

Clinical effect of postconditioning in ST-elevation myocardial infarction patients treated with primary percutaneous coronary intervention: a meta-analysis of randomized controlled trials - Xian-qing Hu; Jian Cheng; Biao Tang; Zhong-heng Zhang; Ke Huang; Yi-ping Yang; Yan-yan Mao; Ming Zhong; Shen-wen Fu (Journal of Zhejiang University-SCIENCE B, 2015)

Aggregate dynamics and associated soil organic matter in topsoils of two 2,000-year paddy soil chronosequences - Ping Zou; Jianrong Fu; Zhihong Cao; Jing Ye; Qiaogang Yu (Journal of Soils and Sediments, 2015)

The roles of IL-2 and IL-10 enhance anti-CD45RBmAb immune inhibition in allograft skin - Wei-Jian Guo; Hui Qi; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2015)

Protective Effects of Sesaminol on BEAS-2B Cells Impaired by Cigarette Smoke Extract - Ping Dong; Xiao Fu; Xiang Wang; Wen-mei Wang; Wen-ming Cao; Wei-yun Zhang (Cell Biochemistry and Biophysics, 2015)

Optimized Preparation of a 99mTc-Radiolabeled Probe for Tracing MicroRNA - Lei Kang; Xiao-jie Xu; Chao Ma; Rong-fu Wang; Ping Yan; Chun-li Zhang; Hong-wei Sun; Ding Li (Cell Biochemistry and Biophysics, 2015)

Anther development of maize (Zea mays) and longstamen rice (Oryza longistaminata) revealed by cryo-SEM, with foci on locular dehydration and pollen arrangement - Chih-Hua Tsou; Ping-Chin Cheng; Chiung-Maan Tseng; Hsiao-Jung Yen; Yu-Lan Fu; Tien-Rong You; David B. Walden (Plant Reproduction, 2015)

Expression of cytochrome P450 CYP81A6 in rice: tissue specificity, protein subcellular localization, and response to herbicide application - Hai-ping Lu; Martin Edwards; Qi-zhao Wang; Hai-jun Zhao; Hao-wei Fu; Jian-zhong Huang; Angharad Gatehouse; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2015)

Characteristics of Dew Formation and Distribution, and Its Contribution to the Surface Water Budget in a Semi-arid Region in China - Qiang Zhang; Sheng Wang; Fu-Lin Yang; Ping Yue; Tong Yao; Wen-Yu Wang (Boundary-Layer Meteorology, 2015)

Geochronology and provenance of detrital zircons from late Palaeozoic strata of central Jilin Province, Northeast China: implications for the tectonic evolution of the eastern Central Asian Orogenic Belt - Zi-Jin Wang; Wen-Liang Xu; Fu-Ping Pei; Zhi-Wei Wang; Yu Li (International Geology Review, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Effects of combined application of organic and inorganic fertilizers plus nitrification inhibitor DMPP on nitrogen runoff loss in vegetable soils - Qiaogang Yu; Junwei Ma; Ping Zou; Hui Lin; Wanchun Sun; Jianzhen Yin; Jianrong Fu (Environmental Science and Pollution Research, 2015)

Removal and Recovery of U(VI) from Low Concentration Radioactive Wastewater by Ethylenediamine-Modified Biomass of Aspergillus niger - De Xin Ding; Xin Xin; Le Li; Nan Hu; Guang Yue Li; Yong Dong Wang; Ping Kun Fu (Water, Air, & Soil Pollution, 2014)

Different secondary metabolic responses to MeJA treatment in shikonin-proficient and shikonin-deficient cell lines from Arnebia euchroma (Royle) Johnst - Sheng Wang; Lan Ping Guo; Teng Xie; Jian Yang; Jin Fu Tang; Xuan Li; Xiao Wang; Lu Qi Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Evaluation of HODE-15, FDE-15, CDE-15, and BDE-15 toxicity on adult and embryonic zebrafish (Danio rerio) - Li Qin; Fu Liu; Hui Liu; Zhongbo Wei; Ping Sun; Zunyao Wang (Environmental Science and Pollution Research, 2014)

Synthesis and cytotoxic activities of novel bergenin derivatives - Na-Na Liu; Fu-Kai Bao; Jing-Bo Chen; Xiang-Hui Zeng; Shui-Jing Chi; Jian-Ping Liu (Medicinal Chemistry Research, 2014)

Serological report of pandemic and seasonal human influenza virus infection in dogs in southern China - Xin Yin; Fu-Rong Zhao; Dong-Hui Zhou; Ping Wei; Hui-Yun Chang (Archives of Virology, 2014)

Hybridization and mitochondrial genome introgression between Rana chensinensis and R. kukunoris - Yin Qi; Bin Lu; Haiyan Gao; Ping Hu; Jinzhong Fu (Molecular Ecology, 2014)
Mitochondrial genome (mito‐genome) introgression among metazoans is commonplace, and several biological processes may promote such introgression. We examined two proposed processes for the mito‐genome introgression between Rana chensinensis and R. kukunoris : natural hybridization and sex‐biased dispersal. We sampled 477 individuals from 28 sites in the potential hybrid zone in the western Tsinling Mountains. Mitochondrial gene ( cyt ‐ b ) trees were used to examine the introgression events. Microsatellite DNA loci, cyt ‐ b and morphological data were used to identify hybrids and to examine the extent of natural hybridization. We detected rampant bidirectional introgressions, both ancient and recent, between the two species. Furthermore, we found a wide hybrid zone, and frequent and asymmetric hybridization. The hybrid zone cline analysis revealed a clear mitochondrial–nuclear discordance; while most nuclear markers displayed similar and steep clines, cyt ‐ b had a displaced cline centre and a more gradual and wider cline. We also detected strong and asymmetric historical maternal gene flow across the hybrid zone. This widespread hybridization and detected low mito‐nuclear conflicts may, at least partially, explain the high frequency of introgression. Lastly, microsatellite data and population genetic methods were used to assess sex‐biased dispersal. A weak pattern of female‐biased dispersal was detected in both species, suggesting it may not play an important role in the observed introgression. Our data are consistent with the hybridization hypothesis, but support for the sex‐biased dispersal hypothesis is weak. We further suggest that selective advantages of the R. kukunoris ‐type mito‐genome in thermal adaptation may also contribute to the introgression between the two species.

Screening and monitoring zearalenone-producing Fusarium species by PCR and zearalenone by monoclonal antibodies in feed from China - Shi-Chun Pei; Yu-Ping Zhen; Jian-Wei Gao; Won-Jong Lee; Hong-Fu Zhang; Cheng Ji; Xuan-Zhe Zhang; Cong Chen (Food Additives & Contaminants Part B-Surveillance, 2014)

Phenotypic characterization of craniofacial bone marrow stromal cells: unique properties of enhanced osteogenesis, cell recruitment, autophagy, and apoptosis resistance - Weijie Dong; Jie Ge; Ping Zhang; Yu Fu; Ziwen Zhang; Jie Cheng; Hongbing Jiang (Cell and Tissue Research, 2014)

Sodium fluoride induces apoptosis in the kidney of rats through caspase-mediated pathways and DNA damage - Guo Hua Song; Ji Ping Gao; Chun Fang Wang; Chao Yang Chen; Xiao Yan Yan; Min Guo; Yu Wang; Fu Bing Huang (Journal of Physiology and Biochemistry, 2014)

Influence of ciprofloxacin on microbial community structure and function in soils - Hao Cui; Shu-Ping Wang; Jin Fu; Zhi-Qiang Zhou; Na Zhang; Li Guo (Biology and Fertility of Soils, 2014)

Isolation and characterization of phosphate-solubilizing bacteria from betel nut (Areca catechu) and their effects on plant growth and phosphorus mobilization in tropical soils - Fu-Ping Liu; Hai-Qing Liu; Hai-Long Zhou; Zhi-Guo Dong; Xu-Hao Bai; Peng Bai; Jian-Jun Qiao (Biology and Fertility of Soils, 2014)

Architecture and development of a multi-stage Baiyun submarine slide complex in the Pearl River Canyon, northern South China Sea - Lei Wang; Shi-Guo Wu; Qing-Ping Li; Da-Wei Wang; Shao-Ying Fu (Geo-Marine Letters, 2014)

siRNA Combinations Mediate Greater Suppression of Hepatitis B virus Replication in Mice - Guiqiu Li; Lu Fu; Jinghong Jiang; Yuzhuo Ping; Yanjun Huang; Yongchen Wang (Cell Biochemistry and Biophysics, 2014)

Anti-tumor Effects of Gene Therapy with GALV Membrane Fusion Glycoprotein in Lung Adenocarcinoma - Bing Zhu; Jian-ru Yang; Xin-ping Fu; Yue-quan Jiang (Cell Biochemistry and Biophysics, 2014)

Gene Therapy of Lung Adenocarcinoma using Herpes Virus Expressing a Fusogenic Membrane Glycoprotein - Bing Zhu; Jian-ru Yang; Yue-quan Jiang; Shi-feng Chen; Xin-ping Fu (Cell Biochemistry and Biophysics, 2014)

Streptomycin inhibits electrophysiological changes induced by stretching of chronically infarcted rat hearts - Jun-xian Cao; Lu Fu; Qian-ping Gao; Rong-sheng Xie; Fan Qu (Journal of Zhejiang University-SCIENCE B, 2014)

Characterization of OsDREB6 responsive to osmotic and cold stresses in rice - Ya-Guang Ke; Zhi-Jun Yang; Shun-Wu Yu; Tian-Fei Li; Jin-Hong Wu; Huan Gao; Ya-Ping Fu; Li-Jun Luo (Journal of Plant Biology, 2014)

Structure-based design, synthesis, and anticonvulsant activity of isatin-1-N-phenylacetamide derivatives - Chao Xie; Li-Ming Tang; Fu-Nan Li; Li-Ping Guan; Cheng-Yan Pan; Si-Hong Wang (Medicinal Chemistry Research, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Analyzing and modeling rheological behavior of liver fibrosis in rats using shear viscoelastic moduli - Ying Zhu; Yi Zheng; Yuan-yuan Shen; Xin Chen; Xin-yu Zhang; Hao-ming Lin; Yan-rong Guo; Tian-fu Wang; Si-ping Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Geochronology and geochemistry of the Late Triassic Longtan pluton in South China: termination of the crustal melting and Indosinian orogenesis - Liang Qiu; Dan-Ping Yan; Mei-Fu Zhou; Nicholas T. Arndt; Shuang-Li Tang; Liang Qi (International Journal of Earth Sciences, 2014)

Biological and genomic analysis of a PBSX-like defective phage induced from Bacillus pumilus AB94180 - Tingting Jin; Xiaoming Zhang; Yang Zhang; Zhongsheng Hu; Zhengwei Fu; Junpeng Fan; Ming Wu; Yi Wang; Ping Shen; Xiangdong Chen (Archives of Virology, 2014)

Model-based optimisation of nitrogen and water management for wheat–maize systems in the North China Plain - Anna Michalczyk; Kurt Christian Kersebaum; Marco Roelcke; Tobias Hartmann; Shan-Chao Yue; Xin-Ping Chen; Fu-Suo Zhang (Nutrient Cycling in Agroecosystems, 2014)

Estrogen receptor α gene PvuII polymorphism and coronary artery disease: a meta-analysis of 21 studies - Jie Ding; Hui Xu; Xiang Yin; Fu-rong Zhang; Xiao-ping Pan; Yi-an Gu; Jun-zhu Chen; Xiao-gang Guo (Journal of Zhejiang University-SCIENCE B, 2014)

The TNF-alpha -308G/A polymorphism is associated with type 2 diabetes mellitus: an updated meta-analysis - Yuliang Zhao; Zheng Li; Ling Zhang; Yonggang Zhang; Yingying Yang; Yi Tang; Ping Fu (Molecular Biology Reports, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

The vacuoles containing multivesicular bodies: a new observation in interaction between Ustilago esculenta and Zizania latifolia - Jing-ze Zhang; Fu-qiang Chu; De-ping Guo; Mohammad Reza Ojaghian; Kevin D Hyde (European Journal of Plant Pathology, 2014)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Improvement of enamel bond strengths for conventional and resin-modified glass ionomers: acid-etching vs. conditioning - Ling Zhang; Tian Tang; Zhen-liang Zhang; Bing Liang; Xiao-miao Wang; Bai-ping Fu (Journal of Zhejiang University-SCIENCE B, 2013)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Constraints from zircon U–Pb ages, O and Hf isotopic compositions on the origin of Neoproterozoic peraluminous granitoids from the Jiangnan Fold Belt, South China - Jun-Hong Zhao; Mei-Fu Zhou; Jian-Ping Zheng (Contributions to Mineralogy and Petrology, 2013)

Altered miRNA Expression is Associated with Differentiation, Invasion, and Metastasis of Esophageal Squamous Cell Carcinoma (ESCC) in Patients from Huaian, China - Hai Long Fu; De Ping Wu; Xiu Fang Wang; Jian Guo Wang; Feng Jiao; Lei Lei Song; Hui Xie; Xu Yang Wen; Hu Sheng Shan; Yun Xiang Du; Ya Ping Zhao (Cell Biochemistry and Biophysics, 2013)

Agricultural Technologies for Enhancing the Phytoremediation of Cadmium-Contaminated Soil by Amaranthus hypochondriacus L. - Ningyu Li; Zhian Li; Qinglin Fu; Ping Zhuang; Bin Guo; Hua Li (Water, Air, & Soil Pollution, 2013)

An approach to evaluate groundwater recharge from streamflow and groundwater records - Wen-Jui Kung; Hsin-Fu Yeh; Hung-I Lin; Wei-Ping Chen; Cheng-Haw Lee (Geosciences Journal, 2013)

Using RPC Block Adjustment models for the accuracy of environmental research, cartography and geomarketing: a new concept of cartography - Fu-Yung Kuan; Yen-Ping Ho; Ruei-Yuan Wang; Cheng-Wu Chen (Stochastic Environmental Research and Risk Assessment, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Differentiation of nelsonitic magmas in the formation of the ~1.74 Ga Damiao Fe–Ti–P ore deposit, North China - Wei Terry Chen; Mei-Fu Zhou; Tai-Ping Zhao (Contributions to Mineralogy and Petrology, 2013)

Interstitial cells of Cajal mediate excitatory sympathetic neurotransmission in guinea pig prostate - Jiang-ping Wang; Guo-fu Ding; Qin-zhang Wang (Cell and Tissue Research, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

An in vivo molecular imaging probe 18F-Annexin B1 for apoptosis detection by PET/CT: preparation and preliminary evaluation - Ming-Wei Wang; Fang Wang; Yu-Jia Zheng; Ying-Jian Zhang; Yong-Ping Zhang; Qing Zhao; Clifton Kwang-Fu Shen; Yue Wang; Shu-Han Sun (Apoptosis, 2013)

Fluid evolution of the Jiawula Ag–Pb–Zn deposit, Inner Mongolia: mineralogical, fluid inclusion, and stable isotopic evidence - De-Gao Zhai; Jia-Jun Liu; Jian-Ping Wang; Mei-Juan Yao; Sheng-Hua Wu; Chao Fu; Zhen-Jiang Liu; Shou-Guang Wang; Yu-Xi Li (International Geology Review, 2013)

Inducible regulation of GDNF expression in human neural stem cells - ShuYan Wang; Ping Ren; YunQian Guan; ChunLin Zou; LinLin Fu; Yu Zhang (Science China Life Sciences, 2013)

Isolation of marine bacteria with antimicrobial activities from cultured and field-collected soft corals - Yu-Hsin Chen; Jimmy Kuo; Ping-Jung Sung; Yu-Chia Chang; Mei-Chin Lu; Tit-Yee Wong; Jong-Kang Liu; Ching-Feng Weng; Wen-Hung Twan; Fu-Wen Kuo (World Journal of Microbiology and Biotechnology, 2012)

Grain and shoot zinc accumulation in winter wheat affected by nitrogen management - Yan-Fang Xue; Shan-Chao Yue; Yue-Qiang Zhang; Zhen-Ling Cui; Xin-Ping Chen; Fu-Chun Yang; Ismail Cakmak; Steve P. McGrath; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2012)

The reduction in zinc concentration of wheat grain upon increased phosphorus-fertilization and its mitigation by foliar zinc application - Yue-Qiang Zhang; Yan Deng; Ri-Yuan Chen; Zhen-Ling Cui; Xin-Ping Chen; Russell Yost; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2012)

Contribution of SATB2 to the stronger osteogenic potential of bone marrow stromal cells from craniofacial bones - Ping Zhang; Jie Men; Yu Fu; Tengfei Shan; Jinhai Ye; Yunong Wu; Zhenjiang Tao; Laikui Liu; Hongbing Jiang (Cell and Tissue Research, 2012)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

A novel dirigent protein gene with highly stem-specific expression from sugarcane, response to drought, salt and oxidative stresses - Guo Jin-long; Xu Li-ping; Fang Jing-ping; Su Ya-chun; Fu Hua-ying; Que You-xiong; Xu Jing-sheng (Plant Cell Reports, 2012)

The impact of E-cadherin expression on non-small cell lung cancer survival: a meta-analysis - Ying Wu; Hong-Bing Liu; Ming Ding; Jian-Nan Liu; Ping Zhan; Xiao-Su Fu; Gan Lu (Molecular Biology Reports, 2012)

Abundance and composition of ammonia-oxidizing bacteria and archaea in different types of soil in the Yangtze River estuary - Xiao-ran Li; Yi-ping Xiao; Wen-wei Ren; Zeng-fu Liu; Jin-huan Shi; Zhe-xue Quan (Journal of Zhejiang University-SCIENCE B, 2012)

Characteristics and sources of non-methane hydrocarbons and halocarbons in wintertime urban atmosphere of Shanghai, China - Ping Song; Fu-Hai Geng; Xue-Fang Sang; Chuen-Yu Chan; Lo-Yin Chan; Qiong Yu (Environmental Monitoring and Assessment, 2012)

Climate Change Adaptation Among Tibetan Pastoralists: Challenges in Enhancing Local Adaptation Through Policy Support - Yao Fu; R. Edward Grumbine; Andreas Wilkes; Yun Wang; Jian-Chu Xu; Yong-Ping Yang (Environmental Management, 2012)

Polycyclic aromatic hydrocarbons in animal-based foods from Shanghai: bioaccessibility and dietary exposure - Ying-Xin Yu; Liang Chen; Dan Yang; Yu-Ping Pang; Shao-Huan Zhang; Xin-Yu Zhang; Zhi-Qiang Yu; Ming-Hong Wu; Jia-Mo Fu (Food Additives & Contaminants: Part A, 2012)

Sprout vacuum-infiltration: a simple and efficient agroinoculation method for virus-induced gene silencing in diverse solanaceous species - Hua-xue Yan; Da-qi Fu; Ben-zhong Zhu; Hai-ping Liu; Xiao-ying Shen; Yun-bo Luo (Plant Cell Reports, 2012)

Molecular biomarkers of colorectal cancer: prognostic and predictive tools for clinical practice - Wei-qin Jiang; Fang-fang Fu; Yang-xia Li; Wei-bin Wang; Hao-hao Wang; Hai-ping Jiang; Li-song Teng (Journal of Zhejiang University-SCIENCE B, 2012)

Neuroprotection by Silencing iNOS Expression in a 6-OHDA Model of Parkinson’s Disease - Min Li; Fu-rong Dai; Xiao-ping Du; Qi-dong Yang; Yuxiang Chen (Journal of Molecular Neuroscience, 2012)

Estrogen improved metabolic syndrome through down-regulation of VEGF and HIF-1α to inhibit hypoxia of periaortic and intra-abdominal fat in ovariectomized female rats - JinWen Xu; QiuLing Xiang; GuiPing Lin; XiaoDong Fu; KeWen Zhou; Ping Jiang; ShuHui Zheng; TingHuai Wang (Molecular Biology Reports, 2012)

Evidence of iron cyanides as supplementary nitrogen source to rice seedlings - Xiao-Zhang Yu; Ping-Ping Shen; Ji-Guang Gu; Yan Zhou; Fu-Zhong Zhang (Ecotoxicology, 2012)

Construction of Escherichia coli strains producing l-serine from glucose - Yu Li; Gu-Kui Chen; Xin-Wei Tong; Hui-Tu Zhang; Xiao-Guang Liu; Yi-Han Liu; Fu-Ping Lu (Biotechnology Letters, 2012)

Structural insights into a human anti-IFN antibody exerting therapeutic potential for systemic lupus erythematosus - Songying Ouyang; Bin Gong; Jin-Zhi Li; Li-Xia Zhao; Wei Wu; Fu-Shun Zhang; Lina Sun; Shu-Jun Wang; Meng Pan; Chuan Li; Wenguang Liang; Neil Shaw; et al. (Journal of Molecular Medicine, 2012)

A role for anti-CD45RB monoclonal antibody treatment upon dendritic cells - Hui Qi; Jin-Peng Liu; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2012)

Cytology and ultrastructure of interactions between Ustilago esculenta and Zizania latifolia - Jing-Ze Zhang; Fu-Qiang Chu; De-Ping Guo; Kevin D. Hyde; Guang-Lin Xie (Mycological Progress, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

Heterogeneous mantle source and magma differentiation of quaternary arc-like volcanic rocks from Tengchong, SE margin of the Tibetan Plateau - Mei-Fu Zhou; Paul T. Robinson; Christina Yan Wang; Jun-Hong Zhao; Dan-Ping Yan; Jian-Feng Gao; John Malpas (Contributions to Mineralogy and Petrology, 2012)

Constraining the mid-crustal channel flow beneath the Tibetan Plateau: data from the Nielaxiongbo gneiss dome, SE Tibet - Dan-Ping Yan; Mei-Fu Zhou; Paul T. Robinson; Djordje Grujic; John Malpas; Allen Kennedy; Peter H. Reynolds (International Geology Review, 2012)

Identification of volatile components in yak butter using SAFE, SDE and HS-SPME-GC/MS - Ning Li; Bao-Guo Sun; Fu-Ping Zheng; Hai-Tao Chen; Si-Yuan Liu; Chen Gu; Zhen-Yang Song (Natural Product Research, 2012)

An Accurate Method of Computing the Gradient of Seismic Wave Reflection Coefficients (SWRCs) for the Inversion of Stratum Parameters - Xiao-Bo Liu; Fu-Ping Liu; Xian-Jun Meng; Jia-Qi Xiao (Surveys in Geophysics, 2012)

Neuroprotection by marine-derived compound, 11-dehydrosinulariolide, in an in vitro Parkinson’s model: a promising candidate for the treatment of Parkinson’s disease - Wu-Fu Chen; Chiranjib Chakraborty; Chun-Sung Sung; Chien-Wei Feng; Yen-Hsuan Jean; Yen-You Lin; Han-Chun Hung; Tzu-Yi Huang; Shi-Ying Huang; Thung-Ming Su; Ping-Jyun Sung; Jyh-Horng Sheu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Fine mapping of 14q24.1 breast cancer susceptibility locus - Phoebe Lee; Yi-Ping Fu; Jonine D. Figueroa; Ludmila Prokunina-Olsson; Jesus Gonzalez-Bosquet; Peter Kraft; Zhaoming Wang; Kevin B. Jacobs; Meredith Yeager; Marie-Josèphe Horner; Susan E. Hankinson; Amy Hutchinson; et al. (Human Genetics, 2012)

Hydrolysis of flavonoid glycosides by propolis β-glycosidase - Cui-Ping Zhang; Gang Liu; Fu-Liang Hu (Natural Product Research, 2012)

The reduction of reactive oxygen species formation by mitochondrial alternative respiration in tomato basal defense against TMV infection - Yang-Wen-Ke Liao; Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; De-Kun Dong; Yu-Ping Jiang; Yan-Hong Zhou; Xiao-Jian Xia; Wu-Sheng Liang; Jing-Quan Yu (Planta, 2012)

Signal transduction during cold, salt, and drought stresses in plants - Guo-Tao Huang; Shi-Liang Ma; Li-Ping Bai; Li Zhang; Hui Ma; Ping Jia; Jun Liu; Ming Zhong; Zhi-Fu Guo (Molecular Biology Reports, 2012)

Orbilia blumenaviensis and its Arthrobotrys anamorph - Min Qiao; Ying Zhang; Shi-Fu Li; H.-O. Baral; E. Weber; Hong-Yan Su; Jian-Ping Xu; Ke-Qin Zhang; Ze-Fen Yu (Mycological Progress, 2012)

Heterotrophic bacterial and Synechococcus spp. Growth and mortality along the inshore-offshore in the East China Sea in summer - An-Yi Tsai; Gwo-Ching Gong; Robert W. Sanders; Kuo-Ping Chiang; Chien-Fu Chao (Journal of Oceanography, 2012)

Speciation in the Rana chensinensis species complex and its relationship to the uplift of the Qinghai–Tibetan Plateau - WEI‐WEI ZHOU; YANG WEN; JINZHONG FU; YONG‐BIAO XU; JIE‐QIONG JIN; LI DING; MI‐SOOK MIN; JING CHE; YA‐PING ZHANG (Molecular Ecology, 2012)
Speciation remains a fundamental issue in biology. Herein, we report an investigation into speciation in the Rana chensinensis species complex using DNA sequence data from one mitochondrial and five nuclear genes. A phylogenetic analysis of the data revealed four major clades in the complex, and each of them was found to likely represent a species, including one cryptic species. Ecological niche models were generated from 19 climatic variables for three of the four major clades, which were represented by widespread sampling, including R. chensinensis , Rana kukunoris and the potential cryptic species. Each clade is associated with a unique ecological unit, and this indicates that ecological divergence probably drove speciation. Ecological divergence is likely related to the late Cenozoic orogenesis of the Qinghai–Tibetan Plateau. In addition, gene flow between species was detected but only in peripheral portions of the ranges of the four major clades, thus likely had little influence on the speciation processes. Discordances between mitochondrial and nuclear genes were also found; the nominal species, R. chensinensis , contains multiple maternal clades, suggesting potential mitochondrial introgression between R. chensinensis and R. kukunoris .

Synthesis of (–)-arctigenin derivatives and their anticancer activity - Chen Gui-Rong; Cai Li-Ping; Dou De-Qiang; Kang Ting-Guo; Li Hong-Fu; Li Fu-Rui; Jiang Ning (Natural Product Research, 2012)

Comparative full-length sequence analysis of Marek’s disease virus vaccine strain 814 - Feng Zhang; Chang-Jun Liu; Yan-Ping Zhang; Zhi-Jie Li; Ai-Ling Liu; Fu-Hai Yan; Feng Cong; Yun Cheng (Archives of Virology, 2012)

Expression of a secretory β-glucosidase from Trichoderma reesei in Pichia pastoris and its characterization - Ping Chen; Xianyu Fu; Tzi Bun Ng; Xiu-Yun Ye (Biotechnology Letters, 2011)

Long-term (1998–2007) trends on the spatial distribution of heterotrophic ciliates in the East China Sea in summer: effect of the Three Gorges Dam construction - An-Yi Tsai; Gwo-Ching Gong; Kuo-Ping Chiang; Chien-Fu Chao; Herng-Ru Guo (Journal of Oceanography, 2011)

Fas/FasL pathway-mediated alveolar macrophage apoptosis involved in human silicosis - San-qiao Yao; Liying Wang Rojanasakul; Zhi-yuan Chen; Ying-jun Xu; Yu-ping Bai; Gang Chen; Xi-ying Zhang; Chun-min Zhang; Yan-qin Yu; Fu-hai Shen; Ju-xiang Yuan; Jie Chen; et al. (Apoptosis, 2011)

Erratum to: Effects of proNGF on Neuronal Viability, Neurite Growth and Amyloid-beta Metabolism - Yan-Jiang Wang; Deborah Valadares; Ying Sun; Xin Wang; Jin-Hua Zhong; Xiao-Hong Liu; Shohreh Majd; Li Chen; Chang-Yue Gao; Si Chen; Yoon Lim; Anthony Pollard; et al. (Neurotoxicity Research, 2011)

The Activation of NMDA Receptor–ERK Pathway in the Central Amygdala is Required for the Expression of Morphine-Conditioned Place Preference in the Rat - Fang Li; Xiao-Sheng Wang; Ru-Ping Dai; Jian-Yi Zhang; Xin-Fu Zhou; Wei Hao; Chang-Qi Li (Neurotoxicity Research, 2011)

Erratum to: Genetic analysis of Down syndrome-associated heart defects in mice - Chunhong Liu; Masae Morishima; Tao Yu; Sei-Ichi Matsui; Li Zhang; Dawei Fu; Annie Pao; Alberto C. Costa; Katheleen J. Gardiner; John K. Cowell; Norma J. Nowak; Michael S. Parmacek; et al. (Human Genetics, 2011)

Genetic analysis of Down syndrome-associated heart defects in mice - Chunhong Liu; Masae Morishima; Tao Yu; Sei-Ichi Matsui; Li Zhang; Dawei Fu; Annie Pao; Alberto C. Costa; Katheleen J. Gardiner; John K. Cowell; Normal J. Nowak; Michael S. Parmacek; et al. (Human Genetics, 2011)

Estimation of rice neck blasts severity using spectral reflectance based on BP-neural network - Hao Zhang; Hao Hu; Xiao-bin Zhang; Lian-feng Zhu; Ke-feng Zheng; Qian-yu Jin; Fu-ping Zeng (Acta Physiologiae Plantarum, 2011)

Levels and Congener Profiles of Particle-bound Polybrominated Dibenzo-p-dioxins/furans (PBDD/Fs) in Ambient Air around Guangzhou, China - Huiru Li; Lin Zhou; Ligui Mo; Ping’an Peng; Guoying Sheng; Jiamo Fu; Zhiqiang Yu (Bulletin of Environmental Contamination and Toxicology, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

Lipopolysaccharide-stimulated activation of murine DC2.4 cells is attenuated by n-butylidenephthalide through suppression of the NF-κB pathway - Ru-Huei Fu; Horng-Jyh Hran; Ching-Liang Chu; Chin-Mao Huang; Shih-Ping Liu; Yu-Chi Wang; Ya-Hsien Lin; Woei-Cherng Shyu; Shinn-Zong Lin (Biotechnology Letters, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Molecular characterisation of cereal cyst nematodes in winter wheat on the Huang-Huai floodplain of China using RFLP and rDNA-ITS sequence analyses - Bo Fu; Hong-xia Yuan; Yu Zhang; Xing-song Hou; Gao-lei Nian; Peng Zhang; Xiao-ping Xing; Bing-jian Sun; Ian T. Riley; Hong-lian Li (Australasian Plant Pathology, 2011)

Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells - Ping Lin; Jiejun Fu; Binjiahui Zhao; Feng Lin; Haifeng Zou; Leiyu Liu; Cheng Zhu; Hongmei Wang; Xiaoguang Yu (Molecular Biology Reports, 2011)

A large indel mutation of the bovine ADD1/SREBP1c gene and its effects on growth traits in some native cattle breeds from China - Yong-Zhen Huang; En-Ping Zhang; Jing Wang; Yong-Tao Huai; Liang Ma; Fu-Ying Chen; Xian-Yong Lan; Chu-Zhao Lei; Xing-Tang Fang; Ju-Qiang Wang; Hong Chen (Molecular Biology Reports, 2011)

Chronosequence of paddy soils and phosphorus sorption–desorption properties - Ping Zou; Jianrong Fu; Zhihong Cao (Journal of Soils and Sediments, 2011)

Molecular Identification and Physiological Characterization of a Putative Novel Plasma Membrane Protein from Arabidopsis Involved in Glucose Response - Moon-Soo Chung; Ping Huang; Chan Man Ha; Ji Hyung Jun; Sung-Ju Ahn; Fu-chun Zhang; Hyun-Jong Bae; Baik Ho Cho; Cheol Soo Kim (Journal of Plant Biology, 2011)

Three novel SNPs in the coding region of PPARγ gene and their associations with meat quality traits in cattle - Yue Yuan Fan; Lin Sen Zan; Chang Zhen Fu; Wan Qiang Tian; Hong Bao Wang; Yan Yan Liu; Ya Ping Xin (Molecular Biology Reports, 2011)

Anticancer Drug-Loaded Nanospheres Based on Biodegradable Amphiphilic ε-Caprolactone and Carbonate Copolymers - Guo-Ping Yan; Rong-Feng Zong; Liang Li; Ting Fu; Fan Liu; Xiang-Hua Yu (Pharmaceutical Research, 2010)

Effect of high glucose levels on the calcification of vascular smooth muscle cells by inducing osteoblastic differentiation and intracellular calcium deposition via BMP-2/Cbfα-1 pathway - Fang Liu; Hui Zhong; Jing-yuan Liang; Ping Fu; Zhi-juan Luo; Li Zhou; Rong Gou; Jun Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Microbial dynamics in an oligotrophic bay of the western subtropical Pacific: Impact of short-term heavy freshwater runoff and upwelling - An-Yi Tsai; Gwo-Ching Gong; Robert W. Sanders; Chien-Fu Chao; Kuo-Ping Chiang (Journal of Oceanography, 2010)

Th17 promotes acute rejection following liver transplantation in rats - Xiao-jun Xie; Yu-fu Ye; Lin Zhou; Hai-yang Xie; Guo-ping Jiang; Xiao-wen Feng; Yong He; Qin-fen Xie; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Research on flux of dry atmospheric falling dust and its characterization in a subtropical city, Guangzhou, South China - Jinping Zhao; Ping’an Peng; Jianzhong Song; Shexia Ma; Guoying Sheng; Jiamo Fu (Air Quality, Atmosphere & Health, 2010)

Effects of Artemisinin Derivative on the Growth Metabolism of Tetrahymena thermophila BF5 Based on Expression of Thermokinetics - Xue-Song Shen; Qi Su; Zhuang-ping Qiu; Jing-yi Xu; Yan-xia Xie; Han-fu Liu; Yi Liu (Biological Trace Element Research, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Meiotic nondisjunction in resynthesized Brassica napus and generation of aneuploids through microspore culture and their characterization - Jing Wen; Xin-hua Zeng; Yuan-yuan Pu; Li-ping Qi; Zai-yun Li; Jin-xing Tu; Chao-zhi Ma; Jin-xiong Shen; Ting-dong Fu (Euphytica, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Effects of proNGF on Neuronal Viability, Neurite Growth and Amyloid-beta Metabolism - Yan-Jiang Wang; Deborah Valadares; Ying Sun; Xin Wang; Jin-Hua Zhong; Xiao-Hong Liu; Shohreh Majd; Li Chen; Chang-Yue Gao; Si Chen; Yoon Lim; Anthony Pollard; et al. (Neurotoxicity Research, 2010)

Expression and characterization of Momordica Chanrantia anti-hyperglycaemic peptide in Escherichia coli - Si-Xiu Liu; Zhong-Ping Fu; Rui-Min Mu; Zhi-Bi Hu; Fu-Jun Wang; Xiang-Rong Wang (Molecular Biology Reports, 2010)

Isopentenyl transferase gene (ipt) downstream transcriptionally fused with gene expression improves the growth of transgenic plants - Jian-Chun Guo; Rui-Jun Duan; Xin-Wen Hu; Kai-Mian Li; Shao-Ping Fu (Transgenic Research, 2010)

Protective effect of selaginellin on glutamate-induced cytotoxicity and apoptosis in differentiated PC12 cells - Chen-Jing Wang; Chang-Ping Hu; Kang-Ping Xu; Qiong Yuan; Fu-Shuang Li; Hui Zou; Gui-Shan Tan; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Pancreatic somatostatinoma with obscure inhibitory syndrome and mixed pathological pattern - Bo Zhang; Qiu-ping Xie; Shun-liang Gao; Yan-biao Fu; Yu-lian Wu (Journal of Zhejiang University-SCIENCE B, 2010)

cDNA cloning and expression analysis of a putative decarbonylase TaCer1 from wheat (Triticum aestivum L.) - Xiaojun Hu; Zhengbin Zhang; Weiqiang Li; Zhenyan Fu; Shuxin Zhang; Ping Xu (Acta Physiologiae Plantarum, 2009)

Protein phosphatase 1A (PPM1A) is involved in human cytotrophoblast cell invasion and migration - Baohua Zhang; Zhi Zhou; Haiyan Lin; Xiaoyin Lv; Jiejun Fu; Ping Lin; Cheng Zhu; Hongmei Wang (Histochemistry and Cell Biology, 2009)

Embryo and anther regulation of the mabinlin II sweet protein gene in Capparis masaikai Lévl - Xin-Wen Hu; Si-Xin Liu; Jian-Chun Guo; Ji-Tao Li; Rui-Jun Duan; Shao-Ping Fu (Functional & Integrative Genomics, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Dong Niu; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Necessity of Screening Water Chestnuts for Microcystins After Cyanobacterial Blooms Break Out - Fu-Gang Xiao; Xiao-Lian Zhao; Jian Tang; Xiao-Hong Gu; Jing-Ping Zhang; Wei-Min Niu (Archives of Environmental Contamination and Toxicology, 2009)

Protective effect of DNA-mediated immunization with liposome-encapsulated GRA4 against infection of Toxoplasma gondii - Rui Chen; Shao-hong Lu; Qun-bo Tong; Di Lou; Dong-yan Shi; Bing-bing Jia; Guo-ping Huang; Jin-fu Wang (Journal of Zhejiang University-SCIENCE B, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Niu Dong; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

A value chain approach to crisis response system: the case of Qingdao - Jian Hua Li; Zheng Ping Zhang; Rui Huan Jing; Chong Fu Huang (Stochastic Environmental Research and Risk Assessment, 2009)

Heavy metal contamination in soil alongside mountain railway in Sichuan, China - Hao Liu; Li-Ping Chen; Ying-Wei Ai; Xia Yang; Yan-Hua Yu; Yuan-Bin Zuo; Guo-Yong Fu (Environmental Monitoring and Assessment, 2009)

Protective effects of N-acetylcysteine in isoproterenol-induced myocardium injury in rats - Bin Liu; Weimin Li; Yue Li; Zhonghua Wang; Hongli Li; Ping Liu; Jun Fu (Molecular Biology Reports, 2009)

A High Polymorphism Level in Rhinopithecus roxellana - Deng Pan; Hong-Xing Hu; Shi-Jie Meng; Zheng-Ming Men; Yun-Xin Fu; Ya-Ping Zhang (International Journal of Primatology, 2009)

Somatic Embryogenesis and in vitro Flowering in Saposhnikovia divaricata - Qi Qiao; Fu-Wu Xing; Ya-Ping Xiao; Hong-Feng Chen (Journal of Plant Growth Regulation, 2009)

Generation of a stable mammalian cell line for simultaneous expression of multiple genes by using 2A peptide-based lentiviral vector - Tao Hu; Qiong Fu; Ping Chen; Ke Zhang; Deyin Guo (Biotechnology Letters, 2009)

On-site variety discrimination of tomato plant using visible-near infrared reflectance spectroscopy - Hui-rong Xu; Peng Yu; Xia-ping Fu; Yi-bin Ying (Journal of Zhejiang University-SCIENCE B, 2009)

Determination of soluble solid content and acidity of loquats based on FT-NIR spectroscopy - Xia-ping Fu; Jian-ping Li; Ying Zhou; Yi-bin Ying; Li-juan Xie; Xiao-ying Niu; Zhan-ke Yan; Hai-yan Yu (Journal of Zhejiang University-SCIENCE B, 2009)

Determination of Microcystin-LR in Water from Lake Tai, China - Fu-Gang Xiao; Xiao-Lian Zhao; Jian Tang; Xiao-Hong Gu; Jing-Ping Zhang; Wei-Min Niu (Bulletin of Environmental Contamination and Toxicology, 2009)

Identification, expression and tissue distribution of a renalase homologue from mouse - Jian Wang; Shaoling Qi; Wei Cheng; Li Li; Fu Wang; Ying-Zi Li; Shu-Ping Zhang (Molecular Biology Reports, 2008)

Increased pathogenesis and inflammation of airways from respiratory syncytial virus infection in T cell deficient nude mice - Juan Zhou; Xi-Qiang Yang; Zhou Fu; Xiao-Dong Zhao; Li-Ping Jiang; Li-Jia Wang; Yu-Xia Cui (Medical Microbiology and Immunology, 2008)

Ambient air monitoring of Beijing MSW logistics facilities in 2006 - Chun-Ping Li; Guo-Xue Li; Yi-Ming Luo; Yan-Fu Li (Environmental Monitoring and Assessment, 2008)

Group Time Delay in the Reflection of P-Polarized Electromagnetic Plane Waves at a Stratigraphic Interface - Fu-Ping Liu; Rui-Zhong Li; Jin-yao Li; Hui-Guo Chen; Chang-Chun Yang (Mathematical Geosciences, 2008)

A simple and effective method for total RNA isolation of appressoria in Magnaporthe oryzae - Tong-bao Liu; Jian-ping Lu; Xiao-hong Liu; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Light distribution, photosynthetic rate and yield in a Paulownia-wheat intercropping system in China - Fangdong Li; Ping Meng; Dali Fu; Baoping Wang (Agroforestry Systems, 2008)

Strategic Zoning for Urban Wastewater Reuse in China - Siyu Zeng; Jining Chen; Ping Fu (Water Resources Management, 2008)

Effect of moisture transport on microclimate under T-shirts - Xiao-Qun Dai; Ritsuko Imamura; Guo-Lian Liu; Fu-Ping Zhou (European Journal of Applied Physiology, 2008)

Review of Holocene glacial chronologies based on radiocarbon dating in Tibet and its surrounding mountains - Chaolu Yi; Hualiang Chen; Jianqiang Yang; Bin Liu; Ping Fu; Kexin Liu; Shijie Li (Journal of Quaternary Science, 2008)
A compilation of 53 14 C ages on moraines constrains the Holocene glacial history of Tibet and the surrounding mountains. Several Holocene glacial stages are identified. The Little Ice Age had three substages at 1.0–0.13 cal. ka BP. However, the glacial advances may have occurred 200–600 a earlier in southern and eastern bordering mountains than in the northern bordering mountains. The earlier glacial advance might have been driven by humid conditions in bordering areas of Tibet. Most glacial advances in the Neoglaciation occurred at 3.5–1.4 cal. ka BP. They can be identified in almost every mountain range. An early Holocene glacial advance occurred 9.4–8.8 cal. ka BP, in both central Tibet and bordering mountains. The timings of Holocene glacial advances are synchronous with the cooling periods in the δ 18 O record from ice cores and with the results of optically stimulated luminescence dating and cosmogenic exposure dating in Tibet. Copyright © 2008 John Wiley & Sons, Ltd.

Trade-offs between constitutive and induced resistance in wild crucifers shown by a natural, but not an artificial, elicitor - Peng-Jun Zhang; Jin-Ping Shu; Cheng-Xin Fu; Yun Zhou; Ying Hu; Myron P. Zalucki; Shu-Sheng Liu (Oecologia, 2008)

Magnaporthe oryzae MTP1 gene encodes a type III transmembrane protein involved in conidiation and conidial germination - Qin Lu; Jian-ping Lu; Xiao-dong Li; Xiao-hong Liu; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Application of NIR spectroscopy for firmness evaluation of peaches - Xia-ping FU; Yi-bin Ying; Ying Zhou; Li-juan Xie; Hui-rong Xu (Journal of Zhejiang University-SCIENCE B, 2008)

Solid lipid nanoparticles loading adefovir dipivoxil for antiviral therapy - Zhang Xing-guo; Miao Jing; Li Min-wei; Jiang Sai-ping; Hu Fu-qiang; Du Yong-zhong (Journal of Zhejiang University-SCIENCE B, 2008)

Evidence of Gene Conversion in the Evolutionary Process of the Codon 41/42 (-CTTT) Mutation Causing β-Thalassemia in Southern China - Wen Zhang; Wang-Wei Cai; Wei-Ping Zhou; Hai-Peng Li; Liang Li; Wei Yan; Qin-Kai Deng; Ya-Ping Zhang; Yun-Xin Fu; Xiang-Min Xu (Journal of Molecular Evolution, 2008)

Chymase induces profibrotic response via transforming growth factor-β1/Smad activation in rat cardiac fibroblasts - Xiao-Yan Zhao; Lian-You Zhao; Qiang-Sun Zheng; Jin-Lin Su; Hao Guan; Fu-Jun Shang; Xiao-Lin Niu; Yan-Ping He; Xiao-Long Lu (Molecular and Cellular Biochemistry, 2008)

Evolution of subcontinental lithospheric mantle beneath eastern China: Re–Os isotopic evidence from mantle xenoliths in Paleozoic kimberlites and Mesozoic basalts - Hong-Fu Zhang; Steven L. Goldstein; Xin-Hua Zhou; Min Sun; Jian-Ping Zheng; Yue Cai (Contributions to Mineralogy and Petrology, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Molecular and functional comparisons of the vacuolar Na+/H+ exchangers originated from glycophytic and halophytic species - Jin-yao Li; Xiao-wei He; Li Xu; Jie Zhou; Ping Wu; Hui-xia Shou; Fu-chun Zhang (Journal of Zhejiang University-SCIENCE B, 2008)

Amperometric glucose biosensors based on layer-by-layer assembly of chitosan and glucose oxidase on the Prussian blue-modified gold electrode - Bing Yin; Ruo Yuan; Yaqing Chai; Shihong Chen; Shurui Cao; Yang Xu; Ping Fu (Biotechnology Letters, 2008)

Loop-mediated isothermal amplification for rapid detection of Bacillus anthracis spores - Yan-Mei Qiao; Yong-Chao Guo; Xian-En Zhang; Ya-Feng Zhou; Zhi-Ping Zhang; Hong-Ping Wei; Rui-Fu Yang; Dian-Bing Wang (Biotechnology Letters, 2007)

Identification and expression analysis of hepcidin-like cDNAs from pigeon (Columba livia) - Yu Ming Fu; Su Ping Li; Yue Feng Wu; Yan Zhong Chang (Molecular and Cellular Biochemistry, 2007)

Mitochondrial Control Region and Population Genetic Patterns of Nycticebus bengalensis and N. pygmaeus - Deng Pan; Jing-Hua Chen; Colin Groves; Ying-Xiang Wang; Etsuo Narushima; Helena Fitch-Snyder; Paul Crow; Xiangyu Jinggong; Vu Ngoc Thanh; Oliver Ryder; Leona Chemnick; Hong-Wei Zhang; et al. (International Journal of Primatology, 2007)

Deep lingual arterial chemoembolization of tongue carcinoma with microcapsuled anticancer drug - Hong He; Jian-qi Huang; Fei-yun Ping; Guan-fu Chen; Su-zhan Zhang (Journal of Zhejiang University-SCIENCE B, 2007)

Cloning, sequencing and expression analysis of the NAR promoter activated during hyphal stage of Magnaporthe grisea - Jian-ping Lu; Zhi-bing Duan; Tong-bao Liu; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Fibrarecisin, a novel triterpenoid from Fibraurea recisa with antitumor activity - Jiao-Long Fu; Chang-Heng Tan; Li-Ping Lin; Ji Huang; Da-Yuan Zhu (Natural Product Research, 2007)

Assignment of CCR7 gene to chicken chromosome 27 by radiation hybrid panel mapping - Yong Tian; Li-zhi Lu; Yan Fu; Zheng-rong Tao; Jun-da Shen; De-qian Wang; Ai-ping Yuan; Zhao-zheng Yin (Journal of Zhejiang University-SCIENCE B, 2007)

Measurement of soluble solids content in watermelon by Vis/NIR diffuse transmittance technique - Hai-qing Tian; Yi-bin Ying; Hui-shan Lu; Xia-ping Fu; Hai-yan Yu (Journal of Zhejiang University-SCIENCE B, 2007)

Ex vivo expansion and pluripotential differentiation of cryopreserved human bone marrow mesenchymal stem cells - Ying Xiang; Qiang Zheng; Bing-bing Jia; Guo-ping Huang; Yu-lin Xu; Jin-fu Wang; Zhi-jun Pan (Journal of Zhejiang University-SCIENCE B, 2007)

Identification of poly-reactive natural IgM antibody that recognizes late apoptotic cells and promotes phagocytosis of the cells - Meng Fu; Ping-shen Fan; Wei Li; Cheng-xin Li; Ying Xing; Jing-gang An; Gang Wang; Xue-li Fan; Tian-wen Gao; Yu-feng Liu; Shigaku Ikeda (Apoptosis, 2007)

Molecular Phylogeny of Nycticebus Inferred from Mitochondrial Genes - Jing-Hua Chen; Deng Pan; Colin Groves; Ying-Xiang Wang; Etsuo Narushima; Helena Fitch-Snyder; Paul Crow; Vu Ngoc Thanh; Oliver Ryder; Hong-Wei Zhang; Yun-xin Fu; Ya-ping Zhang (International Journal of Primatology, 2006)

Application Fourier transform near infrared spectrometer in rapid estimation of soluble solids content of intact citrus fruits - Hui-shan Lu; Hui-rong Xu; Yi-bin Ying; Xia-ping Fu; Hai-yan Yu; Hai-qing Tian (Journal of Zhejiang University-SCIENCE B, 2006)

High RAPD but no cpDNA sequence variation in the endemic and endangered plant, Heptacodium miconioides Rehd. (Caprifoliaceae) - Hui-Ping Lu; Yue-Wei Cai; Xiao-Yong Chen; Xin Zhang; Yong-Jie Gu; Guang-Fu Zhang (Genetica, 2006)

Identification and characterization of piggyBac-like elements in the genome of domesticated silkworm, Bombyx mori - Han-Fu Xu; Qing-You Xia; Chun Liu; Ting-Cai Cheng; Ping Zhao; Jun Duan; Xing-Fu Zha; Shi-Ping Liu (Molecular Genetics and Genomics, 2006)

Promoter trapping in Magnaporthe grisea - Xiao-hong Liu; Jian-ping Lu; Jiao-yu Wang; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2006)

Identification and expression analysis of alternatively spliced isoforms of human interleukin-23 receptor gene in normal lymphoid cells and selected tumor cells - Xiang-Yue Zhang; Hai-Jing Zhang; Yun Zhang; Ying-Jie Fu; Jie He; Li-Ping Zhu; Shu-Hui Wang; Li Liu (Immunogenetics, 2006)

Prediction of valid acidity in intact apples with Fourier transform near infrared spectroscopy - Yan-de Liu; Yi-bin Ying; Xia-ping Fu (Journal of Zhejiang University-SCIENCE B, 2005)

Representative appressorium stage cDNA library of Magnaporthe grisea - Jian-ping Lu; Tong-bao Liu; Xiao-yun Yu; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2005)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

Removal of dibutyl phthalate by a staged, vertical-flow constructed wetland - Wen Yu Zhao; Zhen Bin Wu; Qiao Hong Zhou; Shui Ping Cheng; Gui Ping Fu; Feng He (Wetlands, 2004)

Michael addition of imidazole with acrylates catalyzed by alkaline protease from Bacillus subtilis in organic media - Ying Cai; Shi-Ping Yao; Qi Wu; Xian-Fu Lin (Biotechnology Letters, 2004)

Insulin 3: From chemical synthesis to biological function - Ping Fu; Ross A. D. Bathgate; Geoffrey W. Tregear; John D. Wade (International Journal of Peptide Research and Therapeutics, 2003)

Use of oligonucleotide fingerprinting and faecal DNA in identifying the distribution of the Chinese tiger (Panthera tigris amoyensis Hilzheimer) - Qiu-Hong Wan; Sheng-Guo Fang; Guo-Fu Chen; Zhang-Ming Wang; Ping Ding; Mu-Yuan Zhu; Kong-Shou Chen; Jiu-Hua Yu; Yue-Ping Zhao (Biodiversity and Conservation, 2003)

The Origin and Genetic Diversity of Chinese Native Chicken Breeds - Dong Niu; Yan Fu; Jing Luo; Hui Ruan; Xu-Ping Yu; Gong Chen; Ya-Ping Zhang (Biochemical Genetics, 2002)

Concept, distribution law and formation machanism of inland saline-alkaline wetland - Guang-you Sun; Xin-zheng Luo; Fu-ke Yi; Xiao-ping Zhang (Chinese Geographical Science, 2000)

Oxidative modification of lipoproteins in hypertriglyceridemic patients and hypercholesterolemic rabbits in vivo - Bing W. Liu; Yu Jiang; Ming D. Fu; Yu Liu; Ping Fan (Molecular and Cellular Biochemistry, 2000)

The effects of spaceflight on soluble protein, isoperoxidase, and genomic DNA in ural licorice (Glycyrrhiza uralensis fisch.) - Wen-Yuan Gao; Rong-Zhao Fu; Lei Fan; Shu-Ping Zhao; Kee-Yoeup Paek (Journal of Plant Biology, 2000)

Mitochondrial Genetic Variation in Chinese Pigs and Wild Boars - Yong-Fu Huang; Xian-Wei Shi; Ya-Ping Zhang (Biochemical Genetics, 1999)

Genetic Diversity of Cattle in South China as Revealed by Blood Protein Electrophoresis - Long Nie; Ying Yu; Xi-Quan Zhang; Guan-Fu Yang; Ji-Kun Wen; Ya-Ping Zhang (Biochemical Genetics, 1999)

Biology and life history of Dabry's sturgeon, Acipenser dabryanus, in the Yangtze River - Ping Zhuang; Fu'en Ke; Qiwei Wei; Xuefu He; Yuji Cen (Environmental Biology of Fishes, 1997)

Biology, fisheries, and conservation of sturgeons and paddlefish in China - Qiwei Wei; Fu'en Ke; Jueming Zhang; Ping Zhuang; Junde Luo; Rueqiong Zhou; Wenhua Yang (Environmental Biology of Fishes, 1997)